The “Too-Few Elephant Problem”: Quantitative Analysis of Historical Elephant Tree-Toppling Rates Across Africa - Sally Archibald; Anya P. Courtenay; Fezile Mtsetfwa; Domingos Fortunato P. F. da Silva; Katherine Bunney; Robert Guldemond; Penny Mograbi; Caitlin Ransom; Casey M. Ryan; Norman Owen-Smith (Ecosystems, 2026)
Elephants were a major driver of tree stem mortality in Africa, but their impacts are now spatially constrained and they no longer topple trees across the continent. Thus, most African landscapes lack a key ecological agent that helped maintain diversity and functioning. Even ecologists living in Africa fail to anticipate the rampant destruction of trees that can occur when elephants live in and move through landscapes. If we can build in a consensus on the degree of above-ground tree turnover that is inherent in different contexts, it would inform restoration projects and ecological definitions of degradation. We collated empirical data on treefall in ecosystems with and without elephants and predicted past tree loss spatially. The metrics used (%trees or #trees ha −1 ) reveal assumptions about the processes controlling elephant damage. On average elephants knock down 5.4 [IQR 3.0–8.3] % of the trees in an ecosystem per annum. Mapping this into places that no longer contain elephants reveals the above-ground biomass turnover that would have been the norm for millennia before elephants were widely exterminated. On average, this is ~ 1/3 of woody biomass production but at a local scale it can often exceed production. There is an urgent need for better theory on elephant tree interactions, and restoration projects should embrace the rapid turnover dynamics these ecosystems evolved with.

Antibiofilm efficacy of zwitterionic 2-methacryloloxyethyl phosphorylcholine (MPC) polymer coatings against Vibrio fischeri - Murchana Sarma; Ryan P.O’ Hara; Ashfaqul Hoque Khadem; Manas D. Warke; Lihua Lou; Ayse Asatekin; Debora F. Rodrigues (Water Research, 2026)

Immune system evaluation of Echinacea Purpurea root extract in female Harlan Sprague Dawley (Hsd:Sprague Dawley SD) rats - Victor J. Johnson; Suramya Waidyanatha; Dori R. Germolec; Michelle C. Cora; Mark F. Cesta; Keith R. Shockley; Angela Jeffers; Karen Cimon; Esra Mutlu; Tim Cristy; Jessica Pierfellice; Michael I. Luster; et al. (Food and Chemical Toxicology, 2026)

Observation of urban karst flows inform planning, design and construction of green stormwater infrastructure - Kathryn M. Boening-Ulman; R. Andrew Tirpak; Jay F. Martin; Alessandra S. Braswell; William F. Hunt; Ryan J. Winston (Journal of Hydrology, 2026)

Associations between perfluoroalkyl substances and multiple sclerosis in U.S. cohorts compared with NMOSD, MOGAD, and healthy controls - Farren B.S. Briggs; Federico Montini; Charles F. Spurlock; Christine Ryan; Jessica N. Cooke Bailey; Erika S. Trapl; Guzel I. Shaginurova; Lukasz S. Wylezinski; Cheryl L. Sesler; Mahboobeh Fereidan Esfahani; Jessica Sagen; Hannah E. Gardener; et al. (Environmental Research, 2026)

Assessment of microneedle array insertion into skin using Raman spectroscopic techniques - Rezvan Jamaledin; Panagiota Zarmpi; Adrián M. Alambiaga-Caravaca; Vasundhara Tyagi; Qonita Kurnia Anjani; Eneko Larrañeta; Ryan F. Donnelly; Natalie A. Belsey; Richard H. Guy; M. Begoña Delgado-Charro (Drug Delivery and Translational Research, 2026)

Tipping the balance: reef community shifts after a regional urchin population collapse - Nicolas Rivas; W. Ryan James; Valentina Bautista; Madison Sandquist; Arianna F. Guerriero; Silvana B. Arias; Alex E. Mercado-Molina; Jennifer Rehage; Rolando O. Santos (Coral Reefs, 2026)

Corrigendum to “Tip loaded cyclodextrin-carvedilol complexes microarray patches” [Carbohydrate Polymers Volume 320, 15 November 2023, 121194] - Qonita Kurnia Anjani; Akmal Hidayat Bin Sabri; Khuriah Abdul Hamid; Natalia Moreno-Castellanos; Huanhuan Li; Ryan F. Donnelly (Carbohydrate Polymers, 2026)

Assessment of the occurrence of phthalate esters (PAEs) in indoor office PM2.5 from Brazil and the UK - Cristian Ryan A. Argamino; Jéssica dos Santos Silva; Jishnu Pandamkulangara Kizhakkethil; Svetlana Stevanovic; Martyn Ward; Matthew McKenzie; Anna Bogush; Jacqueline F. Hamilton; Ricardo H.M. Godoi; Ivan Kourtchev (Atmospheric Pollution Research, 2026)

Dietary nitrate supplementation does not improve resistance exercise performance in resistance-trained women - Sydney N. Brennan; Justin M. Foster; Raymond T. Gerardo; Trevor J. Molnar; Ryan Tran; Christopher B. Sottile; Kyle S. Geppert; Michael Egiazarian; Abigail F. Ballhagen; Money Ghimire; John R. M. Renwick; Lewis A. Gough; et al. (European Journal of Applied Physiology, 2026)

Versatile and sensitive dual-detection HPLC method for rapid quantification of apomorphine hydrochloride: application to ex vivo percutaneous permeation and deposition studies utilising novel transdermal pressure-sensitive adhesive patches - Andrew P. Graham; Qonita Kurnia Anjani; René Holm; Alejandro J. Paredes; Ryan F. Donnelly (Drug Delivery and Translational Research, 2026)

Baleen Whale Occurrence in the Waters Off Virginia and North Carolina, U.S.A. From 2001 to 2019 - Sarah D. Mallette; William A. McLellan; D. Ann Pabst; M. Louise Burt; Ryan J. McAlarney; Gwendolyn G. Lockhart; Erin W. Cummings; Joel T. Bell; Matthew B. Ogburn; Philip K. Hamilton; Andrew J. Read; Robert L. Brownell; et al. (Marine Mammal Science, 2026)
Eighteen years of visual survey and strandings data were used to describe baleen whale occurrence along the continental shelf of Virginia and North Carolina, U.S.A. This region experiences heavy anthropogenic use, which poses risks for mortality and injury to baleen whales. Between 2001 and 2019, six species of baleen whales were recorded, and whales occurred year‐round. The total number of (on‐ and off‐effort) sightings and strandings amounted to 838 whales, including humpback ( Megaptera novaeangliae , n = 503) , fin ( Balaenoptera physalus , n = 197) , North Atlantic right ( Eubalaena glacialis , NARW, n = 76 ), common minke ( B. acutorostrata , n = 51), sei ( B. borealis , n = 10), and blue ( B. musculus , n = 1) whales. Spatial modeling and abundance estimates indicated whale density and distribution changed seasonally. The highest densities of all whales combined occurred in winter and spring. Across seasons, average densities were highest in the northern portion of the study area. Ninety percent of NARW sightings were outside the designated Seasonal Management Areas in place for their protection. The stranding record offered a complementary view of species richness and seasonality. This study provides a baseline of baleen whale occurrence in an area experiencing increasing anthropogenic pressures (e.g., ship traffic and offshore wind‐energy development).

Adaptation and Response in Drylands: A Dryland Research Agenda and Campaign Strategy - Andrew F. Feldman; Sasha C. Reed; Konrad Wessels; Dennis Ojima; David J. P. Moore; William K. Smith; Niall P. Hanan; Cibele Amaral; Flurin Babst; Joel A. Biederman; Marcy Litvak; Natasha MacBean; et al. (Global Change Biology, 2026)
Dryland ecosystems cover 41% of Earth's land surfaces, account for 44% of cultivated lands and 60% of food sources, and make large contributions to the global water and carbon cycles. However, these ecosystems are experiencing unprecedented extremes including heatwaves, floods, and droughts as well as hotter temperatures and often declining water resource availability. These ecosystems are some of the most challenging to monitor given their high temporal variability with rapid response to their environment as well as vast spatial variability with intermixing of different plant species and life forms amongst bare soil coverage. The Adaptation and Response in Drylands (ARID) campaign was selected by National Aeronautics and Space Administration (NASA) as a scoping study to develop a research agenda for a dryland field campaign. Here, we detail our ARID science research agenda and implementation plan that were developed based on an extensive community engagement effort in over 160 events with over a thousand scientists, land managers, and Tribal communities between 2023 and 2024. The selected science themes cover drought and climate variability, ecosystem structure, function, and biodiversity, carbon cycle interannual variability and trends, and social ecological systems (land management and adaptation). We then detail our remote sensing, modeling, and field‐based strategies to capture high temporal and high spatial resolution processes. Finally, our implementation strategy is presented which includes focus area selections in a core intensive western U.S. domain and distributed international domains. This strategy includes our overarching guiding principles of using multi‐temporal airborne acquisitions and super sites as well as enhancing land management in co‐development with end‐user partners. While originally developed for NASA, our ARID report creates a blueprint for any future dryland field campaign, at any scale, that can be implemented widely for foundational and applied science objectives.

Universal Thermal Climate Index (UTCI)-adjusted pedestrian accessibility: Urban design exploration for climate-resilience in tropical climates - Elif Esra Aydin; Zebin Chen; F. Peter Ortner; Jing Zhi Tay; Kelvin Li; Ryan Chua (Sustainable Cities and Society, 2026)

Integrating experiments, numerical simulations and Bayesian optimisation to maximise drug permeability of hollow pyramidal microneedle arrays - Ravi Prakash; Rahul Nadda; Abraham M. Abraham; Tahir Emre Yalcin; Ryan F. Donnelly; Diganta Bhusan Das (Chemical Engineering Journal, 2026)

The geochemical and isotopic composition of the Miocene Vestfirðir basalts, Northwest Iceland: Tracking the evolution of the Iceland mantle plume - Ugur Balci; Emma Martin-Roberts; Björn Hardarson; J. Godfrey Fitton; Valerie Olive; Ryan Ickert; Darren F. Mark; Finlay M. Stuart (Chemical Geology, 2026)

Efficacy and safety of pemvidutide in metabolic dysfunction-associated steatohepatitis: a GRADE-assessed meta-analysis of randomized controlled trials - Islam Rajab; Ahmed Emara; Mohamed Saad Rakab; Ahmed Adel Abdel Azim; Heba Aboeldahab; Omar F. Abbas; Ryan A. Rahman; Raffi Karagozian (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Selecting Suitable Nitrogen Offset Strategies In Tropical And Subtropical Regions Globally With Implications To The Great Barrier Reef, Australia - Diego F. Correa; Ryan D. R. Turner; Martine Maron; Lina M. González-González; Michele A. Burford; Jing Lu; Joanne Burton; Joseph McMahon; Debra Chamberlain; Yongjing Mao; Hugh Possingham; Michael St. J. Warne (Environmental Management, 2026)
Water pollution from agricultural, industrial, and urban activities threatens aquatic ecosystems and the essential services they provide. Excess nitrogen has been identified as a key driver of water quality degradation, impacting biodiversity, food security, and human health. One approach to mitigating nitrogen pollution is water quality offsetting, compensating for pollution impacts by implementing nitrogen reduction measures elsewhere to achieve no net decline in water quality. Selecting and implementing suitable nitrogen offset types remains challenging. This study presents a framework for identifying, selecting, and implementing effective nitrogen offset strategies in tropical and subtropical regions globally, using the Great Barrier Reef Catchment Area (GBRCA) as an example. This framework is based on the premise that effective nitrogen offset design requires integrating evidence on nitrogen mitigation performance, appropriate criteria for selecting offset types, and adaptive management to address uncertainty in environmental outcomes. Accordingly, the framework comprises three interrelated components: (1) assessment of water quality improvement methods for nitrogen reduction in the GBRCA and other tropical and subtropical regions based on performance (i.e., efficacy, effectiveness, and efficiency); (2) selection of suitable offset types based on their performance, co-benefits, and spatial and technical feasibility; and (3) integration of adaptive management strategies, Geographic Information Systems (GIS) tools, and monitoring systems to strengthen the effectiveness of nitrogen offsetting. This is the first global assessment of nitrogen offset performance in tropical and subtropical regions, offering insights to improve water quality management through offsetting. This framework is adaptable to other regions and pollutants, guiding effective offset implementation to enhance watershed resilience.

Correction: Preparation, characterisation, and testing of reservoir-based implantable devices loaded with tizanidine and lidocaine - Camila J. Picco; Mihir S. Bhalerao; Octavio E. Fandino; Elizabeth R. Magill; Qonita Kurnia Anjani; Jonathan G. Acheson; Ryan F. Donnelly; Juan Domínguez-Robles; Eneko Larrañeta (Drug Delivery and Translational Research, 2026)

A framework to inform economic valuation of non-use benefits from coral reef intervention efforts - Ryan F. Heneghan; Gabriela Scheufele; Yves-Marie Bozec; Anna K. Cresswell; Christopher Doropoulos; Katharina E. Fabricius; Renata Ferrari; Manuel Gonzalez-Rivero; Marji Puotinen; Ken Anthony (Coral Reefs, 2026)
Healthy coral reefs hold significant value to society, not just from industries such as tourism or fishing, but by their very existence. These so-called ‘non-use benefits’ are increasingly endangered as the health of coral reefs faces escalating threats from climate change. Yet, current observation and modelling tools that help guide reef intervention efforts typically do not provide guidance on how the impact of management actions on reef ecology flows through to changes in non-use benefits. Here, we demonstrate how ecological metrics, as measured by existing reef observation or modelling tools, can be translated to an economic valuation of non-use benefits from conservation actions on Australia’s Great Barrier Reef (GBR). Using our framework, we find that an additional square kilometre of reef maintained in ‘good’ or ‘very good’ condition by an intervention, from 2026 to 2100, generates a median present value of ~ $4.7 million (2025 Australian dollars) in non-use benefits for the Australian public. However, we note that this estimate is surrounded by a high level of uncertainty due to limitations in available source studies used for benefit transfer, with the full range of estimated benefits falling between $0.4–$11.8 million dollars. This substantial uncertainty could be reduced by implementing a non-use valuation study customised to the GBR context. Rigorous and transparent valuation of how reef ecosystem respond to conservation actions is critical, given the rapid rise of private investment in the nature repair market. The framework presented here offers an approach that leverages existing models and expert knowledge and is designed for application to any reef conservation action whose ecological benefits can be measured or modelled.

Correction to: Tipping the balance: reef community shifts after a regional urchin population collapse - Nicolas Rivas; W. Ryan James; Valentina Bautista; Madison Sandquist; Arianna F. Guerriero; Silvana B. Arias; Alex E. Mercado-Molina; Jennifer Rehage; Rolando O. Santos (Coral Reefs, 2026)

Correction: Rangewide population genetic analysis of the Wood Turtle (Glyptemys insculpta) - Andrew R Whiteley; Dana Weigel-Sheedy; Thomas S.B. Akre; Donald J. Brown; Deahn M. Donner; Charlie Eichelberger; Lori Erb; Katharine D. Gipe; Ellery Lassiter; Michael N. Marchand; Tricia Markle; Donald F. McAlpine; et al. (Conservation Genetics, 2026)

Rangewide population genetic analysis of the Wood Turtle (Glyptemys insculpta) - Andrew R. Whiteley; Dana Weigel-Sheedy; Thomas S.B. Akre; Donald J. Brown; Deahn M. Donner; Charlie Eichelberger; Lori Erb; Katharine D. Gipe; Ellery Lassiter; Michael N. Marchand; Tricia Markle; Donald F. McAlpine; et al. (Conservation Genetics, 2026)

Decadal migration timing and temporal variation in dive behavior of an endangered beluga whale population - Kasey P. Ryan; Sean F. Ryan; Mads Peter Heide-Jørgensen; Steven H. Ferguson; Sasha R. X. Dall; James D. Roth; Cortney A. Watt (Frontiers in Marine Science, 2026)
Introduction Understanding migration timing and movement behavior is critical for predicting population responses to environmental changes. The beluga whale ( Delphinapterus leucas ) population in Cumberland Sound, Nunavut, is currently endangered due to historical and ongoing overharvesting. Methods By comparing satellite telemetry data from two distinct time periods (1998–1999 and 2006–2008), we evaluated beluga whale dive behavior and migration timing in relation to environmental and seasonal factors. To infer potential prey shifts, we compared the proportion of dives deeper than 100 m, where Arctic cod ( Boreogadus saida ) are typically found, with shallower dives indicative of capelin ( Mallotus villosus ) foraging. Dive behavior was analyzed in relation to seasonal progression (day of year), time period, ice cover, bottom depth, and sex using mixed-effects models. Migration timing was evaluated using latitudinal thresholds and a transect line to identify the timing and variability of southward autumn movements relative to sea ice formation. Results We found significant seasonal (day of year) variation in dive behavior, with deep dives increasing from September to December. Additionally, there was a notable shift to more shallow dives in the second time period compared to the first, suggesting a change in foraging from Arctic cod to capelin. We found that the whales’ initial movements out of their summering area appeared largely independent of ice phenology, while their movements later in their migration were highly variable. Discussion The shift in prey likely occurred due to changes in prey distribution driven by warmer ocean temperatures, which may have negative long-term impacts on population health. Some of these behavioral trends contrasted with those of other beluga whale populations, emphasizing the need for population-specific management strategies to support long-term survival of the Cumberland Sound beluga whale population.

Preserving the gut microbiome: hydrogel-forming microneedle delivery of tetracycline reduces gut microbiome disruption compared to oral administration - Stephen A. Kelly; Li Zhao; Jonathan Nzakizwanayo; Aoife M. Rodgers; Thomas P. Thompson; Andrew J. Lee; Helen O. McCarthy; John W. McGrath; Rebecca J. Ingram; Brian V. Jones; Brendan F. Gilmore; Ryan F. Donnelly (Drug Delivery and Translational Research, 2026)
Antibiotics cause significant gut microbiome dysbiosis, particularly when administered orally. This contributes to antimicrobial resistance (AMR) and is associated with myriad health conditions. Novel drug delivery strategies that minimize gut exposure while maintaining therapeutic efficacy are urgently needed. This study aimed to evaluate whether a novel transdermal system could reduce gut microbiome disruption compared to oral delivery. Sprague-Dawley rats received a single tetracycline dose via oral gavage, IV injection, or hydrogel-forming microneedle patch. Faecal samples were collected longitudinally and analysed using 16 S rRNA gene sequencing. Oral tetracycline caused the greatest disruption to gut microbiota. Compared to the timepoint immediately prior to treatment (Day 5a), peak dysbiosis was observed at Day 7. The Firmicutes: Bacteroidetes ratio was significantly reduced following oral and IV tetracycline therapy, but not following microneedle administration. The most significant reductions in alpha and beta diversity at Day 7 were observed in the oral group. Differential abundance analysis showed oral treatment resulted in the highest number of depleted and enriched taxa. The microbiome-sparing effect of microneedle delivery was consistent across all analytical measures, offering a promising strategy to preserve host microbiome health. This minimally invasive approach represents a clinically viable alternative to oral and IV antibiotic administration.

Transdermal ropivacaine delivery via hydrogel-forming microneedles: A pain-free alternative for local anaesthesia - Andang Miatmoko; Qonita Kurnia Anjani; Rifda Tarimi Octavia; Natalia Porfiryeva; Febri Annuryanti; Gwan Young Kim; Ji Yeon Heo; Gwangheum Yoon; Ahreum Choi; Ryan F. Donnelly (Drug Delivery and Translational Research, 2026)

Chemical profiling of industry wastewaters to identify industry sources of contaminants - Chantal A. Keane; Rory Verhagen; Jochen F. Mueller; Jake W. O’Brien; Ryan Shiels; Jiaying Li (Water Research, 2026)

The future of evolutionary behavioral biology - Theo C. M. Bakker; James F. A. Traniello; Tim R. Birkhead; Monika Borgerhoff Mulder; Bernard Crespi; Niels J. Dingemanse; Raghavendra Gadagkar; Ashleigh S. Griffin; Mark E. Hauber; Bert Hölldobler; John L. Hoogland; Sarah B. Hrdy; et al. (Behavioral Ecology and Sociobiology, 2026)

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Molecular approaches to increasing plant root carbon - Declan Lafferty; Jacob Calabria; Ryan Lister; Jorge E. Mayer; Michelle Watt; John F. Golz (Trends in Plant Science, 2026)

Assessing the plausibility of direct constraints on ancient atmospheric P CO 2 from fluid inclusions in halite: a theoretical and experimental approach - Michael Naylor Hudgins; Justin G. Park; Alex M. Ryan; Jessika A. Rogers; Morgan F. Schaller (Geochimica et Cosmochimica Acta, 2026)

Incorporating climate-driven disturbance shifts in population models reveals non-additive dynamics - Ryan D. O'Connell; Cecil C. Frost; Kevin Gross; William F. Morris (Biological Conservation, 2026)

Voriconazole nanosuspension-loaded ocular bilayer dissolving microneedle patch for the management of fungal keratitis - B.H. Jaswanth Gowda; Anjali K. Pandya; Shilpkala Gade; Ross Duncan; Alejandro J. Paredes; Mohammed Gulzar Ahmed; Yiwei Tian; Ryan F. Donnelly; Raghu Raj Singh Thakur; Lalitkumar K. Vora (Drug Delivery and Translational Research, 2026)
Fungal keratitis (FK), caused by fungi like Aspergillus , Fusarium , and Candida , accounts for 20–60% of microbial keratitis cases and over 1 million visual impairments annually. Voriconazole (VOR) is effective against FK, but its eye drop formulations suffer from poor bioavailability, while intrastromal injections are invasive and carry risks. This study aimed to address these challenges by formulating a VOR nanosuspension (NS) and fabricating an ocular bilayer dissolving microneedle array patch (dMAP) incorporating the VOR NS for localized drug delivery to the cornea. The VOR NS was prepared using an aqueous media milling method with polyvinyl alcohol (PVA) and polyvinylpyrrolidone (PVP) as stabilizer and cryoprotectant, resulting in stable nanosized particles with a mean size of 270.11 ± 5.82 nm and a PDI of 0.217 ± 0.019. The formulation demonstrated a 1.71-fold increase in saturation solubility and a high drug content (72.5%). Both VOR NS and free VOR were incorporated into the MAP tips using a two-layer casting method. The VOR NS-loaded bilayer dMAP exhibited higher drug content (118.84 ± 20.67 µg) compared to the free VOR-loaded bilayer dMAP (83.08 ± 2.69 µg). Additionally, they demonstrated superior mechanical strength, greater insertion depth (~ 390 μm), and faster tip dissolution in excised porcine corneal tissue (~ 5 min) compared to the free VOR-loaded bilayer dMAP. Ex vivo studies showed that the VOR NS-loaded bilayer dMAP deposited 47.38 ± 8.08 µg of drug into the porcine cornea, 2.31 times more than the free VOR-loaded bilayer dMAP (20.43 ± 6.11 µg), closely approximating the clinical dose used in VOR intrastromal injections (50 µg/0.1 mL). Furthermore, the disc diffusion assay revealed that VOR NS and VOR NS-loaded bilayer dMAP had greater antifungal activity against Candida albicans and Aspergillus fumigatus compared to free VOR and free VOR-loaded bilayer dMAP. Biocompatibility was confirmed through a human corneal epithelial cell viability assay, and ocular irritation potential was evaluated using the HET-CAM assay, revealing a safe and non-irritant profile. Thus, this innovative NS-MAP hybrid system offers efficient drug delivery with minimal invasiveness and could potentially improve therapeutic outcomes in the management of FK. Graphical Abstract

SNAPSHOT USA 2024: Year 6 of the Coordinated National Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Daniel J. Herrera; Camilla Price; Phuong‐Thao Nguyen‐Nu; Katrina Adamczyk; Peter D. Alexander; David Allen; Jesse M. Alston; Diego F. Alvarado‐Serrano; et al. (Global Ecology and Biogeography, 2026)
Motivation SNAPSHOT USA is an annual, multi‐contributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2024 contains 377,427 records of camera trap image sequence data and 3127 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in 49 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1 August and 19 December in 2024. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2024 comprises two .csv files. The original data can be found within the SNAPSHOT USA 2024 project on the Wildlife Insights platform.

Determinants of L-band backscatter in dry tropical ecosystems: Implications for biomass mapping - João M.B. Carreiras; Thomas Higginbottom; John L. Godlee; Sam Harrison; Lorena Benitez; Penelope J. Mograbi; Aurora Levesley; Karina Melgaço; David Milodowski; Georgia Pickavance; Geoff Wells; Edmar Almeida de Oliveira; et al. (Remote Sensing of Environment, 2026)

Correction to: Rapidly dissolving polymeric microneedles for minimally invasive intraocular drug delivery - Raghu Raj Singh Thakur; Ismaiel A. Tekko; Farhan Al-Shammari; Ahlam A. Ali; Helen McCarthy; Ryan F. Donnelly (Drug Delivery and Translational Research, 2026)

Sedimentary facies and invertebrate faunal exchange confirm humid conditions in the tropical eastern Atlantic during interglacial Marine Isotopic Stage (MIS) 11c - Carlos S. Melo; José Madeira; Ricardo S. Ramalho; Ana C. Rebelo; Michael W. Rasser; Esther Martín-González; Alfred Uchman; Carlos Marques da Silva; Emílio Rolán; Luís Silva; Joseph A. Stewart; Laura F. Robinson; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Dendrochronology of curl-leaf mountain mahogany (Cercocarpus ledifolius Nutt.) - R. Justin DeRose; Ryan D. Jess; Matthew F. Bekker; James A. Lutz; Joseph D. Birch (Dendrochronologia, 2026)

Correction to: The attribution of human health outcomes to climate change: transdisciplinary practical guidance - K. L. Ebi; A. Haines; R. F. S. Andrade; C. Åström; M. L. Barreto; A. Bonell; K. Bowen; N. Brink; C. Caminade; C. J. Carlson; R. Carter; P. Chua; et al. (Climatic Change, 2026)

Vulnerability of marine megafauna to global at‐sea anthropogenic threats - Michelle VanCompernolle; Juliet Morris; Hannah J. Calich; Jorge P. Rodríguez; Sarah A. Marley; Jessica R. Pearce; Briana Abrahms; Katya Abrantes; André S. Afonso; Alex Aguilar; Andrews Agyekumhene; Tomonari Akamatsu; et al. (Conservation Biology, 2026)
Marine megafauna species are affected by a wide range of anthropogenic threats. To evaluate the risk of such threats, species’ vulnerability to each threat must first be determined. We build on the existing threats classification scheme and ranking system of the International Union for Conservation of Nature (IUCN) Red List of Threatened Species by assessing the vulnerability of 256 marine megafauna species to 23 at‐sea threats. The threats we considered included individual fishing gear types, climate‐change‐related subthreats not previously assessed, and threats associated with coastal impacts and maritime disturbances. Our ratings resulted in 70 species having high vulnerability ( v > 0.778 out of 1) to at least 1 threat, primarily drifting longlines, temperature extremes, or fixed gear. These 3 threats were also considered to have the most severe effects (i.e., steepest population declines). Overall, temperature extremes and plastics and other solid waste were rated as affecting the largest proportion of populations. Penguins, pinnipeds, and polar bears had the highest vulnerability to temperature extremes. Bony fishes had the highest vulnerability to drifting longlines and plastics and other solid waste; pelagic cetaceans to 4 maritime disturbance threats; elasmobranchs to 5 fishing threats; and flying birds to drifting longlines and 2 maritime disturbance threats. Sirenians and turtles had the highest vulnerability to at least one threat from all 4 categories. Despite not necessarily having severe effects for most taxonomic groups, temperature extremes were rated among the top threats for all taxa except bony fishes. The vulnerability scores we provide are an important first step in estimating the risk of threats to marine megafauna. Importantly, they help differentiate scope from severity, which is key to identifying threats that should be prioritized for mitigation.

Preemptive activation of hypolimnetic oxygenation improves control of Fe and Mn in drinking water reservoirs - Cecelia E. Wood; Carly E. Bauer; Adrienne Breef-Pilz; Abigail S.L. Lewis; Nicholas W. Hammond; Ryan P. McClure; Mary F. Verne; Cayelan C. Carey; Madeline E. Schreiber (Water Research, 2026)

Retraction Note to: Cold Environment Exacerbates Brain Pathology and Oxidative Stress Following Traumatic Brain Injuries: Potential Therapeutic Effects of Nanowired Antioxidant Compound H-290/51 - Aruna Sharma; Dafin F. Muresanu; José Vicente Lafuente; Per-Ove Sjöquist; Ranjana Patnaik; Z Ryan Tian; Asya Ozkizilcik; Hari S. Sharma (Molecular Neurobiology, 2026)

Retraction Note to: Timed Release of Cerebrolysin Using Drug-Loaded Titanate Nanospheres Reduces Brain Pathology and Improves Behavioral Functions in Parkinson’s Disease - Asya Ozkizilcik; Aruna Sharma; Dafin F. Muresanu; José V. Lafuente; Z. Ryan Tian; Ranjana Patnaik; Herbert Mössler; Hari S. Sharma (Molecular Neurobiology, 2026)

Retraction Note to: Nanowired Delivery of Growth Hormone Attenuates Pathophysiology of Spinal Cord Injury and Enhances Insulin-Like Growth Factor-1 Concentration in the Plasma and the Spinal Cord - Dafin F. Muresanu; Aruna Sharma; José V. Lafuente; Ranjana Patnaik; Z. Ryan Tian; Fred Nyberg; Hari S. Sharma (Molecular Neurobiology, 2026)

Reply to the letter : To consider the exercise density in the dose–response relationship: the idea is promising, the operationalization tricky! - Fabian Herold; Liye Zou; Paula Theobald; Patrick Manser; Ryan S. Falck; Qian Yu; Teresa Liu-Ambrose; Arthur F. Kramer; Kirk I. Erickson; Boris Cheval; Yanxia Chen; Matthew Heath; et al. (European Journal of Applied Physiology, 2026)

Influence of exogenous ketosis on spontaneous cardiovagal baroreflex gain and blood pressure responses to isometric handgrip in individuals with metabolic syndrome: a placebo-controlled pilot study - Jon Stavres; Ryan S. Aultman; Caleb F. Brandner; Anabelle Vallecillo-Bustos; Abby T. Compton; Sydney H. Swafford; Ta’Quoris A. Newsome; Austin J. Graybeal (European Journal of Applied Physiology, 2026)

Assessment of leachables and extractables in “super-swelling” hydrogel-forming microarray patches - Qonita Kurnia Anjani; Peter E. McKenna; Eneko Larrañeta; Panagiotis Manesiotis; Yidan Luo; Masoud Adhami; Fabiana Volpe-Zanutto; Gareth Orr; Sabrina Roussel; Ryan F. Donnelly (Drug Delivery and Translational Research, 2026)
Hydrogel-forming microarray patches (MAPs) offer a minimally invasive platform for transdermal drug delivery, enabling systemic absorption of active pharmaceutical ingredients. Unlike dissolving MAPs, which deposit their entire polymer matrix into the skin, hydrogel-forming MAPs remain intact upon removal, reducing polymer exposure while delivering higher drug doses than dissolving or coated MAPs. Moreover, they have demonstrated excellent biocompatibility and do not cause skin or systemic issues, even with repeated application in humans. This study assessed the leachable and extractable compounds from hydrogel-forming MAPs composed of Gantrez ® S-97, PEG 10,000, and sodium carbonate under various conditions. Under physiological conditions (37°C in water), minimal PEG 10,000 leaching (10.4 ± 2.0%) and negligible Gantrez ® S-97 extraction (< 2%) confirmed the hydrogel matrix’s stability and safety. However, stress testing in DMSO at 70°C led to increased PEG 10,000 extraction (up to 32.9 ± 6.1%) and minor Gantrez ® S-97 degradation, likely due to ester hydrolysis. These findings highlight the robustness of hydrogel-forming MAPs, ensuring minimal systemic exposure to unbound polymers while maintaining effective drug delivery. The results support their potential for chronic therapeutic applications requiring repeated dosing. Further clinical studies are needed to validate these findings, facilitating regulatory approval and broader adoption across diverse medical applications. Graphical Abstract

Sustainable digitalisation - a system thinking approach for determining costs and benefits in the agri-sector - K. Soma; G. Brunori; C. Giagnocavo; F. Meulman; M. Ryan; R.M. Heredia Hortigüela; C. Iliopoulos; M. Paulus; A. Ferrari; E. Kilis; S. Grando; V. Bellon-Maurel; et al. (Agricultural Systems, 2026)

Invasive grass litter controls rangeland plant community dynamics - Esben L. Kjaer; Torre J. Hovick; Kevin Sedivec; Ryan F. Limb (Journal of Environmental Management, 2025)

Deep-sea ecosystems of the North Atlantic Ocean: discovery, status, function and future challenges - A. Louise Allcock; Diva J. Amon; Amelia E.H. Bridges; Ana Colaço; Elva Escobar-Briones; Ana Hilário; Kerry L. Howell; Nélia C. Mestre; Frank E. Muller-Karger; Imants G. Priede; Paul V.R. Snelgrove; Kathleen Sullivan Sealey; et al. (Deep Sea Research Part I: Oceanographic Research Papers, 2025)

Preparation, characterisation, and testing of reservoir-based implantable devices loaded with tizanidine and lidocaine - Camila J. Picco; Mihir S. Bhalerao; Octavio E. Fandino; Elizabeth R. Magill; Qonita Kurnia Anjani; Jonathan G. Acheson; Ryan F. Donnelly; Juan Domínguez-Robles; Eneko Larrañeta (Drug Delivery and Translational Research, 2025)
Multiple sclerosis is a chronic neuroimmunological disorder that causes progressive disability, primarily in young adults. It places a significant burden on healthcare systems due to high medication costs and long-term care needs. Implantable devices offer a promising alternative for delivering sustained drug doses in the treatment of chronic conditions. This study introduces a novel long-acting subcutaneous implant for dual-drug delivery: tizanidine (TZ) for spasticity management and lidocaine (LD) for post-insertion pain relief. Reservoir-type implants were developed with TZ in the core and LD in the shell. Two fabrication methods—direct compression and vacuum compression moulding (VCM)—were evaluated for TZ-loaded pellets (3 mm diameter, ~ 10 mm length) using TZ base and TZ hydrochloride. Pellets were encapsulated inside a biodegradable polycaprolactone (PCL) tubular membrane to control drug release. Direct compression pellets, made with poly(vinyl pyrrolidone) and hydroxypropyl-β-cyclodextrin, disintegrated quickly, releasing TZ over 20 days. VCM pellets, formulated with PCL or PCL/poly(ethylene glycol) (PEG), offered prolonged release: up to 200 days for TZ base and 80 days for TZ hydrochloride. Adding PEG accelerated TZ release, reducing duration to 20 days (TZ base) and 125 days (TZ hydrochloride). LD was incorporated into the PCL membrane, providing up to three days of sustained release. Physicochemical analysis confirmed formulation homogeneity and no covalent interactions. These findings highlight the potential of this implant system for MS-related spasticity management, supporting further research into long-acting implants to improve treatment adherence and patient outcomes. Graphical Abstract

Applying the IUCN Global Ecosystem Typology to classify, describe, and map ecosystems based on regional data and Indigenous knowledge - Alys R. Young; Hugh F. Davies; Margaret L. Ayre; Alana Brekelmans; Brett A. Bryan; Jane Elith; Kate Hadden; Mavis Kerinaiua; David A. Keith; Donna L. Lewis; Kinjia M. Munkara‐Murray; Sarah Ryan; et al. (Conservation Biology, 2025)
Effective ecosystem conservation for biodiversity and human well‐being relies on accurate information. Consistent approaches to classifying, describing, and assessing ecosystems can improve understanding of ecological processes, threats, and management. We explored how the International Union for Conservation of Nature (IUCN) Global Ecosystem Typology—a global classification framework based on ecosystem function—could support the development of a classification of ecosystems for the Tiwi Islands, Australia, by incorporating scientific information and Indigenous Tiwi knowledge to facilitate environmental management and conservation. We synthesized ecosystem information from previous research, field data, reports, and Tiwi knowledge authorities to develop a classification, descriptions, and a map of 14 terrestrial ecosystem types. These ecosystem types were defined and described based on ecological processes and were broader yet largely congruent with existing vegetation classifications. Including functional properties accounted for variation in the vegetation physiognomy exhibited by dynamic and disturbance‐prone ecosystems, such as savannas. Because we considered Tiwi knowledge authorities and the IUCN Global Ecosystem Typology, our inventory included ecosystem types that were typically omitted from previous classifications, which should allow for more comprehensive assessments and management. Relating the new ecosystem typology to the IUCN Global Ecosystem Typology will facilitate comparisons among similar ecosystems, regarding, for example, effective threat abatement options. Describing the biota and processes opens new avenues for monitoring. More collaborative work is needed to explore how Western scientific ecosystem inventories operate alongside and in connection with management of Tiwi murrakupuni enacted by Tiwi people. Given the ongoing loss of biodiversity, ecosystem management must draw on information across domains, scales, and knowledge systems. We demonstrated an approach to this task and provided socioecologically relevant ecosystem information.

Atmospheric deposition drives microplastic contamination in remote lakes of Newfoundland, Canada - Anna C. Ryan; Vittorio Maselli; Noreen E. Kelly; Tony R. Walker; Erika F. Merschrod S. (Science of The Total Environment, 2025)

Household air pollution and blood pressure among adult women participants of the Household Air Pollution Intervention Network Trial: An exposure-response analysis - Ajay Pillarisetti; Wenlu Ye; Jennifer L. Peel; Howard Chang; Lindsay J. Underhill; Kalpana Balakrishnan; Anaité Díaz-Artiga; John P. McCracken; Ghislaine Rosa; Lisa M. Thompson; Vigneswari Aravindalochanan; Dana Boyd Barr; et al. (Environmental Research, 2025)

Gestational and postnatal exposures to fine particulate matter (PM2.5) and their association with acute ear infections, diarrhea, respiratory symptoms, and mortality: A longitudinal study of infants in the multicountry Household Air Pollution Intervention Network (HAPIN) trial - Brandie Banner Shackelford; Kyle Steenland; Miles A. Kirby; Kalpana Balakrishnan; Marilú Chiang; Anaité Diaz-Artiga; John P. McCracken; Lisa M. Thompson; Ghislaine Rosa; Lance A. Waller; Shirin Jabbarzadeh; Jiantong Wang; et al. (Environmental Research, 2025)

Tropics to the Poles: A Snapshot of Coastal Eukaryotic Marine Microalgal Diversity Across Five Ecoregions - Jacqui Stuart; Ken G. Ryan; John K. Pearman; Natalie Robinson; Svenja Halfter; Jacob Thomson‐Laing; Laura Biessy; Kirsty F. Smith (Molecular Ecology, 2025)
Eukaryotic microalgae are key organisms in marine environments, contributing to essential nutrient and biogeochemical cycles. Climate change is already causing shifts in the composition and diversity of microalgal assemblages, with coastal ecosystems experiencing increased pressure. Molecular techniques, such as environmental DNA (eDNA) metabarcoding, have allowed eukaryotic microalgal communities (EMCs) to be characterised more rapidly than traditional methods, addressing some data gaps. Many geographic regions still lack comprehensive baseline assessments of entire EMCs, often focusing on specific taxonomic or functional groups. In this study, we used eDNA metabarcoding of the 18S V9 gene region to characterise EMCs across a latitudinal gradient spanning five ecoregions from the South Pacific to the Ross Sea. Temperate sites had the highest alpha diversity and the most distinct EMCs across all ecoregions. Community composition showed clear latitudinal gradients, with a shift from dinoflagellate‐dominant EMCs at lower latitudes to diatom‐dominant EMCs at higher latitudes. The formation of EMCs was influenced by similar habitats/conditions (homogeneous selection) and proximity (homogenising dispersal) within ecoregions, while variable conditions (variable selection) and limited interconnectivity (dispersal limitation) were more prevalent between ecoregions. This snapshot of coastal EMC diversity across five ecoregions highlights distinct latitudinal patterns in community composition, with temperate regions showing higher diversity compared to polar areas. These findings provide a useful baseline for future monitoring and can help guide assessments of potential changes in microalgal communities due to climate change.

Dacarbazine-loaded Bilayer Dissolving Microneedle Array Patch for Localized Delivery in Cutaneous Melanoma - B. H. Jaswanth Gowda; Tahir Emre Yalcin; Anjali K. Pandya; Shilpkala Gade; Mohammed Gulzar Ahmed; Raghu Raj Singh Thakur; Ryan F. Donnelly; Lalitkumar K. Vora (The AAPS Journal, 2025)
Melanoma is a highly aggressive skin cancer that accounts for only ~ 1% of all skin cancer cases but is responsible for most skin cancer-related deaths. Despite advances in systemic therapies, localized treatment options remain limited. Dacarbazine (DCB), the only FDA-approved chemotherapeutic agent for melanoma, is administered intravenously and is associated with systemic toxicity, poor patient compliance, and nonspecific drug distribution. This study presents a bilayer dissolving microneedle array patch (dMAP) for localized, minimally invasive delivery of DCB to the skin, offering a potential alternative for treating cutaneous melanoma. The tip-casting gel formulation was optimized to ensure sharp, defect-free MAP tips with uniform drug distribution. The optimized bilayer dMAP exhibited strong mechanical properties (< 10% needle deformation) and effective insertion capability, reaching approximately 390 µm in depth within the Parafilm® M model. Ex vivo evaluations using full-thickness neonatal porcine skin demonstrated the complete dissolution of bilayer dMAP tips within 60 min and effective pore formation, as confirmed by methylene blue staining. In ex vivo setup, the bilayer dMAP formulation demonstrated 3.93-fold increase in permeability and a 3.02-fold increase in DCB deposition compared with those of the suspension. Furthermore, bilayer dMAP maintained complete drug stability over 8 days at room temperature under light-protected conditions, whereas free DCB showed approximately 7.5% degradation in aqueous media over the same duration. Therefore, bilayer dMAP provides a stable, minimally invasive, and efficient platform for localized drug delivery to the skin, highlighting its potential as a promising alternative to conventional topical formulations for the treatment of cutaneous melanoma. Graphical Abstract

Retrofitted watershed scale green infrastructure reduces heavy metals in urban stormwater from residential land use - Joseph S. Smith; Kay Bernard; Kathryn M. Boening-Ulman; Jay F. Martin; R. Andrew Tirpak; David M. Wituszynski; Ryan J. Winston (Journal of Hazardous Materials, 2025)

Beyond FITT: addressing density in understanding the dose–response relationships of physical activity with health—an example based on brain health - Fabian Herold; Liye Zou; Paula Theobald; Patrick Manser; Ryan S. Falck; Qian Yu; Teresa Liu-Ambrose; Arthur F. Kramer; Kirk I. Erickson; Boris Cheval; Yanxia Chen; Matthew Heath; et al. (European Journal of Applied Physiology, 2025)
Research on physical activity (PA) and health has a fundamental concern with dose–response relationships. The variables of (1) Frequency, (2) Intensity, (3) Time, and (4) Type (i.e., the FITT principle) have traditionally been used to operationalize the dosage of PA. We consider some limitations of FITT and propose that it can be complemented by the additional variable density (from the German exercise and training variable Belastungsdichte), which can be defined as the timing of successive work bouts within a single PA bout as well as the timing between successive PA bouts within a specific time period; it does so by quantifying the temporal intervals between successive work or PA bouts (i.e., time spent at a lower PA intensity or resting such as in napping/sleeping or sedentary behaviors). Using the field of PA and brain health as an example, we discuss the opportunities and challenges for further research employing the variable density and consider its potential to improve the understanding of dose–response relationships between PA and health outcomes.

Benthic community change and stress-tolerant coral at a high-latitude coral community in the northwestern Gulf of Mexico - Marissa F. Nuttall; Kelly O’Connell; Ryan J. Eckert; Emma L. Hickerson; Olivia Eisenbach; Donavon French; Jennifer L. DeBose; Michelle Johnston; G. P. Schmahl (Coral Reefs, 2025)

Double Trouble: Aquatic Invasive Plants Can Promote Mosquitoes - Tressia Chikodza; Ross N. Cuthbert; Maarten Schrama; Julie Coetzee; Ryan Wasserman; Michiel P. Veldhuis; Emily F. Strange (Ecology Letters, 2025)
Human activities continue to facilitate biological invasions, profoundly impacting our environment and economy. Plants and insects constitute the majority of invasions to date, with facilitative links established between them, particularly in terrestrial habitats. These relationships remain understudied in aquatic environments, including potential associations between aquatic invasive plants and disease vectors such as mosquitoes. Here, we synthesise current knowledge on the co‐occurrence of aquatic invasive plants and mosquitoes, identify key research gaps and present a conceptual framework underpinned by testable hypotheses on how aquatic invasive plants may influence immature and adult mosquito populations. We provide evidence suggesting that these plant‐mosquito relationships could pose previously unrecognised risks and highlight priority areas for future research to better understand the potential public health implications of aquatic plant invasions. We call for targeted in situ and ex situ investigations to test the proposed hypotheses and increase our understanding of the interactions between aquatic invasive plants and mosquito population dynamics. Testing these hypotheses will inform adaptive, evidence‐based management strategies to simultaneously control aquatic invasive species and vector mosquitoes.

Increased rhinovirus replication following corticosteroid and air pollution exposures - Ryan D. Huff; Nataly El-Bittar; Emily R. Watts; Michael Yoon; Tina Afshar; Shahina Wiehler; Neeloffer Mookherjee; Christopher F. Rider; David Proud; Chris Carlsten (Environmental Research, 2025)

Network of networks: Time series clustering of AmeriFlux sites - David E Reed; Housen Chu; Brad G. Peter; Jiquan Chen; Michael Abraha; Brian Amiro; Ray G. Anderson; M. Altaf Arain; Paulo Arruda; Greg A. Barron-Gafford; Carl Bernacchi; Daniel P. Beverly; et al. (Agricultural and Forest Meteorology, 2025)

Spatio-temporal variability of San Francisco Bay Plume from space - Piero L. F. Mazzini; Cassia Pianca; L. Fernando Pareja-Roman; Kelly L. Cole; Ryan K. Walter; Renato M. Castelao; Elias J. Hunter; Robert J. Chant (Frontiers in Marine Science, 2025)
As brackish turbid waters exit San Francisco Bay, one of the largest estuaries in the U.S. West Coast, they form the San Francisco Bay Plume (SFBP), which spreads offshore and influences the Gulf of the Farallones (GoF), an ecologically significant region in the California Current System that is also home to three National Marine Sanctuaries. This paper provides the first observationally based investigation of the spatio-temporal variability of the SFBP, using a plume tracking algorithm applied to more than two decades (2002-2023) of ocean color data from the Moderate Resolution Imaging Spectroradiometer (MODIS) sensor onboard satellites Aqua and Terra. The turbid SFBP spreads radially, extending 10-20 km offshore around 50% of the time, and during extreme discharge events (<1% of the time), the plume can reach nearly 60 km offshore to the shelf break. The greatest variability in frequency of plume occurrence was observed 10-20 km offshore and it was largely explained by the seasonal cycle (80% of total variance), linked primarily to seasonal changes in river discharge. Largest plume areas (determined by summing up all pixel areas weighted by their respective fraction of plume occurrence) were observed during winter and smallest during summer, occupying on average 24% and 1.5% of GoF area, respectively. Beyond 20-30 km offshore, variability in frequency of plume occurrence was dominated by the intraseasonal band (50-80% of total variance), attributed to plume response to synoptic wind-forcing and/or filaments and eddies, while the interannual band played a secondary role in the plume variability (<20% of total variance). Finally, a multivariable linear regression model of the turbid SFBP area was created to explore the potential predictability of the plume’s influence in the GoF. The model included the annual and semi-annual cycles and discharge anomalies (deseasoned and detrended), and despite its simplicity, it explained over 78% of total variance of the turbid SFBP area. Therefore, it could be a useful tool for scientists and stakeholders to better understand how management actions on freshwater supply can have consequences offshore beyond the Golden Gate and help guide future management decisions in this ecologically important region.

Stabilizing dynamic subsea power cables using Bi-stable nonlinear energy sinks - Anargyros Michaloliakos; Wei-Ying Wong; Ryan Davies; Malakonda Reddy Lekkala; Matthew Hall; Lei Zuo; Alexander F. Vakakis (Ocean Engineering, 2025)

The attribution of human health outcomes to climate change: transdisciplinary practical guidance - K. L. Ebi; A. Haines; R. F. S. Andrade; C. Åström; M. L. Barreto; A. Bonell; K. Bowen; N. Brink; C. Caminade; C. J. Carlson; R. Carter; P. Chua; et al. (Climatic Change, 2025)

In vivo profiling of the endothelium using ‘AngioTag’ zebrafish - Mayumi F. Miller; Leah J. Greenspan; Derek E. Gildea; Kathryn Monzo; Gennady Margolin; Van N. Pham; Keith K. Ameyaw; Lisa Price; Natalie Aloi; Amber N. Stratman; Andrew E. Davis; Isabella Cisneros; et al. (Angiogenesis, 2025)
Vascular endothelial cells in vivo are exquisitely regulated by their local environment, which is disrupted or absent when using methods such as FACS sorting of cells isolated from animals or in vitro cell culture. Here, we profile the gene expression patterns of undisturbed endothelial cells in living animals using a novel “AngioTag” zebrafish transgenic line that permits isolation of actively translating mRNAs from endothelial cells in their native environment. This transgenic line uses the endothelial cell-specific kdrl promoter to drive expression of an epitope tagged Rpl10a 60 S ribosomal subunit protein, allowing for Translating Ribosome Affinity Purification (TRAP) of actively translating endothelial cell mRNAs. By performing TRAP-RNAseq on AngioTag animals, we demonstrate strong enrichment of endothelial-specific genes and have uncovered both novel endothelial genes and unique endothelial gene expression signatures for different adult organs. Finally, we generated a versatile “UAS: RiboTag” transgenic line to allow a wider array of different zebrafish cell and tissue types to be examined using TRAP-RNAseq methods. These new tools offer an unparalleled resource to study the molecular identity of cells in their normal in vivo context.

Evaluation of physical and chemical modifications to drug reservoirs for stimuli-responsive microneedles - Luchi Li; Qonita Kurnia Anjani; Aaron R. J. Hutton; Mingshan Li; Akmal Hidayat Bin Sabri; Lalitkumar Vora; Yara A. Naser; Yushi Tao; Helen O. McCarthy; Ryan F. Donnelly (Drug Delivery and Translational Research, 2025)
Hydrogel-forming microneedle (MN) arrays are minimally-invasive devices that can penetrate the stratum corneum , the main barrier to topical drug application, without causing pain. However, drug delivery using hydrogel-forming MN arrays tends to be relatively slow compared to rapid drug delivery using conventional needles and syringes. Therefore, in this work, for the first time, different physical and chemical delivery enhancement methods were employed in combination with PVA-based hydrogel-forming MN arrays. Using a model drug, ibuprofen (IBU) sodium, the designed systems were assessed in terms of the extent of transdermal delivery. Iontophoresis (ITP) and heat-assisted drug delivery technology were investigated as physical permeation enhancement techniques. Ex vivo studies demonstrated that the ITP (0.5 mA/cm 2 )-mediated combination strategy significantly enhanced the transdermal permeation of IBU sodium over the first 6 h (~ 5.11 mg) when compared to MN alone (~ 1.63 mg) ( p < 0.05). In contrast, heat-assisted technology showed almost no promoting effect on transdermal delivery. Furthermore, IBU sodium-containing rapidly dissolving lyophilised and effervescent reservoirs, classified as chemical modification methods, were prepared. Both strategies achieved rapid and effective ex vivo IBU sodium permeation, equating to ~ 78% (30.66 mg) and ~ 71% (28.43 mg) from lyophilised and effervescent reservoirs, respectively. Moreover, in vivo pharmacokinetic studies showed that the IBU sodium plasma concentration within lyophilised and effervescent groups reached a maximum concentration (C max ) at 4 h (~ 282.15 µg/mL) and 6 h (~ 140.81 µg/mL), respectively. These strategies not only provided rapid achievement of therapeutic levels (10–15 µg/ml), but also resulted in sustained release of IBU sodium for at least 48 h, which could effectively reduce the frequency of administration, thereby improving patient compliance and reducing side effects of IBU sodium. Graphical Abstract

Next generation Arctic vegetation maps: Aboveground plant biomass and woody dominance mapped at 30 m resolution across the tundra biome - Kathleen M. Orndahl; Logan T. Berner; Matthew J. Macander; Marie F. Arndal; Heather D. Alexander; Elyn R. Humphreys; Michael M. Loranty; Sarah M. Ludwig; Johanna Nyman; Sari Juutinen; Mika Aurela; Juha Mikola; et al. (Remote Sensing of Environment, 2025)

The costs and healing rates of minor injuries in neonatal reef sharks - Shamil F. Debaere; Ornella C. Weideli; Ryan Daly; Elena M. C. Milanesi; José E. Trujillo; Ian A. Bouyoucos; Johann Mourier; Andrew Chin; Serge Planes; Gudrun De Boeck; Jodie L. Rummer (Journal of Fish Biology, 2025)
Elasmobranch fishes (i.e., sharks, skates, and rays) exhibit remarkable wound‐healing capabilities and consistently maintain a high capacity for tissue regeneration throughout their lives. This high capacity for wound healing may be particularly important for neonatal elasmobranchs that are still developing their immune system. However, little is known about the costs associated with wound healing and the potential influence of environmental variables or life history. In this study, we explore (1) the impact of minor, external injuries on the growth and body condition of neonatal blacktip reef ( Carcharhinus melanopterus ) and sicklefin lemon ( Negaprion acutidens ) sharks using a long‐term fisheries‐independent dataset from Moorea, French Polynesia, (2) the influence of ambient temperature on healing rates in neonatal blacktip reef sharks at two experimental temperatures (25°C and 29°C), and (3) variations in umbilical wound‐healing rates between blacktip reef and sicklefin lemon sharks using an additional long‐term dataset from St. Joseph Atoll, Seychelles. We found no impact of minor, external injuries on growth and body condition in neonatal blacktip reef and sicklefin lemon sharks, accelerated umbilical wound healing in neonatal blacktip reef sharks exposed to elevated ambient temperatures, and distinct umbilical wound‐healing rates between neonatal blacktip reef and sicklefin lemon sharks. Enhancing our understanding of sharks' healing capabilities and the influence of environmental factors on this process is crucial for informing handling practices aimed at improving post‐release survival rates of captured sharks under current and future oceanic conditions.

The Human Shield Hypothesis: Does Predator Avoidance of Humans Create Refuges for Prey? - Kaitlyn M. Gaynor; Eamonn I. F. Wooster; April Robin Martinig; Jennifer R. Green; Aimee Chhen; Sandra Cuadros; Ryan Gill; Gopal Khanal; Nicola Love; Rekha Marcus; C. Lauren Mills; Kwasi Wrensford; et al. (Ecology Letters, 2025)
As anthropogenic disturbance restructures ecological communities worldwide, ecologists have developed and tested hypotheses about which species “win” and “lose” in the face of human impacts. One heavily invoked paradigm is that of the human shield, which posits that predators avoid areas of human disturbance due to perceived risk from humans, and prey therefore seek refuge in these areas of perceived safety. Since its introduction in 2007, the human shield hypothesis (HSH) has gained popularity in the ecological literature, although there are more passing mentions of human shields than there are robust tests of the HSH. Here, we systematically review evidence for the HSH and evaluate how it is commonly discussed and tested. While there are several clear‐cut cases of human shields, the emergence of human shields is highly context‐dependent. By formally outlining the assumptions of the HSH, we derive predictions about what ecological and anthropogenic contexts are most likely to be conducive to human shields. Further robust studies that compete the HSH against alternative hypotheses and account for confounding factors can shed light on the role of human shields in human‐modified ecosystems and inform the conservation and management of wildlife in a changing world.

Comparing phthalate exposure between bottlenose dolphins (Tursiops truncatus) residing in urban and rural environments - Miranda K. Dziobak; Tita Curtin; Randall S. Wells; Ryan Takeshita; Cynthia R. Smith; Eric Zolman; Christina N. Toms; Robyn F. Allen; Leslie B. Hart (Frontiers in Marine Science, 2025)
Introduction Exposure to phthalate esters has previously been documented in bottlenose dolphins ( Tursiops truncatus ) inhabiting an urban estuary (Sarasota Bay, FL, USA; 2010-2019). Phthalates are chemicals commonly added to plastic products and consumer goods to enhance qualities such as flexibility, fragrance, and stability. Chemical leaching from products into the marine environment leaves wildlife vulnerable to reproductive, developmental, and metabolic impairment. Environmental phthalate exposure has been shown to vary relative to human activity and urbanization. Methods To evaluate potential differences in dolphin exposure risk, urine was collected from free-ranging bottlenose dolphins residing in an urban (Sarasota Bay, FL, USA; 2010-2024; n=71) and rural estuary (Barataria Bay, LA, USA; 2011- 2023; n=45). Urinary phthalate metabolite concentrations were quantified with high-performance liquid chromatography (HPLC; Agilent 1100; WatersXBridge BEH C18, 2.5 μm, 2.1x50 mm analytical column) coupled to a triple quadrupole mass spectrometer (MS; Applied Biosystems Sciex API 4000) with an electrospray ionization (ESI negative) interface. Results The magnitude of MEHP detection did not differ significantly between sampling sites (p=0.97); however, MEHP was detected more frequently in Sarasota Bay dolphins (73.24%; n=52; 95% CI: 61.20-82.73) than Barataria Bay dolphins (33.33%; n=15; 95% CI: 20.00-48.95%). Dolphins from Sarasota Bay may be exposed to a greater diversity of phthalates compared to Barataria Bay dolphins, indicated by differences in the detected phthalate metabolite profile. Discussion Notably, dolphins from Barataria Bay were impacted by the Deepwater Horizon oil spill, with evidence suggesting long-term negative health outcomes. The endocrine-disrupting effects of phthalates could exacerbate metabolic, reproductive, or immune dysfunction in dolphins, especially those with compromised health. The higher phthalate detection frequency in Sarasota Bay dolphins suggests increased urban exposure risks; however, detection in dolphins from Barataria Bay raises concerns for dolphins in recovering ecosystems. Further research is needed to assess potential synergistic impacts of chemical mixtures, and targeted mitigation strategies in contaminated environments.

Rare and low-frequency variants in families with otitis media - Regie Lyn P. Santos-Cortez; Christina L. Elling; Helen Z. Gomez; Elisabet Einarsdottir; Juha Kere; Petri S. Mattila; Lena Hafrén; Allen F. Ryan (Journal of Molecular Medicine, 2025)

Evaluating the efficacy of Rose Bengal-PVA combinations within PCL/PLA implants for sustained cancer treatment - Sara Demartis; Camila J. Picco; Eneko Larrañeta; Anna Korelidou; Rayhanul Islam; Jonathan A. Coulter; Paolo Giunchedi; Ryan F. Donnelly; Giovanna Rassu; Elisabetta Gavini (Drug Delivery and Translational Research, 2025)
The current investigation aims to address the limitations of conventional cancer therapy by developing an advanced, long-term drug delivery system using biocompatible Rose Bengal (RB)-loaded polyvinyl alcohol (PVA) matrices incorporated into 3D printed polycaprolactone (PCL) and polylactic acid (PLA) implants. The anticancer drug RB’s high solubility and low lipophilicity require frequent and painful administration to the tumour site, limiting its clinical application. In this study, RB was encapsulated in a PVA (RB@PVA) matrix to overcome these challenges and achieve a localised and sustained drug release system within a biodegradable implant designed to be implanted near the tumour site. The RB@PVA matrix demonstrated an RB loading efficiency of 77.34 ± 1.53%, with complete RB release within 30 min. However, when integrated into implants, the system provided a sustained RB release of 75.84 ± 8.75% over 90 days. Cytotoxicity assays on PC-3 prostate cancer cells indicated an IC50 value of 1.19 µM for RB@PVA compared to 2.49 µM for free RB, effectively inhibiting cancer cell proliferation. This innovative drug delivery system, which incorporates a polymer matrix within an implantable device, represents a significant advancement in the sustained release of hydrosoluble drugs. It holds promise for reducing the frequency of drug administration, thereby improving patient compliance and translating experimental research into practical therapeutic applications.

Worldwide Soundscapes: A Synthesis of Passive Acoustic Monitoring Across Realms - Kevin F. A. Darras; Rodney A. Rountree; Steven L. Van Wilgenburg; Anna F. Cord; Frederik Pitz; Youfang Chen; Lijun Dong; Agnès Rocquencourt; Camille Desjonquères; Patrick Mauritz Diaz; Tzu‐Hao Lin; Théophile Turco; et al. (Global Ecology and Biogeography, 2025)
Aim The urgency for remote, reliable and scalable biodiversity monitoring amidst mounting human pressures on ecosystems has sparked worldwide interest in Passive Acoustic Monitoring (PAM), which can track life underwater and on land. However, we lack a unified methodology to report this sampling effort and a comprehensive overview of PAM coverage to gauge its potential as a global research and monitoring tool. To address this gap, we created the Worldwide Soundscapes project, a collaborative network and growing database comprising metadata from 416 datasets across all realms (terrestrial, marine, freshwater and subterranean). Location Worldwide, 12,343 sites, all ecosystem types. Time Period 1991 to present. Major Taxa Studied All soniferous taxa. Methods We synthesise sampling coverage across spatial, temporal and ecological scales using metadata describing sampling locations, deployment schedules, focal taxa and audio recording parameters. We explore global trends in biological, anthropogenic and geophysical sounds based on 168 selected recordings from 12 ecosystems across all realms. Results Terrestrial sampling is spatially denser (46 sites per million square kilometre—Mkm 2 ) than aquatic sampling (0.3 and 1.8 sites/Mkm 2 in oceans and fresh water) with only two subterranean datasets. Although diel and lunar cycles are well sampled across realms, only marine datasets (55%) comprehensively sample all seasons. Across the 12 ecosystems selected for exploring global acoustic trends, biological sounds showed contrasting diel patterns across ecosystems, declined with distance from the Equator, and were negatively correlated with anthropogenic sounds. Main Conclusions PAM can inform macroecological studies as well as global conservation and phenology syntheses, but representation can be improved by expanding terrestrial taxonomic scope, sampling coverage in the high seas and subterranean ecosystems, and spatio‐temporal replication in freshwater habitats. Overall, this worldwide PAM network holds promise to support cross‐realm biodiversity research and monitoring efforts.

TropiRoot 1.0: Database of tropical root characteristics across environments - Amanda L. Cordeiro; Daniela F. Cusack; Nathaly Guerrero‐Ramírez; Richard J. Norby; Laura Toro; Michelle Y. Wong; S. Joseph Wright; Kristine Grace M. Cabugao; Kelly M. Andersen; Lucia Fuchslueger; Colleen M. Iversen; Fiona Soper; et al. (Ecology, 2025)
Tropical ecosystems contain the world's largest biodiversity of vascular plants. Yet, our understanding of tropical functional diversity and its contribution to global diversity patterns is constrained by data availability. This discrepancy underscores an urgent need to bridge data gaps by incorporating comprehensive tropical root data into global datasets. Here, we provide a database of tropical root characteristics. This new database, TropiRoot 1.0, will be instrumental in evaluating an array of hypotheses pertaining to root functional ecology and plant biogeography, both within the tropics and relative to other global biomes. The data compilation was conducted by the TropiRoot Initiative, in partnership with the Fine‐Root Ecology Database (FRED) and the Global Root Trait (GRooT) database, Colorado State University (CSU) and the Smithsonian Tropical Research Institute (STRI). Literature search and data extraction were conducted between 2020 and 2024. Literature was identified using Web of Science, Scopus, and complemented using the expert knowledge of members of TropiRoot. To provide broad environmental and geographical distributions, literature searches included root characteristics (traits) across global change drivers, natural gradients, and from different continents. We adopted FRED standardized data columns and streamlined the format to enhance accessibility for data extraction across various user groups. This optimized framework resulted in a smaller, yet comprehensive datasheet. To make the database compatible with other global root trait initiatives, column identification was standardized following the codes provided by FRED. These efforts culminated in data extracted from 104 new sources, resulting in more than 8000 rows of data (either species or community data). Most of the data in TropiRoot 1.0 include root characteristics such as root biomass, morphology, root dynamics, mass fraction, architecture, anatomy, physiology, and root chemistry. This initiative represents a 30% increase in the currently available data for tropical roots in FRED. TropiRoot 1.0 contains root characteristics from 25 different countries, where seven are located in Asia, six in South America, five in Central America and the Caribbean, four in Africa, two in North America, and 1 in Oceania. Due to the volume of data, when ancillary data were available, including soil data, these data were either extracted and included in the database or its availability was recorded in an additional column. Multiple contributors checked the entries for outliers during the collation process to ensure data quality. For text‐based observations, we examined all cells to ensure that their content relates to their specific categories. For numerical observations, we ordered each numerical value from least to greatest and plotted the values, checking apparent outliers against the data in their respective sources and correcting or removing incorrect or impossible values. Some data (soil and aboveground) have different columns for the same variable presented in different units, including originally published units, but root characteristics data had units converted to match those reported in FRED. By filling a gap from global databases, TropiRoot 1.0 expands our knowledge of otherwise so far underrepresented regions and our ability to assess global trends. This advancement can be used to improve tropical forest representation in vegetation models. The data are freely available and should be cited when used.

Optimistic but tired of hearing about COVID: optimism as a predictor of COVID-19 information and behavioral fatigue among Filipino youth - Jerome V. Cleofas; Ryan Michael F. Oducado (The Social Science Journal, 2025)

Accounting for soil water improves prediction of lentil phenology for improved frost and heat stress management - Yashvir Singh Chauhan; Muhuddin Rajin Anwar; Mark F. Richards; Ryan H.L. Ip; David J. Luckett; Lachlan Lake; Victor O. Sadras; Kadambot H.M. Siddique (European Journal of Agronomy, 2025)

Extending protein-film electrochemistry across enzymology and biological inorganic chemistry to investigate, track and control the reactions of non-redox enzymes and spectroscopically silent metals - Clare F. Megarity; Ryan A. Herold; Fraser A. Armstrong (JBIC Journal of Biological Inorganic Chemistry, 2025)
Protein film electrochemistry has helped to unravel many complex reactivities of electron-transferring proteins and enzymes. A versatile descendant, the ‘Electrochemical Leaf’, offers new opportunities to extend electrochemical control to myriad enzymes that neither transfer electrons nor catalyse any redox reaction, including those dependent on spectroscopically limited, labile or other challenging metal ions. By embedding a cascade comprised of several enzymes—one of which electrochemically recycles NAD(P)(H), a second being a dehydrogenase—within a porous electrode formed from fused nanoparticles, the interconnected reactions are tightly channeled to transmit energy and information, rapidly and interactively. Under nanoconfinement, nicotinamide cofactors and cascade intermediates serve as specific current carriers, far beyond the electron itself. Graphical abstract

Test of Rapamycin in Aging Dogs (TRIAD): study design and rationale for a prospective, parallel-group, double-masked, randomized, placebo-controlled, multicenter trial of rapamycin in healthy middle-aged dogs from the Dog Aging Project - Amanda E. Coleman; Kate E. Creevy; Rozalyn Anderson; May J. Reed; Virginia R. Fajt; Kathleen M. Aicher; Genna Atiee; Brian G. Barnett; Ryan D. Baumwart; Beth Boudreau; Suzanne M. Cunningham; Matthew D. Dunbar; et al. (GeroScience, 2025)

The economic fundamentals of virtual fencing compared to traditional fencing - Dana L. Hoag; Ryan Reuter; Daniel F. Mooney; Jeff Vitale; John Ritten; Nathan DeLay; Paul H. Evangelista; Anthony Vorster (Rangelands, 2025)

Developmental basis of natural tooth shape variation in cichlid fishes - Ryan F. Bloomquist (The Science of Nature, 2025)
While most dentate non-mammalian vertebrates possess simple conical teeth, some demonstrate complex tooth shapes. Lake Malawi cichlid fishes are an extreme example of this, exhibiting a myriad of tooth shapes driven by an ecologically derived rapid evolution of closely related but distinct species. Tooth shape in mammals is generally considered to be established by signaling centers called primary and secondary enamel knots, which are not believed to be present in non-mammalian vertebrates. In this study, signaling centers of gene expression with epithelial folding with similar molecular patterns to that of mammalian enamel knots are identified, and differences of asymmetric gene expression are identified between fish that possess species specific polymorphisms of either bicuspid or tricuspid teeth. Gene expression is then manipulated indirectly using a small molecule inhibitor of the Notch pathway, resulting in phenotypical aberrations of tooth shape and patterning, including a mimic of a tricuspid tooth in a fish with a naturally occurring bicuspid dentition. This study provides insight into the evolutionary origins of tooth shape and advances our knowledge of the molecular determinants of dental morphology with translational utility in regenerative dentistry.

Global Marine Flyways Identified for Long‐Distance Migrating Seabirds From Tracking Data - Joanne M. Morten; Ana P. B. Carneiro; Martin Beal; Anne‐Sophie Bonnet‐Lebrun; Maria P. Dias; Marie‐Morgane Rouyer; Autumn‐Lynn Harrison; Jacob González‐Solís; Victoria R. Jones; Virginia A. Garcia Alonso; Michelle Antolos; Javier A. Arata; et al. (Global Ecology and Biogeography, 2025)
Aim To identify the broad‐scale oceanic migration routes (‘marine flyways’) used by multiple pelagic, long‐distance migratory seabirds based on a global compilation of tracking data. Location Global. Time Period 1989–2023. Major Taxa Studied Seabirds (Families: Phaethontidae, Hydrobatidae, Diomedeidae, Procellariidae, Laridae and Stercorariidae). Methods We collated a comprehensive global tracking dataset that included the migratory routes of 48 pelagic and long‐distance migrating seabird species across the Atlantic, Indian, Pacific and Southern Oceans. We grouped individuals that followed similar routes, independent of species or timings of migration, using a dynamic time warping clustering approach. We visualised the routes of each cluster using a line density analysis and used knowledge of seabird spatial ecology to combine the clusters to identify the broad‐scale flyways followed by most pelagic migratory seabirds tracked to‐date at an ocean‐basin scale. Results Six marine flyways were identified across the world's oceans: the Atlantic Ocean Flyway, North Indian Ocean Flyway, East Indian Ocean Flyway, West Pacific Ocean Flyway, Pacific Ocean Flyway and Southern Ocean Flyway. Generally, the flyways were used bidirectionally, and individuals either followed sections of a flyway, a complete flyway, or their movements linked two or more flyways. Transhemispheric figure‐of‐eight routes in the Atlantic and Pacific oceans, and a circumnavigation flyway in the Southern Ocean correspond with major wind ‐ driven ocean currents. Main Conclusions The marine flyways identified demonstrate that pelagic seabirds have similar and repeatable migration routes across ocean‐basin scales. Our study highlights the need to account for connectivity in seabird conservation and provides a framework for international cooperation.

Challenging Paradigms Around the Role of Colony Size, Taxa, and Environment on Bleaching Susceptibility - Mariana Álvarez‐Noriega; Eoghan A Aston; Madison Becker; Katharina E Fabricius; Will F Figueira; Sophie E Gordon; Ryan Krensel; Marine AA Lechene; Tiny Remmers; Maren Toor; Renata Ferrari (Global Change Biology, 2025)
Understanding how bleaching severity varies across space and among and within taxa helps predict changes in community composition due to climate change and informs conservation efforts. Photogrammetry offers a non‐invasive and time effective method for quantifying attributes of thousands of coral colonies across large, environmentally diverse reef areas. This approach circumvents the limitations of traditional survey methods, where detailed tracking of individual colonies comes at the expense of large sampling areas and sample sizes. Using photogrammetry, we measured colony size and scored bleaching severity of > 5000 colonies of 13 taxa across 26 sites (> 7400 m 2 of reef) during a mild bleaching event in the central Great Barrier Reef (GBR) in 2022. We quantified the relationship between bleaching severity and key biological and environmental factors: colony size, taxonomic identity, degree‐heating weeks (DHWs), water velocity, various measures of reef structural complexity, depth, and distance to coast. Our results show that bleaching probability decreased with increasing colony size for most taxa, contradicting the current understanding of size‐dependent bleaching. Counter to conventional thinking, tabular Acropora spp. presented very low levels of bleaching in 2022 despite being among the most severely bleached taxa during the bleaching event in 1998, suggesting possible adaptation in the last two decades. Our results show a high level of idiosyncrasy in environmental gradients of bleaching severity. For instance, the effect of depth on was taxon‐dependent and the effect of wave velocity differed between inshore and offshore reefs. Our results challenge prevailing paradigms around the role of colony size and environment in regulating bleaching susceptibility, suggesting that refugia are not universal but instead depend on specific environment‐taxonomic combinations and taxon‐specific colony sizes.

Shortfalls in the protection of Important Shark and Ray Areas undermine shark conservation efforts in the Central and South American Pacific - Théophile L. Mouton; Adriana Gonzalez-Pestana; Christoph A. Rohner; Ryan Charles; Emiliano García-Rodríguez; Peter M. Kyne; Amanda Batlle-Morera; Giuseppe Notarbartolo di Sciara; Asia O. Armstrong; Enzo Acuña; Joanna Alfaro-Shigueto; Randall Arauz; et al. (Marine Policy, 2025)

Maximizing biological insights from instruments attached to animals - Roxanne S. Beltran; A. Marm Kilpatrick; Simona Picardi; Briana Abrahms; Gabriel M. Barrile; William K. Oestreich; Justine A. Smith; Max F. Czapanskiy; Arina B. Favilla; Ryan R. Reisinger; Jessica M. Kendall-Bar; Allison R. Payne; et al. (Trends in Ecology & Evolution, 2025)

Decision analysis of Integrated Pest Management: A case study on invasive sea lamprey in the Great Lakes Basin - Sean A. Lewandoski; Kelly F. Robinson; Travis O. Brenden; Ryan Booth; Peter Hrodey; John B. Hume; Thomas C. Pratt; Anne M. Scott; Matthew Symbal; C. Michael Wagner; Nicholas S. Johnson (Journal of Environmental Management, 2025)

Systematic review of impacts of occupational exposure to wildfire smoke on respiratory function, symptoms, measures and diseases - Win Wah; Asmare Gelaw; Deborah C. Glass; Malcolm R. Sim; Ryan F. Hoy; Janneke Berecki-Gisolf; Karen Walker-Bone (International Journal of Hygiene and Environmental Health, 2025)

Retraction Note to: Sleep Deprivation-Induced Blood-Brain Barrier Breakdown and Brain Dysfunction are Exacerbated by Size-Related Exposure to Ag and Cu Nanoparticles. Neuroprotective Effects of a 5-HT3 Receptor Antagonist Ondansetron - Aruna Sharma; Dafin F. Muresanu; José V. Lafuente; Ranjana Patnaik; Z. Ryan Tian; Anca D. Buzoianu; Hari S. Sharma (Molecular Neurobiology, 2025)

Use of modified human hemangioma tissue cultures and human umbilical vein endothelial cell cultures to gain mechanistic insights into imiquimod treatment for infantile hemangioma - Abby Meyer; Lindsey Mortensen; Kimberly A. Miller; Wendy A. Miller; Ryan F. Fader; Beverly R. Wuertz; Frank G. Ondrey (In Vitro Cellular & Developmental Biology - Animal, 2025)

Quercetin loaded polymeric dissolving microarray patches: fabrication, characterisation and evaluation - Qonita Kurnia Anjani; Natalia Moreno-Castellanos; Masoud Adhami; Delly Ramadon; Jangga Jangga; Ryan F. Donnelly (Drug Delivery and Translational Research, 2025)
Quercetin, a natural compound, shows promising potential in wound healing by reducing fibrosis, limiting scar formation, and boosting fibroblast proliferation. However, its effectiveness is hindered by poor solubility, resulting in low bioavailability and necessitating high doses for therapeutic efficacy. This study presents a novel approach, fabricating quercetin-loaded microarray patches (MAPs) using widely employed solubility enhancement strategies. Fabricated MAPs exhibited favourable mechanical strength and could be inserted into excised porcine skin to a depth of 650 μm. Furthermore, formulations containing Soluplus ® significantly increased the drug loading capacity, achieving up to 2.5 mg per patch and complete dissolution within an hour of application on excised porcine skin. In vitro studies on full-thickness neonatal porcine skin demonstrated that Soluplus ® -enhanced MAPs effectively delivered quercetin across various skin layers, achieving a delivery efficiency exceeding 80% over 24 h. Additionally, these prototype MAPs displayed anti-inflammatory properties and demonstrated biocompatibility with human keratinocyte skin cells. Therefore, quercetin-loaded MAPs employing Soluplus ® as a solubility enhancer present a promising alternative strategy for wound healing and anti-inflammatory therapy applications. Graphical abstract

Moisture-mineral interactions drive bacterial and organic matter turnover in glacier-sourced riparian sediments undergoing pedogenesis - A. Peyton Smith; Kenton A. Rod; Tayte Campell; Kaizad F. Patel; Alice Dohnalkova; Malak Tfaily; Lupita Renteria; Vanessa L. Bailey; Ryan Renslow (Soil Biology and Biochemistry, 2024)

A transcontinental threat: Plastic waste from Africa invades Brazil's coast - Lucio Brabo; Laercio L. Martins; Ryan Andrades; Carlos E.P. Teixeira; Adriana Pereira do Nascimento; Rufino Neto Andrade de Azevedo; Luís E.A. Bezerra; Rivelino M. Cavalcante; Kelly Ferreira Cottens; Romulo Alexandre Soares; Paulo Henrique Gomes de Oliveira Sousa; Tarin F. Mont'Alverne; et al. (Science of The Total Environment, 2024)

Development of Salmonella enterica serovar Typhimurium, Listeria monocytogenes, and Pseudomonas aeruginosa multi-species in vitro dry surface biofilm models: Insights into resilience and persistence in low-moisture environments - Gurpreet K. Chaggar; Donald B. Bryant; Ryan Chen; Daniel Fajardo; Zuri A. Jules-Culver; Rishi Drolia; Haley F. Oliver (Food Control, 2024)

Impact of extreme bushfire seasons on rates of occupational injury and disease compensation claims in first responders - Win Wah; Janneke Berecki-Gisolf; Deborah C. Glass; Ryan F. Hoy; Malcolm R. Sim; Alex Collie; Karen Walker-Bone (International Archives of Occupational and Environmental Health, 2024)

Fawn bedsite selection by a large ungulate living in a peri-urban area - Kimberly Conteddu; Katie Wilson; Bawan Amin; Srivats Chari; Amy Haigh; Laura L. Griffin; Matthew Quinn; Andrew Ryan; Adam F. Smith; Simone Ciuti (European Journal of Wildlife Research, 2024)

Acute inorganic nitrate ingestion does not impact oral microbial composition, cognitive function, or high-intensity exercise performance in female team-sport athletes - Rachel Tan; Courtney Merrill; Chandler F. Riley; Maya A. Hammer; Ryan T. Kenney; Alyssa A. Riley; Jeffrey Li; Alexandra C. Zink; Sean T. Karl; Katherine M. Price; Luka K. Sharabidze; Samantha N. Rowland; et al. (European Journal of Applied Physiology, 2024)
The purpose of this study was to investigate the effects of acute nitrate (NO 3 − )-rich beetroot juice ingestion on explosive and high-intensity exercise performance, oral microbiota composition, and cognitive flexibility (i.e., function), before and after maximal intermittent running exercise. Fifteen women team-sport athletes were assigned in a randomized, double-blind, crossover design to consume concentrated NO 3 – -depleted beetroot juice (PL; 0.1 mmol NO 3 − ) and NO 3 − -rich beetroot juice (BR; 12.0 mmol NO 3 − ) 2.5 h prior to performing a battery of exercise performance tasks and cognitive testing before and after the Yo–Yo intermittent recovery level 1 (YYIR1) running test. Resting plasma [NO 3 − ] and plasma nitrite ([NO 2 − ]) were elevated following BR ( P < 0.001). BR did not impact global composition or relative abundance of taxa in the oral microbiome ( P > 0.05) or cognitive flexibility before or after exercise ( P > 0.05). There was no significant difference in performance during 20-m (PRE, PL: 4.38 ± 0.27 vs. BR: 4.38 ± 0.32 s; POST, PL: 4.45 ± 0.29 vs. BR: 4.43 ± 0.35 s) and 10-m sprints (PRE, PL 2.78 ± 0.15 vs. BR 2.79 ± 0.18 s; POST, PL: 2.82 ± 0.16 vs. BR: 2.81 ± 0.19 s), isokinetic handgrip dynamometry, medicine ball throw, horizontal countermovement jump, or YYIR1 (PL: 355 ± 163 m vs. BR: 368 ± 184 m) between BR and PL ( P > 0.05). These findings indicate that acute dietary NO 3 − may not influence the oral microbiome, explosive and high-intensity exercise performance, or cognitive function in women team-sport athletes.

Shortcutting Photorespiration Protects Potato Photosynthesis and Tuber Yield Against Heatwave Stress - Katherine Meacham‐Hensold; Amanda P. Cavanagh; Peyton Sorensen; Paul F. South; Jessica Fowler; Ryan Boyd; Jooyeon Jeong; Steven Burgess; Samantha Stutz; Ryan N. Dilger; Moonsub Lee; Nicholas Ferrari; et al. (Global Change Biology, 2024)
Over two growing seasons, a chloroplast localized synthetic glycolate metabolic pathway expressed in potato, enhanced tuber biomass. We confirmed that this yield benefit did not come at the cost of tuber quality. In 2022, after two early season natural heatwaves, we observed enhanced daily carbon assimilation rates and increased photosynthetic capacity, with transformed plants having up to 23% higher V cmax and 13% higher J max during tuber bulking stages, indicating that transformed plants were better able to withstand growing season heatwaves than untransformed controls. The increases in photosynthetic capacity and potato tuber mass after early season heatwaves were greater than in seasons without heatwaves and present the AP3 pathway as a promising avenue for yield increases in the face of forecast increased intensity and duration of heatwave events as a result of global warming.

Influence of zwitterionic amphiphilic copolymers on heterogeneous gypsum formation: A promising approach for scaling resistance - Meng Wang; Xiaobing Zuo; Raynara M.S. Jacovone; Ryan O'Hara; Abhishek Narayan Mondal; Ayse Asatekin; Debora F. Rodrigues (Water Research, 2024)

The relative importance of postharvest eating quality and sustainability attributes for apple fruit: A case study using new sensory–consumer approaches - F. Roger Harker; Christina M. Roigard; Ann E. Colonna; David Jin; Grace Ryan; Sok L. Chheang; Duncan I. Hedderley; Paul Dalziel (Postharvest Biology and Technology, 2024)

Phylotranscriptomic relationships of the Oophila clade of green algae associated to amphibian egg masses - Miguel Vences; Maria Sachs; Iker Irisarri; Fabian Bartels; Pontus F. Eriksson; Sven Künzel; Atsushi Kurabayashi; Ane T. Laugen; Zachary T. Vegso; Cory D. Bishop; Ryan Kerney; Hartmut Arndt (Molecular Phylogenetics and Evolution, 2024)

An Extended Neck Position is Likely to Produce Cervical Spine Injuries Through Buckling in Accidental Head-First Impacts During Rugby Tackling - Pavlos Silvestros; Ryan D. Quarrington; Ezio Preatoni; Harinderjit S. Gill; Claire F. Jones; Dario Cazzola (Annals of Biomedical Engineering, 2024)
Catastrophic cervical spine injuries in rugby often occur during tackling. The underlying mechanisms leading to these injuries remain unclear, with neck hyperflexion and buckling both proposed as the causative factor in the injury prevention literature. The aim of this study was to evaluate the effect of pre-impact head–neck posture on intervertebral neck loads and motions during a head-first rugby tackle. Using a validated, subject-specific musculoskeletal model of a rugby player, and computer simulations driven by in vivo and in vitro data, we examined the dynamic response of the cervical spine under such impact conditions. The simulations demonstrated that the initial head–neck sagittal-plane posture affected intervertebral loads and kinematics, with an extended neck resulting in buckling and supraphysiologic intervertebral shear and flexion loads and motions, typical of bilateral facet dislocation injuries. In contrast, an initially flexed neck increased axial compression forces and flexion angles without exceeding intervertebral physiological limits. These findings provide objective evidence that can inform injury prevention strategies or rugby law changes to improve the safety of the game of rugby.

Controlled human exposures to diesel exhaust or particle-depleted diesel exhaust with allergen modulates transcriptomic responses in the lung - Shijia Li; Ryan D. Huff; Christopher F. Rider; Agnes C.Y. Yuen; Chris Carlsten (Science of The Total Environment, 2024)

Testing food web theory in a large lake: The role of body size in habitat coupling in Lake Michigan - Bryan M. Maitland; Harvey A. Bootsma; Charles R. Bronte; David B. Bunnell; Zachary S. Feiner; Kari H. Fenske; William W. Fetzer; Carolyn J. Foley; Brandon S. Gerig; Austin Happel; Tomas O. Höök; Friedrich W. Keppeler; et al. (Ecology, 2024)
The landscape theory of food web architecture (LTFWA) describes relationships among body size, trophic position, mobility, and energy channels that serve to couple heterogenous habitats, which in turn promotes long‐term system stability. However, empirical tests of the LTFWA are rare and support differs among terrestrial, freshwater, and marine systems. Further, it is unclear whether the theory applies in highly altered ecosystems dominated by introduced species such as the Laurentian Great Lakes. Here, we provide an empirical test of the LTFWA by relating body size, trophic position, and the coupling of different energy channels using stable isotope data from species throughout the Lake Michigan food web. We found that body size was positively related to trophic position, but for a given trophic position, organisms predominately supported by pelagic energy had smaller body sizes than organisms predominately supported by nearshore benthic energy. We also found a hump‐shaped trophic relationship in the food web where there is a gradual increase in the coupling of pelagic and nearshore energy channels with larger body sizes as well as higher trophic positions. This highlights the important role of body size and connectivity among habitats in structuring food webs. However, important deviations from expectations are suggestive of how species introductions and other anthropogenic impacts can affect food web structure in large lakes. First, native top predators appear to be flexible couplers that may provide food web resilience, whereas introduced top predators may confer less stability when they specialize on a single energy pathway. Second, some smaller bodied prey fish and invertebrates, in addition to mobile predators, coupled energy from pelagic and nearshore energy channels, which suggests that some prey species may also be important integrators of energy pathways in the system. We conclude that patterns predicted by the LTFWA are present in the face of species introductions and other anthropogenic stressors to a degree, but time‐series evaluations are needed to fully understand the mechanisms that promote stability.

Ethnomedicinal importance and antimicrobial activity of Leonotis ocymifolia - Mariam O. Oyedeji-Amusa; Sandy F. Van Vuuren; Ryan D. Rattray; Ben-Erik Van Wyk (South African Journal of Botany, 2024)

The CRISM investigation in Mars orbit: Overview, history, and delivered data products - Frank P. Seelos; Kimberly D. Seelos; Scott L. Murchie; M. Alexandra Matiella Novak; Christopher D. Hash; M. Frank Morgan; Raymond E. Arvidson; John Aiello; Jean-Pierre Bibring; Janice L. Bishop; John D. Boldt; Ariana R. Boyd; et al. (Icarus, 2024)

Formulation and evaluation of ivermectin-loaded dissolving microarray patches for rosacea disease - Qonita Kurnia Anjani; Sara Demartis; Natalia Moreno-Castellanos; Elisabetta Gavini; Ryan F. Donnelly (Journal of Pharmaceutical Investigation, 2024)
Purpose This investigation aims to develop and characterise dissolving microarray patches (MAPs) loaded with ivermectin (IVM) for rosacea therapy. Methods Tween ® 80 and Soluplus ® were evaluated to enhance the water solubility of IVM powder. Three dissolving MAPs were fabricated using a two-layer casting method, pure IVM-loaded (F1), IVM-Tween ® 80 (F2), and IVM-Soluplus ® (F3) loaded patches. Formulations were evaluated for drug content, in vitro and ex vivo mechanical performances, ex vivo skin dissolution time, dermatokinetics, in vitro biocompatibility and activity against rosacea. Results IVM solubility in water was improved with surfactants, reaching 1206.42 ± 53.78 and 130.78 ± 12.78 µg/mL in Tween ® 80 and Soluplus ® solutions, respectively. The MAPs, featuring bubble-free, perfectly shaped pyramidal needles of approximately 800 μm, exhibited considerably higher IVM content in F2 and F3 than in F1 (2.31 ± 0.26 mg for F1, 3.58 ± 0.15 mg for F2, and 3.19 ± 0.22 mg for F3). All formulations demonstrated mechanical robustness and penetrated the skin to a depth of 650 μm. The highest IVM deposition in the skin at 24 h was achieved by F2, selected as the lead formulation (F1 = 1456.35 ± 266.90 µg; F2 = 2165.24 ± 130.13 µg; F3 = 1684.74 ± 212.09 µg). Furthermore, F2 and F3 provided faster IVM deposition, most likely due to the quicker dissolution rate of microneedles in the skin. F2 proved biocompatible to skin cells in vitro and effectively inhibited the inflammatory cascade associated with rosacea diseases. Conclusion This study encourages further investigation into IVM-loaded dissolving MAPs formulated with Tween ® 80 for rosacea therapy.

Illitization of montmorillonite in ammonium solutions under hydrothermal conditions - María Bentabol; Daniel Lamarca-Irisarri; Alexander E.S. Van Driessche; Peter C. Ryan; F. Javier Huertas (Applied Clay Science, 2024)

Disentangling effects of dispersal, environment and anthropogenic barriers on functional connectivity in aquatic systems - Casey C. Day; Dominique Alò; Ryan K. Simmons; Stacy R. Cotey; Katherine E. Zarn; Ian F. Gazeley; Maureen Small; Marie‐Josee Fortin; Andrew R. Bearlin; Seth R. Smith; Erin L. Landguth (Molecular Ecology, 2024)
Disentangling the roles of structural landscape factors and animal movement behaviour can present challenges for practitioners managing landscapes to maintain functional connectivity and achieve conservation goals. We used a landscape genetics approach to combine robust demographic, behavioural and genetic datasets with spatially explicit simulations to evaluate the effects of anthropogenic barriers (dams, culverts) and natural landscape resistance (gradient, elevation) affecting dispersal behaviour, genetic connectivity and genetic structure in a resident population of Westslope Cutthroat Trout ( Oncorhynchus clarkii lewisi ). Analyses based on 10 years of sampling effort revealed a pattern of restricted dispersal, and population genetics identified discrete population clusters between distal tributaries and the mainstem stream and no structure within the mainstem stream. Demogenetic simulations demonstrated that, for this population, the effects of existing anthropogenic barriers on population structure are redundant with effects of restricted dispersal associated with the underlying environmental resistance. Our approach provides an example of how extensive field sampling combined with landscape genetics can be incorporated into spatially explicit simulation modelling to explore how, together, movement ecology and landscape resistance can be used to inform decisions around restoration and connectivity.

Characterizing feral swine movement across the contiguous United States using neural networks and genetic data - Rachael M. Giglio; Courtney F. Bowden; Ryan K. Brook; Antoinette J. Piaggio; Timothy J. Smyser (Molecular Ecology, 2024)
Globalization has led to the frequent movement of species out of their native habitat. Some of these species become highly invasive and capable of profoundly altering invaded ecosystems. Feral swine ( Sus scrofa × domesticus ) are recognized as being among the most destructive invasive species, with populations established on all continents except Antarctica. Within the United States (US), feral swine are responsible for extensive crop damage, the destruction of native ecosystems, and the spread of disease. Purposeful human‐mediated movement of feral swine has contributed to their rapid range expansion over the past 30 years. Patterns of deliberate introduction of feral swine have not been well described as populations may be established or augmented through small, undocumented releases. By leveraging an extensive genomic database of 18,789 samples genotyped at 35,141 single nucleotide polymorphisms (SNPs), we used deep neural networks to identify translocated feral swine across the contiguous US. We classified 20% (3364/16,774) of sampled animals as having been translocated and described general patterns of translocation using measures of centrality in a network analysis. These findings unveil extensive movement of feral swine well beyond their dispersal capabilities, including individuals with predicted origins >1000 km away from their sampling locations. Our study provides insight into the patterns of human‐mediated movement of feral swine across the US and from Canada to the northern areas of the US. Further, our study validates the use of neural networks for studying the spread of invasive species.

The enemy of my enemy… Exotic mammals present biotic resistance against invasive alien conifers - Thomas F. Carlin; Thomas S. H. Paul; Jan H. Dudenhoeffer; Carol Rolando; Max Novoselov; Ryan S. Vorster; Casey R. Springford; Matthew B. Scott (Biological Invasions, 2024)
Plant invasions are a widespread and recurring phenomenon that cause significant economic and environmental damage. Invasive alien conifers are weeds that are not only costly to manage, but consistently reinvade after management efforts. Understanding how many seeds survive to germinate is a key part in understanding the weed life cycle puzzle. Here we investigated the contribution that seed predators have on reducing invasive alien conifer seed survival across both invaded and uninvaded habitats in Aotearoa New Zealand. We combined quantitative and qualitative experiments to measure seed predation across invaded and uninvaded habitats, as well as to identify which fauna are the most prolific seed predators. We utilised ex-situ empirical evidence with in-situ observations to provide realistic impacts from different seed predator species. We found that introduced mammals, particularly rodents, were the primary seed predators of invasive conifers. Seed predation pressure was highest in herbicide treated invasive alien conifer forests, indigenous beech forests, and managed pasture containing grazing livestock. Indigenous tussock areas support fewer vertebrate seed predators and as a result are particularly vulnerable to conifer invasion. The majority of seed predation occurs within the first two weeks post-dispersal. These results suggest that introduced mammal control operations, which are essential to protect endemic New Zealand species, will likely result in increasing invasive conifer populations by reducing seed predation pressure. Seed predation varies greatly between habitats, suggesting invasion and reinvasion rates are higher in ungrazed areas of lower forest density that support fewer introduced mammals.

Evaluation of Apparatus and Protocols to Measure Human Passive Neck Stiffness and Range of Motion - Mingyue Liu; Ryan D. Quarrington; Baptiste Sandoz; William S. P. Robertson; Claire F. Jones (Annals of Biomedical Engineering, 2024)
Understanding of human neck stiffness and range of motion (ROM) with minimal neck muscle activation (“passive”) is important for clinical and bioengineering applications. The aim of this study was to develop, implement, and evaluate the reliability of methods for assessing passive-lying stiffness and ROM, in six head-neck rotation directions. Six participants completed two assessment sessions. To perform passive-lying tests, the participant’s head and torso were strapped to a bending (flexion, extension, lateral bending) or a rotation (axial rotation) apparatus, and clinical bed, respectively. The head and neck were manually rotated by the researcher to the participant’s maximum ROM, to assess passive-lying stiffness. Participant-initiated (“active”) head ROM was also assessed in the apparatus, and seated. Various measures of apparatus functionality were assessed. ROM was similar for all assessment configurations in each motion direction except flexion. In each direction, passive stiffness generally increased throughout neck rotation. Within-session reliability for stiffness (ICC > 0.656) and ROM (ICC > 0.872) was acceptable, but between-session reliability was low for some motion directions, probably due to intrinsic participant factors, participant-apparatus interaction, and the relatively low participant number. Moment-angle corridors from both assessment sessions were similar, suggesting that with greater sample size, these methods may be suitable for estimating population-level corridors.

Microbial community and extracellular polymeric substance dynamics in arid–zone temporary pan ecosystems - Tafara F. Bute; Adam Wyness; Ryan J. Wasserman; Farai Dondofema; Chad Keates; Tatenda Dalu (Science of The Total Environment, 2024)

Chrono-tailored drug delivery systems: recent advances and future directions - Christine T. Butler; Aoife M. Rodgers; Annie M. Curtis; Ryan F. Donnelly (Drug Delivery and Translational Research, 2024)
Circadian rhythms influence a range of biological processes within the body, with the central clock or suprachiasmatic nucleus (SCN) in the brain synchronising peripheral clocks around the body. These clocks are regulated by external cues, the most influential being the light/dark cycle, in order to synchronise with the external day. Chrono-tailored or circadian drug delivery systems (DDS) aim to optimise drug delivery by releasing drugs at specific times of day to align with circadian rhythms within the body. Although this approach is still relatively new, it has the potential to enhance drug efficacy, minimise side effects, and improve patient compliance. Chrono-tailored DDS have been explored and implemented in various conditions, including asthma, hypertension, and cancer. This review aims to introduce the biology of circadian rhythms and provide an overview of the current research on chrono-tailored DDS, with a particular focus on immunological applications and vaccination. Finally, we draw on some of the key challenges which need to be overcome for chrono-tailored DDS before they can be translated to more widespread use in clinical practice. Graphical Abstract

Calibration and validation of DRAINMOD to predict long-term permeable pavement hydrology - Alessandra S. Braswell; Ryan J. Winston; Jay D. Dorsey; Mohamed A. Youssef; William F. Hunt (Journal of Hydrology, 2024)

Clopidogrel-loaded vascular grafts prepared using digital light processing 3D printing - Masoud Adhami; Camila J. Picco; Usanee Detamornrat; Qonita K. Anjani; Victoria A. Cornelius; Pamela Robles-Martinez; Andriana Margariti; Ryan F. Donnelly; Juan Domínguez-Robles; Eneko Larrañeta (Drug Delivery and Translational Research, 2024)
The leading cause of death worldwide and a significant factor in decreased quality of life are the cardiovascular diseases. Endovascular operations like angioplasty, stent placement, or atherectomy are often used in vascular surgery to either dilate a narrowed blood artery or remove a blockage. As an alternative, a vascular transplant may be utilised to replace or bypass a dysfunctional or blocked blood vessel. Despite the advancements in endovascular surgery and its popularisation over the past few decades, vascular bypass grafting remains prevalent and is considered the best option for patients in need of long-term revascularisation treatments. Consequently, the demand for synthetic vascular grafts composed of biocompatible materials persists. To address this need, biodegradable clopidogrel (CLOP)-loaded vascular grafts have been fabricated using the digital light processing (DLP) 3D printing technique. A mixture of polylactic acid-polyurethane acrylate (PLA-PUA), low molecular weight polycaprolactone (L-PCL), and CLOP was used to achieve the required mechanical and biological properties for vascular grafts. The 3D printing technology provides precise detail in terms of shape and size, which lead to the fabrication of customised vascular grafts. The fabricated vascular grafts were fully characterised using different techniques, and finally, the drug release was evaluated. Results suggested that the performed 3D-printed small-diameter vascular grafts containing the highest CLOP cargo (20% w/w) were able to provide a sustained drug release for up to 27 days. Furthermore, all the CLOP-loaded 3D-printed materials resulted in a substantial reduction of the platelet deposition across their surface compared to the blank materials containing no drug. Haemolysis percentage for all the 3D-printed samples was lower than 5%. Moreover, 3D-printed materials were able to provide a supportive environment for cellular attachment, viability, and growth. A substantial increase in cell growth was detected between the blank and drug-loaded grafts. Graphical Abstract

Cost–benefit analysis of ecosystem modeling to support fisheries management - Matthew H. Holden; Eva E. Plagányi; Elizabeth A. Fulton; Alexander B. Campbell; Rachel Janes; Robyn A. Lovett; Montana Wickens; Matthew P. Adams; Larissa Lubiana Botelho; Catherine M. Dichmont; Philip Erm; Kate J. Helmstedt; et al. (Journal of Fish Biology, 2024)
Mathematical and statistical models underlie many of the world's most important fisheries management decisions. Since the 19th century, difficulty calibrating and fitting such models has been used to justify the selection of simple, stationary, single‐species models to aid tactical fisheries management decisions. Whereas these justifications are reasonable, it is imperative that we quantify the value of different levels of model complexity for supporting fisheries management, especially given a changing climate, where old methodologies may no longer perform as well as in the past. Here we argue that cost‐benefit analysis is an ideal lens to assess the value of model complexity in fisheries management. While some studies have reported the benefits of model complexity in fisheries, modeling costs are rarely considered. In the absence of cost data in the literature, we report, as a starting point, relative costs of single‐species stock assessment and marine ecosystem models from two Australian organizations. We found that costs varied by two orders of magnitude, and that ecosystem model costs increased with model complexity. Using these costs, we walk through a hypothetical example of cost‐benefit analysis. The demonstration is intended to catalyze the reporting of modeling costs and benefits.

An Accuracy Assessment of Field and Airborne Laser Scanning–Derived Individual Tree Inventories using Felled Tree Measurements and Log Scaling Data in a Mixed Conifer Forest - Aaron M Sparks; Mark V Corrao; Robert F Keefe; Ryan Armstrong; Alistair M S Smith (Forest Science, 2024)
On-the-ground sample-based forest inventory methods have been the standard practice for more than a century, however, remote sensing technologies such as airborne laser scanning (ALS) are providing wall-to-wall inventories based on individual tree measurements. In this study, we assess the accuracy of individual tree height, diameter, and volume derived from field-cruising measurements and three ALS data-derived methods in a 1.1 ha stand using direct measurements acquired on felled trees and log-scale volume measurements. Results show that although height derived from indirect conventional field measurements and ALS were statistically equivalent to felled tree height measurements, ALS measured heights had lower root mean square error (RMSE) and bias. Individual tree diameters modeled using a height-to-diameter-at-breast-height model derived from local forest inventory data and the software ForestView had moderate RMSE (8.3–8.5 cm) and bias (-3.0 – -0.3 cm). The ALS-based methods underdetected trees but accounted for 78%–91% of the field reference harvested merchantable volume and 71%–99% of the merchantable volume scaled at the mill. The results also illustrate challenges of using mill-scaled volume estimates as validation data and highlight the need for more research in this area. Overall, the results provide key insights to forest managers on accuracies associated with conventional field-derived and ALS-derived individual tree inventories. Study Implications: Forest inventory data provide critical information for operational decisions and forest product supply chain planning. Traditionally, forest inventories have used field sampling of stand conditions, which is time-intensive and cost-prohibitive to conduct at large spatial scales. Remote sensing technologies such as airborne laser scanning (ALS) provide wall-to-wall inventories based on individual tree measurements. This study advances our understanding of the accuracy of conventional field-derived and ALS-derived individual tree inventories by evaluating these inventories with felled tree and log scaling data. The results provide key insights to forest managers on errors associated with conventional field and ALS-derived individual tree measurements.

Effects of social isolation and galactic cosmic radiation on fine motor skills and behavioral performance - Austin M. Adkins; Emily M. Colby; Alea F. Boden; Justin D. Gotthold; Ryan D. Harris; Richard A. Britten; Laurie L. Wellman; Larry D. Sanford (Life Sciences in Space Research, 2024)

Diagenesis of fossil gar fish scales with implications for geochronology and paleoenvironmental applications - John Fink; Marissa M. Tremblay; Thomas S. Tobin; Lisa D. Stockli; Daniel F. Stockli; Ryan B. Ickert (Geochimica et Cosmochimica Acta, 2024)

The natural history and genotype–phenotype correlations of TMPRSS3 hearing loss: an international, multi-center, cohort analysis - Brett M. Colbert; Cris Lanting; Molly Smeal; Susan Blanton; Derek M. Dykxhoorn; Pei-Ciao Tang; Richard L. Getchell; Hedwig Velde; Mirthe Fehrmann; Ryan Thorpe; Prem Chapagain; Heidy Elkhaligy; et al. (Human Genetics, 2024)
TMPRSS3 -related hearing loss presents challenges in correlating genotypic variants with clinical phenotypes due to the small sample sizes of previous studies. We conducted a cross-sectional genomics study coupled with retrospective clinical phenotype analysis on 127 individuals. These individuals were from 16 academic medical centers across 6 countries. Key findings revealed 47 unique TMPRSS3 variants with significant differences in hearing thresholds between those with missense variants versus those with loss-of-function genotypes. The hearing loss progression rate for the DFNB8 subtype was 0.3 dB/year. Post-cochlear implantation, an average word recognition score of 76% was observed. Of the 51 individuals with two missense variants, 10 had DFNB10 with profound hearing loss. These 10 all had at least one of 4 TMPRSS3 variants predicted by computational modeling to be damaging to TMPRSS3 structure and function. To our knowledge, this is the largest study of TMPRSS3 genotype–phenotype correlations. We find significant differences in hearing thresholds, hearing loss progression, and age of presentation, by TMPRSS3 genotype and protein domain affected. Most individuals with TMPRSS3 variants perform well on speech recognition tests after cochlear implant, however increased age at implant is associated with worse outcomes. These findings provide insight for genetic counseling and the on-going design of novel therapeutic approaches.

Heliophysics and space weather information architecture and innovative solutions: Current status and ways forward - Arnaud Masson; Shing F. Fung; Enrico Camporeale; Masha M. Kuznetsova; Stefaan Poedts; Julie Barnum; Rebecca Ringuette; D. De Zeeuw; Shawn Polson; Viacheslav M. Sadykov; Vicente Navarro; Brian Thomas; et al. (Advances in Space Research, 2024)

Water and sediment chemistry drivers of chlorophyll-a dynamics within a Ramsar declared floodplain pan wetland system - Linton F. Munyai; Lutendo Mugwedi; Ryan J. Wasserman; Farai Dondofema; Eddie Riddell; Chad Keates; Tatenda Dalu (Environmental Science and Pollution Research, 2024)

Global genetic diversity and historical demography of the Bull Shark - Bautisse D. Postaire; Floriaan Devloo‐Delva; Juerg M. Brunnschweiler; Patricia Charvet; Xiao Chen; Geremy Cliff; Ryan Daly; J. Marcus Drymon; Mario Espinoza; Daniel Fernando; Kerstin Glaus; Michael I. Grant; et al. (Journal of Biogeography, 2024)
Aim Biogeographic boundaries and genetic structuring have important effects on the inferences and interpretation of effective population size ( N e ) temporal variations, a key genetics parameter. We reconstructed the historical demography and divergence history of a vulnerable coastal high‐trophic shark using population genomics and assessed our ability to detect recent bottleneck events. Location Western and Central Indo‐Pacific (IPA), Western Tropical Atlantic (WTA) and Eastern Tropical Pacific (EPA). Taxon Carcharhinus leucas (Müller & Henle, 1839). Methods A DArTcap™ approach was used to sequence 475 samples and assess global genetic structuring. Three demographic models were tested on each population, using an ABC‐RF framework coupled with coalescent simulations, to investigate within‐cluster structure. Divergence times between clusters were computed, testing multiple scenarios, with fastsimcoal . N e temporal variations were reconstructed with STAIRWAYPLOT. Coalescent simulations were performed to determine the detectability of recent bottleneck under the estimated historical trend for datasets of this size. Results Three genetic clusters corresponding to the IPA, WTA and EPA regions were identified, agreeing with previous studies. The IPA presented the highest genetic diversity and was consistently identified as the oldest. No significant within‐cluster structuring was detected. N e increased globally, with an earlier onset in the IPA, during the last glacial period. Coalescent simulations showed that weak and recent bottlenecks could not be detected with our dataset, while old and/or strong bottlenecks would erase the observed ancestral expansion. Main Conclusions This study further confirms the role of marine biogeographic breaks in shaping the genetic history of large mobile marine predators. N e historical increases in N e are potentially linked to extended coastal habitat availability. The limited within‐cluster population structuring suggests that N e can be monitored over ocean basins. Due to insufficient amount of available genetic data, it cannot be concluded whether overfishing is impacting Bull Shark genetic diversity, calling for whole‐genome sequencing.

A geoarchaeological review of Balzi Rossi, Italy: A crossroad of Palaeolithic populations in the northwest Mediterranean - D.D. Ryan; E. Starnini; M. Serradimigni; E. Rossoni-Notter; O. Notter; A. Zerboni; F. Negrino; S. Grimaldi; M. Vacchi; L. Ragaini; A. Rovere; A. Perego; et al. (Quaternary Science Reviews, 2024)

The potential to manage releases of Bacillus anthracis using bioretention and a high flow media filter: Results of simulated runoff testing with tracer spores Bacillus globigii - Kathryn M. Boening-Ulman; Anne M. Mikelonis; J. Lee Heckman; M. Worth Calfee; Katherine Ratliff; Sungmin Youn; Joseph S. Smith; Caleb E. Mitchell; William F. Hunt; Ryan J. Winston (Journal of Environmental Management, 2024)

Fatty acid production and associated gene pathways are altered by increased salinity and dimethyl sulfoxide treatments during cryopreservation of Symbiodinium pilosum (Symbiodiniaceae) - Joseph K. Kihika; John K. Pearman; Susanna A. Wood; Lesley L. Rhodes; Kirsty F. Smith; Matthew R. Miller; Juliette Butler; Ken G. Ryan (Cryobiology, 2024)

The promise of microneedle technologies for drug delivery - Ryan F. Donnelly; Mark R. Prausnitz (Drug Delivery and Translational Research, 2024)

Nonlinear life table response experiment analysis: Decomposing nonlinear and nonadditive population growth responses to changes in environmental drivers - Ryan D. O'Connell; Daniel F. Doak; Carol C. Horvitz; John B. Pascarella; William F. Morris (Ecology Letters, 2024)
Life table response experiments (LTREs) decompose differences in population growth rate between environments into separate contributions from each underlying demographic rate. However, most LTRE analyses make the unrealistic assumption that the relationships between demographic rates and environmental drivers are linear and independent, which may result in diminished accuracy when these assumptions are violated. We extend regression LTREs to incorporate nonlinear (second‐order) terms and compare the accuracy of both approaches for three previously published demographic datasets. We show that the second‐order approach equals or outperforms the linear approach for all three case studies, even when all of the underlying vital rate functions are linear. Nonlinear vital rate responses to driver changes contributed most to population growth rate responses, but life history changes also made substantial contributions. Our results suggest that moving from linear to second‐order LTRE analyses could improve our understanding of population responses to changing environments.

A systematic multicriteria-based approach to support product portfolio selection in microalgae biorefineries - Bruno C. Klein; Mateus F. Chagas; Ryan E. Davis; Marcos D.B. Watanabe; Matthew R. Wiatrowski; Edvaldo R. Morais; Lieve M.L. Laurens (Chemical Engineering Journal, 2024)

Geochemical evolution of the REE-enriched Cave Peak porphyry Mo-deposit, Trans-Pecos Texas, USA - Mert Ugurhan; Brent Alan Elliott; J. Richard Kyle; Daniel F. Stockli; Ryan Mathur (Lithos, 2024)

Correction to: Assessing Fish and Macroinvertebrates Assemblages in Relation to Environmental Variables in Makuleke Floodplain Pans: Implications for Biodiversity Conservation - Linton F. Munyai; Lutendo Mugwedi; Ryan J. Wasserman; Farai Dondofema; Tatenda Dalu (Wetlands, 2024)

MAP-box: a novel, low-cost and easy-to-fabricate 3D-printed box for the storage and transportation of dissolving microneedle array patches - Qonita Kurnia Anjani; Álvaro Cárcamo-Martínez; Luki Ahmadi Hari Wardoyo; Natalia Moreno-Castellanos; Akmal Hidayat Bin Sabri; Eneko Larrañeta; Ryan F. Donnelly (Drug Delivery and Translational Research, 2024)
Research on the use of microarray patches (MAPs) has progressed at an unprecedented rate over the years, leading to the development of many novel drug delivery systems. As the technology approaches patients, there are several key aspects that ought to be addressed in order to facilitate the smooth translation of MAPs from bench to bedside. One integral factor includes the choice of devices and packaging for the storage of MAPs. In the current work, a slide-and-seal box, MAP-box, was developed for the storage of dissolving MAPs, using fused-deposition modelling. The device has been designed to act as a pill-box for MAPs not only to provide protection for MAPs from the environment, but also to improve patient’s adherence to treatment. The overall design of the MAP-box was simple, yet offers the capability of sealing and protecting dissolving MAPs up to 30 days. Donepezil HCl was formulated into a dissolvable MAP, which was used to treat dementia related to Alzheimer’s disease. This compound was used as a model formulation to evaluate the utility of the 3D printed MAP-box when placed under three storage conditions: 5 °C and ambient humidity, 25 °C and 65% relative humidity and 40 °C and 75% relative humidity. It was shown that the slide-and-seal box was able to confer protection to MAPs for up to 30 days under accelerated stability study conditions as the drug loading, mechanical properties and insertion properties of MAPs remained unaffected when compared to the unpackaged MAPs stored under these same parameters. These preliminary data provide evidence that the MAP-box prototype may be of great utility for the storage of single or multiple MAPs. Nevertheless, future work will be needed to evaluate their patient usability and its application to different types of MAP systems to fully validate the overall robustness of the prototype. Graphical Abstract

Design, Synthesis, and Biochemical Analysis of a Molecule Designed to Enhance Endosomal Escape - Satish G. Jadhav; Ryan L. Setten; Carlos Medina; Xian-Shu Cui; Steven F. Dowdy (The AAPS Journal, 2023)

Co-occurrence of biodiversity, carbon storage, coastal protection, and fish and invertebrate production to inform global mangrove conservation planning - Michael Sievers; Christopher J. Brown; Jennifer McGowan; Mischa P. Turschwell; Christina A. Buelow; Briana Holgate; Ryan M. Pearson; Maria F. Adame; Dominic A. Andradi-Brown; Andy Arnell; Brendan G. Mackey; Philine S.E. zu Ermgassen; et al. (Science of The Total Environment, 2023)

Preparation, analysis and toxicity characterisation of the redox metabolites of the azo food dye tartrazine - Ruth Pay; Abigail V. Sharrock; Riley Elder; Alaigne Maré; Joe Bracegirdle; Dan Torres; Niall Malone; Jan Vorster; Libusha Kelly; Ali Ryan; P. David Josephy; Emma Allen-Vercoe; et al. (Food and Chemical Toxicology, 2023)

Ecology, evolution and conservation of tidepool fishes of the Americas - Ryan Andrades; Saúl González-Murcia; Thaddaeus J. Buser; Raphael M. Macieira; Juliana M. Andrade; Hudson T. Pinheiro; Ciro C. Vilar; Caio R. Pimentel; João L. Gasparini; Thaís L. Quintão; Fabíola S. Machado; Gustavo Castellanos-Galindo; et al. (Reviews in Fish Biology and Fisheries, 2023)

Global responses to the COVID-19 pandemic by recreational anglers: considerations for developing more resilient and sustainable fisheries - J. Robert Britton; Adrian C. Pinder; Josep Alós; Robert Arlinghaus; Andy J. Danylchuk; Wendy Edwards; Kátia M. F. Freire; Casper Gundelund; Kieran Hyder; Ivan Jarić; Robert Lennox; Wolf-Christian Lewin; et al. (Reviews in Fish Biology and Fisheries, 2023)
The global COVID-19 pandemic resulted in many jurisdictions implementing orders restricting the movements of people to inhibit virus transmission, with recreational angling often either not permitted or access to fisheries and/or related infrastructure being prevented. Following the lifting of restrictions, initial angler surveys and licence sales suggested increased participation and effort, and altered angler demographics, but with evidence remaining limited. Here, we overcome this evidence gap by identifying temporal changes in angling interest, licence sales, and angling effort in world regions by comparing data in the ‘pre-pandemic’ (up to and including 2019); ‘acute pandemic’ (2020) and ‘COVID-acclimated’ (2021) periods. We then identified how changes can inform the development of more resilient and sustainable recreational fisheries. Interest in angling (measured here as angling-related internet search term volumes) increased substantially in all regions during 2020. Patterns in licence sales revealed marked increases in some countries during 2020 but not in others. Where licence sales increased, this was rarely sustained in 2021; where there were declines, these related to fewer tourist anglers due to movement restrictions. Data from most countries indicated a younger demographic of people who participated in angling in 2020, including in urban areas, but this was not sustained in 2021. These short-lived changes in recreational angling indicate efforts to retain younger anglers could increase overall participation levels, where efforts can target education in appropriate angling practices and create more urban angling opportunities. These efforts would then provide recreational fisheries with greater resilience to cope with future global crises, including facilitating the ability of people to access angling opportunities during periods of high societal stress.

SPASE metadata as a building block of a heliophysics science-enabling framework - Shing F. Fung; Arnaud Masson; Lee F. Bargatze; Todd King; Rebecca Ringuette; Robert M. Candey; Chiu Wiegand; Lan K. Jian; Darren De Zeeuw; Karin Muglach; Ryan M. McGranaghan; D. Aaron Roberts; et al. (Advances in Space Research, 2023)

Assessing the genetic diversity of Nymphoides peltata in the native and adventive range using microsatellite markers - Nicholas P. Tippery; Nathan E. Harms; Matthew F. Purcell; Sun Hee Hong; Patrick Häfliger; Katelin Killoy; Ashley L. Wolfe; Ryan A. Thum (Biological Invasions, 2023)

The Structural Response of the Human Head to a Vertex Impact - Darcy W. Thompson-Bagshaw; Ryan D. Quarrington; Andrew M. Dwyer; Nigel R. Jones; Claire F. Jones (Annals of Biomedical Engineering, 2023)
In experimental models of cervical spine trauma caused by near-vertex head-first impact, a surrogate headform may be substituted for the cadaveric head. To inform headform design and to verify that such substitution is valid, the force-deformation response of the human head with boundary conditions relevant to cervical spine head-first impact models is required. There are currently no biomechanics data that characterize the force-deformation response of the isolated head supported at the occiput and compressed at the vertex by a flat impactor. The effect of impact velocity (1, 2 or 3 m/s) on the response of human heads ( N = 22) subjected to vertex impacts, while supported by a rigid occipital mount, was investigated. 1 and 2 m/s impacts elicited force-deformation responses with two linear regions, while 3 m/s impacts resulted in a single linear region and skull base ring fractures. Peak force and stiffness increased from 1 to 2 and 3 m/s. Deformation at peak force and absorbed energy increased from 1 to 2 m/s, but decreased from 2 to 3 m/s. The data reported herein enhances the limited knowledge on the human head’s response to a vertex impact, which may allow for validation of surrogate head models in this loading scenario.

Direct injection liquid chromatography-tandem mass spectrometry as a sensitive and high-throughput method for the quantitative surveillance of antimicrobials in wastewater - Jinglong Li; Katja M. Shimko; Chang He; Brad Patterson; Richard Bade; Ryan Shiels; Jochen F. Mueller; Kevin V. Thomas; Jake W. O'Brien (Science of The Total Environment, 2023)

Tutorial: Electrodynamic balance methods for single particle levitation and the physicochemical analysis of aerosol - Ravleen Kaur Kohli; Ryan D. Davis; James F. Davies (Journal of Aerosol Science, 2023)

Evaluation of an in vitro experimental platform of human polarized intestinal epithelial monolayers for the hazard assessment of insecticidal proteins - Cindi S. Zimmermann; Ryan F. Snow; Brittany Wilson-Mifsud; Kristine LeRoy; Chad Boeckman; Emily Huang; Carey A. Mathesius; Jason M. Roper; Bryan P. Hurley (Food and Chemical Toxicology, 2023)

Tip loaded cyclodextrin-carvedilol complexes microarray patches - Qonita Kurnia Anjani; Akmal Hidayat Bin Sabri; Khuriah Abdul Hamid; Natalia Moreno-Castellanos; Huanhuan Li; Ryan F. Donnelly (Carbohydrate Polymers, 2023)

Evidence of increasing juvenile white sharks ' ( Carcharodon carcharias ) habitat use at the Northern Channel Islands - Ryan M. Freedman; James M. Anderson; Chris Caldow; Brian Stirling; Patrick Rex; Emily Spurgeon; Steve McCullough; Kady Lyons; Jack May; Connor F. White; Ryan K. Logan; Emily Meese; et al. (Journal of Fish Biology, 2023)
Juvenile white sharks ( Carcharodon carcharias ) typically aggregate along coastal beaches; however, high levels of recruitment and shifting oceanographic conditions may be causing habitat use expansions. Telemetry data indicate increased habitat use at the Northern Channel Islands (California, USA) by juvenile white shark that may be in response to increased population density at aggregation locations, or anomalous oceanographic events that impact habitat use or expand available habitat. Findings illustrate the need for long‐term movement monitoring and understanding drivers of habitat use shifts and expansion to improve ecosystem management.

Monitoring population-level foraging distribution of a marine migratory species from land: strengths and weaknesses of the isotopic approach on the Northwest Atlantic loggerhead turtle aggregation - Simona A. Ceriani; Susan Murasko; David S. Addison; David Anderson; Greg Curry; Nicole A. Desjardin; Scott F. Eastman; Daniel R. Evans; Nancy Evou; Mariana M. P. B. Fuentes; Matthew H. Godfrey; Kristen M. Hart; et al. (Frontiers in Marine Science, 2023)
Assessing the linkage between breeding and non-breeding areas has important implications for understanding the fundamental biology of and conserving animal species. This is a challenging task for marine species, and in sea turtles a combination of stable isotope analysis (SIA) and satellite telemetry has been increasingly used. The Northwest Atlantic (NWA) loggerhead ( Caretta caretta ) Regional Management Unit, one of the largest sea turtle populations in the world, provides an excellent opportunity to investigate key biological patterns as well as methodological aspects related to the use of stable isotopes to infer spatial distribution of turtles in foraging areas. We provide the first comprehensive assessment of the annual distribution of NWA adult female loggerheads among foraging areas and investigate the efficacy of various analytical approaches as well as the effect of sample size in these types of studies. A total of 5168 individual females were sampled from seven Management Units (MUs) between 2013-2018. We provide the first estimate of the proportion of females originating from each MU that uses each foraging area and show how this proportion varies over time. We also estimate the relative importance (in terms of number of turtles) of each foraging area to the overall loggerhead breeding aggregation nesting in Florida and in the NWA for each year of the study. The foraging area used by reproductively active females differs considerably across MUs. One of these, the Subtropical NWA, is by far the most important foraging area in terms of both number of individuals and genetic diversity, and therefore this region may be considered as a conservation priority. Through simulations, we show that limited sizes of sample groups (unknowns; training; priors) may result in false geographic differentiation and consequently mislead interpretations. We provide thresholds and methodological recommendations for future studies. This study establishes a fundamental baseline for monitoring the annual contribution of foraging area to a terrestrial-based breeding aggregation of a marine animal in a cost-effective way. This type of monitoring allows for early detection of changes in foraging distributions—a possible effect of climate change on marine ecosystems or of area-specific anthropogenic threats.

DESIGNER fraction concept unmasks minor bioactive constituents in red clover (Trifolium pratense L.) - Ryan Hitzman; Gonzalo R. Malca-Garcia; Caitlin Howell; Hyun-Young Park; J. Brent Friesen; Huali Dong; Tareisha Dunlap; James B. McAlpine; Guenter Vollmer; Maarten C. Bosland; Dejan Nikolić; David C. Lankin; et al. (Phytochemistry, 2023)

Assessing Fish and Macroinvertebrates Assemblages in Relation to Environmental Variables in Makuleke Floodplain Pans: Implications for Biodiversity Conservation - Linton F. Munyai; Lutendo Mugwedi; Ryan J. Wasserman; Farai Dondofema; Tatenda Dalu (Wetlands, 2023)

Spatial extent and isolation of marine artificial structures mediate fish density - Virginia A. Gilliland; Avery E. Fessler; Avery B. Paxton; Erik F. Ebert; Ryan M. Tharp; Brendan J. Runde; Nathan M. Bacheler; Jeffrey A. Buckel; J. Christopher Taylor (Frontiers in Marine Science, 2023)
Installations of artificial structures in coastal oceans create de facto habitat for marine life. These structures encompass wide varieties of physical characteristics, reflecting their multiple, diverse purposes and creating a need to understand which characteristics maximize fish habitat. Here, we test how physical characteristics – horizontal area, vertical relief, and spatial isolation – relate to fish density from echosounder surveys over artificial structures like concrete pipes, train boxcars, and ships purposely sunk to function as reefs. Echosounder mapping of 31 artificial reef structures and associated fish across a 200 km linear length of the continental shelf of North Carolina, USA, revealed that structures with greater horizontal area and vertical relief host higher fish densities than smaller, shorter structures. Artificial structure spatial arrangement also relates to fish density, as isolated structures are generally associated with greater localized fish densities than structures closer to one another. Patterns in the relationships between fish density and reef characteristics differed for schooling fish, as there was some evidence that reefs of intermediate area exhibited higher schooling fish density. These results suggest that intentional design and spatial arrangement of marine built structures like artificial reefs relates to and can be deliberately incorporated into siting and deployment decisions to enhance their role as fish habitat.

Potential environmental and nutritional benefits of replacing ruminant meat with forage fish - Shujuan Xia; Jun'ya Takakura; Wenchao Wu; Julia L. Blanchard; Ryan F. Heneghan; Takashi Yamakawa; Kazuaki Tsuchiya; Tomoko Hasegawa; Shinichiro Fujimori; Kiyoshi Takahashi (Sustainable Production and Consumption, 2023)

Correction to: Application of somatic embryogenesis for development of emerald ash borer-resistant white ash and green ash varietals - Scott A. Merkle; Jennifer L. Koch; A. Ryan Tull; Jessica E. Dassow; David W. Carey; Brittany F. Barnes; Mason W. M. Richins; Paul M. Montello; Kira R. Eidle; Logan T. House; Daniel A. Herms; Kamal J. K. Gandhi (New Forests, 2023)

Walleye and yellow perch resource use in large lakes invaded by spiny water fleas and zebra mussels - Bethany J. Bethke; Heidi M. Rantala; Tyler D. Ahrenstorff; Holly A. Wellard Kelly; Katya E. Kovalenko; Ryan P. Maki; Jodene K. Hirsch; Joshua D. Dumke; Valerie J. Brady; Jaime F. LeDuc; Gretchen J. A. Hansen (Aquatic Ecology, 2023)

Overview of the search for signs of space weathering on the low-albedo asteroid (101955) Bennu - B.E. Clark; A. Sen; X.-D. Zou; D.N. DellaGiustina; S. Sugita; N. Sakatani; M. Thompson; D. Trang; E. Tatsumi; M.A. Barucci; M. Barker; H. Campins; et al. (Icarus, 2023)

Understanding drivers of mercury in lake trout (Salvelinus namaycush), a top-predator fish in southwest Alaska's parklands - Krista K. Bartz; Michael P. Hannam; Tammy L. Wilson; Ryan F. Lepak; Jacob M. Ogorek; Daniel B. Young; Collin A. Eagles-Smith; David P. Krabbenhoft (Environmental Pollution, 2023)

Development of a HPLC fluorometric method for the quantification of enfuvirtide following in vitro releasing studies on thermosensitive in situ forming gel - Huanhuan Li; Qonita Kurnia Anjani; Mary B. McGuckin; Achmad Himawan; Mingshan Li; Ryan F. Donnelly (Drug Delivery and Translational Research, 2023)
Due to the presence of peptidase and protease in the gastrointestinal tract, peptides are subjected to digestion and inactivation when administrated orally. To avoid degradation and maintain the desired efficacy of peptide drugs, there is a demand to develop transdermal and intradermal delivery systems. This requires efficient and specific analytical methods to separate and quantify the peptide drugs from the formulation and the skin matrix in the early stages of pharmaceutical development. A high-performance liquid chromatography (HPLC) system equipped with a fluorometric detector was used to quantify enfuvirtide, which is the first fusion inhibitor for HIV treatment. The HPLC method was developed and validated according to the ICH Q2(R1) guidelines. The viability of the method was demonstrated during in vitro studies, where samples were analysed following intradermal administration of a thermosensitive in situ forming gel. Compared with previously reported methods, this assay proved efficient, sensitive and accurate, with a detection limit of 0.74 μg/mL and a run time of 9 min, mitigating the use of any internal standards and detergents. The addition of an organic solvent to the samples successfully solved the problem of low recovery caused by the adsorption of the drug to the plastic consumables in the sample treatment process. The amount of enfuvirtide releasing from the in situ gel through skin after 7 hours was 16.25 ± 7.08 μg, which was significantly lower than the reconstituted FUZEON ® itself (26.68 ± 10.45 μg), showing a longer release profile. The results may be beneficial as a constructive input for future enfuvirtide quantification within a preclinical setting through in vitro release studies across the skin. Graphical Abstract

Rapidly dissolving bilayer microneedles enabling minimally invasive and efficient protein delivery to the posterior segment of the eye - Yu Wu; Lalitkumar K. Vora; Ryan F. Donnelly; Thakur Raghu Raj Singh (Drug Delivery and Translational Research, 2023)
The discovery of proteins that neutralise vascular endothelial growth factors, such as pegaptanib, ranibizumab and aflibercept, can inhibit the process of angiogenesis, thereby restoring eyesight in individuals with retinal vascular disorders. However, due to the posterior location and chronic nature of retinal diseases, a safe and effective intraocular protein delivery system is currently lacking. Thus, dissolving bilayer microneedles (MNs) with the potential to deliver proteins to the back of the eye in an efficient and minimally invasive manner were developed in this study. A model protein, ovalbumin (OVA), was incorporated into MNs fabricated from different polymers, including hyaluronic acid (HA), polyvinyl alcohol (PVA) and polyvinylpyrrolidone (PVP). Optimised PVA/PVP MNs were demonstrated to be robust enough to pierce porcine sclera with > 75% of the needle length penetrating the sclera and dissolving within 150 s. SDS-PAGE and OVA-specific ELISA revealed that the bioactivity of the model protein was maintained during the manufacture of MNs. In hen’s egg-chorioallantoic membrane test, MNs fabricated from all chosen polymers were classified as non-irritants. Furthermore, ex vivo permeation studies showed that optimised MNs could permeate 86.99 ± 7.37% of OVA through the sclera, twice that of the needle-free patch (42.16 ± 3.95%), highlighting the capability of MNs to circumvent physical barriers and promote protein delivery to the posterior segment of the eye. In this work, a novel, efficient and safe intraocular protein delivery system was successfully established. Graphical abstract

Refining the in vitro release test method for a dapivirine-releasing vaginal ring to match in vivo performance - Diarmaid J. Murphy; Deanna Lim; Ryan Armstrong; Clare F. McCoy; Yahya H. Dallal Bashi; Peter Boyd; Tiffany Derrick; Patrick Spence; Bríd Devlin; R. Karl Malcolm (Drug Delivery and Translational Research, 2023)
Previously reported in vitro release test methods for drug-releasing vaginal rings containing poorly water-soluble drugs have described use of water-alcohol systems or surfactant solutions in efforts to maintain sink conditions. Here, as part of efforts to more closely match in vitro and in vivo release for the 25 mg dapivirine matrix-type silicone elastomer vaginal ring for HIV prevention, we have investigated alternatives to the 1:1 v/v water/isopropanol medium described previously. Specifically, we evaluated dapivirine release from rings into (i) monophasic water/isopropanol mixtures of varying compositions and (ii) biphasic buffer/octanol systems using pH 4.2 and pH 7.0 buffers. The rate and mechanism of dapivirine release were dependent upon the isopropanol concentration in the release medium, in accordance with the observed trend in drug solubility. At 0 and 10% v/v isopropanol concentrations, dapivirine release followed a partition-controlled mechansim. For media containing ≥ 20% v/v isopropanol, in vitro release of dapivirine was significantly increased and obeyed permeation-controlled kinetics. Cumulative release of ~3.5 mg dapivirine over 28 days was obtained using a water isopropanol mixture containing 20% v/v isopropanol, similar to the ~4 mg dapivirine released in vivo. Dapivirine release into the biphasic buffer/octanol system (intended to mimic the fluid/tissue environment in vivo) was constrained by the limited solubility of dapivirine in the buffer component in which the ring resided, such that cumulative dapivirine release was consistently lower than that observed with the 20% v/v isopropanol in water medium. Release into the biphasic system was also pH dependent, in line with dapivirine’s pK a and with potential implications for in vivo release and absorption in women with elevated vaginal pH. Graphical abstract

Third-generation adaptive capacity assessment for climate-resilient development - Carmen E. Elrick-Barr; Ryan Plummer; Timothy F. Smith (Climate and Development, 2023)

Developing flavor profiles for wheat varieties in a breeding program - Ryan Loy; F. Bailey Norwood; Renee Albers-Nelson (Journal of Cereal Science, 2023)

Development and Evaluation of Dissolving Microarray Patches for Co-administered and Repeated Intradermal Delivery of Long-acting Rilpivirine and Cabotegravir Nanosuspensions for Paediatric HIV Antiretroviral Therapy - Kurtis Moffatt; Ismaiel A. Tekko; Lalitkumar Vora; Fabiana Volpe-Zanutto; Aaron R. J. Hutton; Jessica Mistilis; Courtney Jarrahian; Nima Akhavein; Andrew D. Weber; Helen O. McCarthy; Ryan F. Donnelly (Pharmaceutical Research, 2023)
Purpose Whilst significant progress has been made to defeat HIV infection, the efficacy of antiretroviral (ARV) therapy in the paediatric population is often hindered by poor adherence. Currently, two long-acting (LA) intramuscular injectable nanosuspensions of rilpivirine (RPV) and cabotegravir (CAB) are in clinical development for paediatric populations. However, administration requires access to healthcare resources, is painful, and can result in needle-stick injuries to the end user. To overcome these barriers, this proof-of-concept study was developed to evaluate the intradermal delivery of RPV LA and CAB LA via self-disabling dissolving microarray patches (MAPs). Methods Dissolving MAPs of two conformations, a conventional pyramidal and a bilayer design, were formulated, with various nanosuspensions of RPV and CAB incorporated within the respective MAP matrix. MAPs were mechanically robust and were capable of penetrating ex vivo skin with intradermal ARV deposition. Results In a single-dose in vivo study in rats, all ARV MAPs demonstrated sustained release profiles, with therapeutically relevant plasma concentrations of RPV and CAB detected to at least 63 and 28 d, respectively. In a multi-dose in vivo study, repeated MAP applications at 14-d intervals maintained therapeutically relevant plasma concentrations throughout the duration of the study. Conclusions These results illustrate the potential of the platform to repeatedly maintain plasma concentrations for RPV and CAB. As such, these MAPs could represent a viable option to improve adherence in the paediatric population, one that is capable of being painlessly administered in the comfort of the patient’s own home on a biweekly or less frequent basis. Graphical abstract

Application of somatic embryogenesis for development of emerald ash borer-resistant white ash and green ash varietals - Scott A. Merkle; Jennifer L. Koch; A. Ryan Tull; Jessica E. Dassow; David W. Carey; Brittany F. Barnes; Mason W. M. Richins; Paul M. Montello; Kira R. Eidle; Logan T. House; Daniel A. Herms; Kamal J.K. Gandhi (New Forests, 2023)

A framework for establishing a rapid ‘Ōhi‘a death resistance program - Blaine C. Luiz; Christian P. Giardina; Lisa M. Keith; Douglass F. Jacobs; Richard A. Sniezko; Marc A. Hughes; James B. Friday; Philip Cannon; Robert Hauff; Kainana Francisco; Marian M. Chau; Nicklos Dudley; et al. (New Forests, 2023)
Metrosideros polymorpha Gaud. (‘ōhi‘a) is the most abundant native forest tree in Hawai‘i and a keystone species of cultural, ecological, and economic importance. ‘Ōhi‘a forests, particularly on Hawaiʻi Island, are being severely impacted by Rapid ‘Ōhi‘a Death (ROD), which is caused by the fungal pathogens Ceratocystis lukuohia and C. huliohia . ROD is characterized by branch dieback, crown wilting, and mortality. Initial disease resistance screening of four varieties of M. polymorpha with C. lukuohia demonstrated that varieties may differ in susceptibility. Several survivors of field or screening-based infections still exist, providing strong impetus for the establishment of the ‘Ōhiʻa Disease Resistance Program (ʻŌDRP). Here, we outline a framework for guiding the ʻŌDRP throughout the process of identifying and developing ROD resistance in M. polymorpha and, possibly, all Hawaiian Metrosideros species. Core ʻŌDRP projects include: (1) evaluating and operationalizing methods for greenhouse-based production and screening of test plants; (2) greenhouse screening of seedlings and rooted cuttings sampled from native Metrosideros throughout Hawaiʻi; (3) establishing field trials to validate results from greenhouse assays; (4) understanding environmental and genetic drivers of resistance to characterize the durability of resistance to ROD; (5) developing remote sensing and molecular methods to rapidly detect ROD-resistant individuals; and (6) conducting breeding trials to improve the degree and durability of ROD resistance. Ultimately, the ʻŌDRP seeks to produce ROD-resistant material for the perpetuation of M. polymorpha across Hawai‘i, with the goal of preserving the ecology, culture, and communities that are dependent on this tree species.

PFAS Exposures and the Human Metabolome: A Systematic Review of Epidemiological Studies - Sandra India-Aldana; Meizhen Yao; Vishal Midya; Elena Colicino; Leda Chatzi; Jaime Chu; Chris Gennings; Dean P. Jones; Ruth J. F. Loos; Veronica W. Setiawan; Mathew Ryan Smith; Ryan W. Walker; et al. (Current Pollution Reports, 2023)

Effects of developmental exposure to neurotoxic algal metabolites on predator-prey interactions in larval Pimephales promelas - Gina F. Lamka; Autum N. Auxier; Ally Swank; Katie Esarey; Hannah R. Mullinax; Ryan D. Seymour; Jessica L. Ward (Science of The Total Environment, 2023)

Corrigendum to “A functional size-spectrum model of the global marine ecosystem that resolves zooplankton composition”, Ecological Modelling, 2020, 435: 109265 - Ryan F. Heneghan; Jason D. Everett; Patrick Sykes; Sonia D. Batten; Martin Edwards; Kunio Takahashi; Iain M. Suthers; Julia L. Blanchard; Anthony J. Richardson (Ecological Modelling, 2023)

Sediment dispersal and basin evolution during contrasting tectonic regimes along the western Gondwanan margin in the central Andes - Amanda Z. Calle; Brian K. Horton; Raúl García; Ryan B. Anderson; Daniel F. Stockli; Peter P. Flaig; Sean P. Long (Journal of South American Earth Sciences, 2023)

Genetic and physical localization of a major susceptibility gene to Pyrenophora teres f. maculata in barley - Abdullah F. Alhashel; Jason D. Fiedler; Raja Sekhar Nandety; Ryan M. Skiba; Robert S. Bruggeman; Thomas Baldwin; Timothy L. Friesen; Shengming Yang (Theoretical and Applied Genetics, 2023)
Key message Genetic characterization of a major spot form net blotch susceptibility locus to using linkage mapping to identify a candidate gene and user-friendly markers in barley. Abstract Spot form net blotch (SFNB), caused by the necrotrophic fungal pathogen Pyrenophora teres f. maculata ( Ptm ), is an economically important foliar diseases in barley. Although various resistance loci have been identified, breeding for SFNB-resistant varieties has been hampered due to the complex virulence profile of Ptm populations. One resistance locus in the host may be effective against one specific isolate, but it may confer susceptibility to other isolates. A major susceptibility QTL on chromosome 7H, named Sptm1 , was consistently identified in many studies. In the present study, we conduct fine mapping to localize Sptm1 with high resolution. A segregating population was developed from selected F 2 progenies of the cross Tradition (S) × PI 67381 (R), in which the disease phenotype was determined by the Sptm1 locus alone. Disease phenotypes of critical recombinants were confirmed in the following two consecutive generations. Genetic mapping anchored the Sptm1 gene to an ⁓400 kb region on chromosome 7H. Gene prediction and annotation identified six protein-coding genes in the delimited Sptm1 region, and the gene encoding a putative cold-responsive protein kinase was selected as a strong candidate. Therefore, providing fine localization and candidate of Sptm1 for functional validation, our study will facilitate the understanding of susceptibility mechanism underlying the barley- Ptm interaction and offers a potential target for gene editing to develop valuable materials with broad-spectrum resistance to SFNB.

Trophic ecology of co‐occurring fishes in the Sundays River Valley irrigation ponds, assessed using stable isotope and gut content analyses - Lubabalo Mofu; Tatenda Dalu; Ryan J. Wasserman; Darragh J. Woodford; Olaf L. F. Weyl (Journal of Fish Biology, 2023)
The analysis of food web structures has increased the understanding of the dynamics of organisms belonging to different trophic levels. In this study, the diet of two native species, Glossogobius callidus and Gilchristella aestuaria , was assessed in the presence of two non‐native species, Oreochromis mossambicus and Gambusia affinis , in irrigation ponds, Eastern Cape Province, South Africa. The proportion of dietary items consumed and assimilated by the four fish species were inferred from gut contents and carbon and nitrogen stable isotope analysis. Stable isotope analysis revealed that both G . affinis and O . mossambicus had a larger isotopic niche size than G . callidus and G . aestuaria . Although G . callidus fed on benthic resources and G . aestuaria fed on phytoplankton, gut content analysis showed that G . callidus , O . mossambicus and G . affinis fed predominantly on benthic resources, whereas G . aestuaria fed mainly on plankton resources. Considerable niche overlap corroborates the view that resource competition is a major factor shaping the composition of the four fish species. This study highlighted the low diversity of the food web within the Sundays River Valley irrigation ponds, where food items are shared by all the small‐bodied fishes.

Vulnerability to climate change of managed stocks in the California Current large marine ecosystem - Michelle M. McClure; Melissa A. Haltuch; Ellen Willis-Norton; David D. Huff; Elliott L. Hazen; Lisa G. Crozier; Michael G. Jacox; Mark W. Nelson; Kelly S. Andrews; Lewis A.K. Barnett; Aaron M. Berger; Sabrina Beyer; et al. (Frontiers in Marine Science, 2023)
Introduction Understanding how abundance, productivity and distribution of individual species may respond to climate change is a critical first step towards anticipating alterations in marine ecosystem structure and function, as well as developing strategies to adapt to the full range of potential changes. Methods This study applies the NOAA (National Oceanic and Atmospheric Administration) Fisheries Climate Vulnerability Assessment method to 64 federally-managed species in the California Current Large Marine Ecosystem to assess their vulnerability to climate change, where vulnerability is a function of a species’ exposure to environmental change and its biological sensitivity to a set of environmental conditions, which includes components of its resiliency and adaptive capacity to respond to these new conditions. Results Overall, two-thirds of the species were judged to have Moderate or greater vulnerability to climate change, and only one species was anticipated to have a positive response. Species classified as Highly or Very Highly vulnerable share one or more characteristics including: 1) having complex life histories that utilize a wide range of freshwater and marine habitats; 2) having habitat specialization, particularly for areas that are likely to experience increased hypoxia; 3) having long lifespans and low population growth rates; and/or 4) being of high commercial value combined with impacts from non-climate stressors such as anthropogenic habitat degradation. Species with Low or Moderate vulnerability are either habitat generalists, occupy deep-water habitats or are highly mobile and likely to shift their ranges. Discussion As climate-related changes intensify, this work provides key information for both scientists and managers as they address the long-term sustainability of fisheries in the region. This information can inform near-term advice for prioritizing species-level data collection and research on climate impacts, help managers to determine when and where a precautionary approach might be warranted, in harvest or other management decisions, and help identify habitats or life history stages that might be especially effective to protect or restore.

Multisystemic eosinophilic epitheliotropic disease in three donkeys - Georgios Paraschou; Polly E. Vogel; Alison M. Lee; Ryan F. Trawford; Simon L. Priestnall (Journal of Comparative Pathology, 2023)

Long-term growing season aridity and grazing seasonality effects on perennial grass biomass in a Chihuahuan Desert rangeland - Sophia N. Lasché; Ryan W.R. Schroeder; Matthew M. McIntosh; Jacob E. Lucero; Sheri A. Spiegal; Micah P. Funk; Reldon F. Beck; Jerry L. Holechek; Akasha M. Faist (Journal of Arid Environments, 2023)

Natural organic matter source, concentration, and pH influences the toxicity of zinc to a freshwater microalga - Gwilym A.V. Price; Jenny L. Stauber; Dianne F. Jolley; Darren J. Koppel; Eric J. Van Genderen; Adam C. Ryan; Aleicia Holland (Environmental Pollution, 2023)

Is an MRI-derived anatomical measure of dementia risk also a measure of brain aging? - Ramon Casanova; Andrea M. Anderson; Ryan T. Barnard; Jamie N. Justice; Anna Kucharska-Newton; Beverly Gwen Windham; Priya Palta; Rebecca F. Gottesman; Thomas H. Mosley; Timothy M. Hughes; Lynne E. Wagenknecht; Stephen B. Kritchevsky (GeroScience, 2023)

Quantifying Cardiothoracic Variation with Posture and Respiration to Inform Cardiac Device Design - Geeth A. Kondaveeti; Varun A. Bhatia; Ryan P. Lahm; Megan L. Harris; James P. Gaewsky; F. Scott Gayzik; John F. Greenhalgh; Craig A. Hamilton; R. Brandon Stacey; Ashley A. Weaver (Cardiovascular Engineering and Technology, 2023)

Subcellular Accumulation and Depuration of Zinc in Periphytic Algae during Episodic and Continuous Exposures - Pete Cadmus; Ryan J. Friebertshauser; Nayla Rhein; Stephen F. Brinkman; William H. Clements (Archives of Environmental Contamination and Toxicology, 2023)
As the severity of extreme precipitation events increases with global climate change, so will episodic pulses of contamination into lotic systems. Periphytic algae represents bioindicator species in most freshwater systems due to their rapid accumulation of toxicants; therefore, it is vital to understand how accumulation in this group differs across temporally variable exposure regimes. The ability to rapidly accrue contaminants has additional implications for the trophic transfer of metals to primary consumers. While dietary toxicity has been studied in algivorous consumers, techniques used to prepare contaminated periphytic algae for consumption have not been compared. This study used a modified subcellular fractionation method to compare the partitioning of zinc (Zn) in periphyton cultures exposed for various durations (cultured in the presence of Zn and 15 min, 24 h, and 48 h exposures). Three exposure groups were additionally depurated over a period of 24 h in order to compare retention of Zn, an important aspect of preparing diets used in dietary toxicity studies. The results not only provide evidence for increased retention by periphytic algae cultured in the presence of Zn but reveal relationships among treatments and subcellular partitioning that suggest time-dependent accumulation and detoxification. These relationships suggest that episodic exposure of periphytic algae to contaminants may pose a greater risk than that of chronic regimes. Based on these results, we additionally advocate for culturing periphytic algae in the presence of contamination to produce a more reliable diet for dietary exposure testing in algivorous organisms.

Seasonal drivers of productivity and calcification in the coral Platygyra carnosa in a subtropical reef - Walter Dellisanti; Jeffery T. H. Chung; Sam K. F. Yiu; Ryan Ho Leung Tsang; Put Ang; Yip Hung Yeung; Jian-Wen Qiu; Shelby E. McIlroy; Mark L. Wells; Jiajun Wu; Leo Lei Chan (Frontiers in Marine Science, 2023)
Scleractinian corals are increasingly subjected to local stressors combined with global changes. In subtropical areas, corals exhibit metabolic plasticity and resilience in response to variability and extremes in local temperature, salinity, and light; however, the physiological mechanisms by which corals acclimate or adapt to these changing conditions remain disputed. We assessed the physiological status of the coral Platygyra carnosa during a two-year in situ monitoring survey. To obtain metabolic rates (respiration and photosynthesis), photochemical efficiency (Fv / Fm), and biocalcification measurements, non-invasive techniques such as underwater respirometry, Pulse Amplitude Modulated (PAM) fluorometry, total alkalinity measurements, and digital photography were used. Our findings show clear seasonality in water quality parameters, which affected coral health. Elevated temperatures during the summer were below the maximum monthly mean < 31°C) but reduced the energetic productivity of corals (-44% relative to winter). Fluctuations in salinity (25–38 ppt) and pH (7.65–8.44) were linked to rainfall and reduced calcification rates. The conditions during the spring were favorable for coral metabolism and calcification (+20% relative to summer). Overall, our research demonstrates that the metabolic plasticity of P. carnosa in response to shifts in seawater quality allows this species to survive ongoing environmental change. Our in situ observations provide fundamental insights into coral response mechanisms under changing environmental conditions and contribute to projections of coral health under future scenarios of global change.

Effects of watershed-scale green infrastructure retrofits on urban stormwater quality: A paired watershed study to quantify nutrient and sediment removal - Joseph S. Smith; Ryan J. Winston; David M. Wituszynski; R. Andrew Tirpak; Kathryn M. Boening-Ulman; Jay F. Martin (Ecological Engineering, 2023)

Vulnerable Waters are Essential to Watershed Resilience - Charles R. Lane; Irena F. Creed; Heather E. Golden; Scott G. Leibowitz; David M. Mushet; Mark C. Rains; Qiusheng Wu; Ellen D’Amico; Laurie C. Alexander; Genevieve A. Ali; Nandita B. Basu; Micah G. Bennett; et al. (Ecosystems, 2023)
Watershed resilience is the ability of a watershed to maintain its characteristic system state while concurrently resisting, adapting to, and reorganizing after hydrological (for example, drought, flooding) or biogeochemical (for example, excessive nutrient) disturbances. Vulnerable waters include non-floodplain wetlands and headwater streams, abundant watershed components representing the most distal extent of the freshwater aquatic network. Vulnerable waters are hydrologically dynamic and biogeochemically reactive aquatic systems, storing, processing, and releasing water and entrained (that is, dissolved and particulate) materials along expanding and contracting aquatic networks. The hydrological and biogeochemical functions emerging from these processes affect the magnitude, frequency, timing, duration, storage, and rate of change of material and energy fluxes among watershed components and to downstream waters, thereby maintaining watershed states and imparting watershed resilience. We present here a conceptual framework for understanding how vulnerable waters confer watershed resilience. We demonstrate how individual and cumulative vulnerable-water modifications (for example, reduced extent, altered connectivity) affect watershed-scale hydrological and biogeochemical disturbance response and recovery, which decreases watershed resilience and can trigger transitions across thresholds to alternative watershed states (for example, states conducive to increased flood frequency or nutrient concentrations). We subsequently describe how resilient watersheds require spatial heterogeneity and temporal variability in hydrological and biogeochemical interactions between terrestrial systems and down-gradient waters, which necessitates attention to the conservation and restoration of vulnerable waters and their downstream connectivity gradients. To conclude, we provide actionable principles for resilient watersheds and articulate research needs to further watershed resilience science and vulnerable-water management.

Exploring avenues for agricultural intensification: A case study for maize-soybean in the Southern US region - Ignacio Massigoge; Ana Carcedo; Andre Froes de Borja Reis; Clay Mitchell; Scott Day; Joaquin Oliverio; Sandra H. Truong; Ryan F. McCormick; Jose Rotundo; Sara Lira; Ignacio Ciampitti; Carlos D. Messina (Agricultural Systems, 2023)

Pseudocanariomyces americanus, gen. nov., sp. nov.: Update to the Management of a Periprosthetic Hip Infection - Joanna Dukes; Nestor Sosa; Connie F. Cañete-Gibas; Nathan P. Wiederhold; Keenan L. Ryan (Mycopathologia, 2022)

Resolving the Drivers of Algal Nutrient Limitation from Boreal to Arctic Lakes and Streams - Maria Myrstener; Megan L. Fork; Ann-Kristin Bergström; Isolde Callisto Puts; Demian Hauptmann; Peter D. F. Isles; Ryan M. Burrows; Ryan A. Sponseller (Ecosystems, 2022)
Nutrient inputs to northern freshwaters are changing, potentially altering aquatic ecosystem functioning through effects on primary producers. Yet, while primary producer growth is sensitive to nutrient supply, it is also constrained by a suite of other factors, including light and temperature, which may play varying roles across stream and lake habitats. Here, we use bioassay results from 89 lakes and streams spanning northern boreal to Arctic Sweden to test for differences in nutrient limitation status of algal biomass along gradients in colored dissolved organic carbon (DOC), water temperature, and nutrient concentrations, and to ask whether there are distinct patterns and drivers between habitats. Single nitrogen (N) limitation or primary N-limitation with secondary phosphorus (P) limitation of algal biomass was the most common condition for streams and lakes. Average response to N-addition was a doubling in biomass; however, the degree of limitation was modulated by the distinct physical and chemical conditions in lakes versus streams and across boreal to Arctic regions. Overall, algal responses to N-addition were strongest at sites with low background concentrations of dissolved inorganic N. Low temperatures constrained biomass responses to added nutrients in lakes but had weaker effects on responses in streams. Further, DOC mediated the response of algal biomass to nutrient addition differently among lakes and streams. Stream responses were dampened at higher DOC, whereas lake responses to nutrient addition increased from low to moderate DOC but were depressed at high DOC. Our results suggest that future changes in nutrient availability, particularly N, will exert strong effects on the trophic state of northern freshwaters. However, we highlight important differences in the physical and chemical factors that shape algal responses to nutrient availability in different parts of aquatic networks, which will ultimately affect the integrated response of northern aquatic systems to ongoing environmental changes.

A Review of the Compressive Stiffness of the Human Head - Darcy W. Thompson-Bagshaw; Ryan D. Quarrington; Claire F. Jones (Annals of Biomedical Engineering, 2022)
Synthetic surrogate head models are used in biomechanical studies to investigate skull, brain, and cervical spine injury. To ensure appropriate biofidelity of these head models, the stiffness is often tuned so that the surrogate’s response approximates the cadaveric response corridor. Impact parameters such as energy, and loading direction and region, can influence injury prediction measures, such as impact force and head acceleration. An improved understanding of how impact parameters affect the head’s structural response is required for designing better surrogate head models. This study comprises a synthesis and review of all existing ex vivo head stiffness data, and the primary factors that influence the force–deformation response are discussed. Eighteen studies from 1972 to 2019 were identified. Head stiffness statistically varied with age (pediatric vs. adult), loading region, and rate. The contact area of the impactor likely affects stiffness, whereas the impactor mass likely does not. The head’s response to frontal impacts was widely reported, but few studies have evaluated the response to other impact locations and directions. The findings from this review indicate that further work is required to assess the effect of head constraints, loading region, and impactor geometry, across a range of relevant scenarios.

Invasive slipper limpets (Crepidula fornicata) act like a sink, rather than source, of Vibrio spp. - Emma A. Quinn; Sophie H. Malkin; Jessica E. Thomas; Ryan Poole; Charlotte E. Davies; Andrew F. Rowley; Christopher J. Coates (Biological Invasions, 2022)
A large knowledge gap exists regarding the disease profile and pathologic condition of the invasive, slipper limpet Crepidula fornicata . To help address this, we performed a year-long health survey at two sites in South Wales, UK – subtidal Swansea Bay and intertidal Milford Haven. In total, 1,800 limpets were screened systematically for haemolymph bacterial burdens using both general and vibrio-selective growth media (TSA + 2% NaCl and TCBS, respectively), haemolymph (blood) inspection using microscopy, a PCR-based assay targeting Vibrio spp., and multi-tissue histology. Over 99% of haemolymph samples contained cultivable bacterial colony-forming units, and 83% of limpets tested positive for the presence of vibrios via PCR (confirmed via Sanger sequencing). Vibrio presence did not vary greatly between sites, yet a strong seasonal effect was observed with significantly higher bacterial loads during the summer. Binomial logistic regression models revealed larger (older) limpets were more likely to harbour vibrios, and the growth of bacteria on TCBS was a key predictor for PCR-based vibrio detection. Histological assessment of > 340 animals revealed little evidence of inflammation, sepsis or immune reactivity despite the gross bacterial numbers. We contend that slipper limpets are not highly susceptible to bacteriosis at either site, and do not harbour vibrios known to be pathogenic to humans. The lack of susceptibility to local pathogenic bacteria may explain, in part, the invasion success of C. fornicata across this region.

In Vitro Permeation Studies on Carvedilol Containing Dissolving Microarray Patches Quantified Using a Rapid and Simple HPLC-UV Analytical Method - Qonita Kurnia Anjani; Akmal Hidayat Bin Sabri; Mary B. McGuckin; Huanhuan Li; Khuriah Abdul Hamid; Ryan F. Donnelly (AAPS PharmSciTech, 2022)
Analytical method validation is a vital element of drug formulation and delivery studies. Here, high-performance liquid chromatography in conjunction with UV detection (HPLC-UV) has been used to produce a straightforward, quick, yet sensitive analytical approach to quantify carvedilol (CAR). A C18 column was used to isolate the analyte from the mixture by isocratic elution with a mobile phase comprising a mixture of 0.1% v/v trifluoroacetic acid in water and acetonitrile in a ratio of 65:35 v/v at a flow rate of 0.6 mL min −1 . Linearity was observed for CAR concentrations within the range of 1.5–50 μg mL −1 ( R 2 = 0.999) in phosphate buffer saline and within the range of 0.2–6.2 μg mL −1 ( R 2 = 0.9999) in methanol. The International Council on Harmonization (ICH) requirements were followed throughout the validation of the isocratic approach, rendering it specific, accurate, and precise. Moreover, robustness tests indicated that the method remained selective and specific despite small deliberate changes to environmental and operational factors. An efficient extraction procedure was also developed to extract and quantify CAR from excised neonatal porcine skin, resulting in recovery rates ranging from 95 to 97%. The methods reported here have been successfully utilised to evaluate CAR permeation, both transdermally and intradermally following application of a dissolving microarray patch (MAP) to excised neonatal porcine skin. Graphical Abstract

A critical comparison of integral projection and matrix projection models for demographic analysis: Reply - Daniel F. Doak; Ellen Waddle; Ryan E. Langendorf; Allison M. Louthan; Nathalie Isabelle Chardon; Reilly Dibner; Robert K. Shriver; Cristina Linares; Maria Begoña Garcia; Sarah W. Fitzpatrick; William F. Morris; Megan L. DeMarche (Ecology, 2022)

How much city is too much city? Biodiversity and ecosystem functioning along an urban gradient at the interface of land and sea - Jameal F. Samhouri; Andrew Olaf Shelton; Gregory D. Williams; Blake E. Feist; Shannon M. Hennessey; Krista Bartz; Ryan P. Kelly; James L. O’Donnell; Mindi Sheer; Adrian C. Stier; Phillip S. Levin (Frontiers in Marine Science, 2022)
A huge proportion of the world’s population resides in urban areas along the coast. As cities expand, the ability of coastal ecosystems to provide the benefits people derive from nature, ranging from food from fisheries to coastal defense to maritime transportation and beyond, is in question. While it is well understood that coastal development changes ecosystems, quantitative insights about how terrestrial urbanization fundamentally alters ecosystem structure and function in adjacent freshwater and downstream coastal marine habitats remain rare, though a general expectation is that impacts of terrestrial urbanization will attenuate from land to freshwater to coastal marine habitats. Empirical assessments of these phenomena are especially important for species that rely on freshwater and coastal marine habitats at multiple points in their life cycles, including endangered and threatened Pacific salmon ( Oncorhynchus spp.). We investigated associations between landscape-scale urbanization and ecosystem structure (biodiversity of epibenthic invertebrate taxa) and function (benthic net primary productivity and decomposition) in freshwater and coastal marine habitats across six pairs of more and less urbanized, coastal watersheds in Puget Sound, WA, USA, using principal components analysis, analysis of covariance, and Mantel tests. Greater upland urbanization was associated with greater reductions in freshwater biodiversity, measured as the density and evenness of epibenthic invertebrate families. In contrast and surprisingly, however, coastal marine biodiversity (measured as the density and evenness of epibenthic invertebrate families) tended to be higher at more urbanized sites, suggesting the potential role of low to moderate levels of urbanization-related disturbance in determining coastal marine biodiversity patterns. We found no statistical association between urbanization and freshwater and coastal marine ecosystem functions, estimated from changes in accumulated algal biomass on tiles (benthic net primary productivity) and loss of biomass from litter bags (decomposition). In addition, there was no evidence that changes in ecosystem structure and function with urbanization were more severe in freshwater than coastal marine habitats, as might be expected if the land-sea boundary diminished effects of landscape-scale urbanization. Our results suggest that the effects of urbanization can be complex and that attention to terrestrial, freshwater, and coastal marine systems in concert will produce more effective, ecosystem-based management.

Tallo: A global tree allometry and crown architecture database - Tommaso Jucker; Fabian Jörg Fischer; Jérôme Chave; David A. Coomes; John Caspersen; Arshad Ali; Grace Jopaul Loubota Panzou; Ted R. Feldpausch; Daniel Falster; Vladimir A. Usoltsev; Stephen Adu‐Bredu; Luciana F. Alves; et al. (Global Change Biology, 2022)
Data capturing multiple axes of tree size and shape, such as a tree's stem diameter, height and crown size, underpin a wide range of ecological research—from developing and testing theory on forest structure and dynamics, to estimating forest carbon stocks and their uncertainties, and integrating remote sensing imagery into forest monitoring programmes. However, these data can be surprisingly hard to come by, particularly for certain regions of the world and for specific taxonomic groups, posing a real barrier to progress in these fields. To overcome this challenge, we developed the Tallo database, a collection of 498,838 georeferenced and taxonomically standardized records of individual trees for which stem diameter, height and/or crown radius have been measured. These data were collected at 61,856 globally distributed sites, spanning all major forested and non‐forested biomes. The majority of trees in the database are identified to species (88%), and collectively Tallo includes data for 5163 species distributed across 1453 genera and 187 plant families. The database is publicly archived under a CC‐BY 4.0 licence and can be access from: https://doi.org/10.5281/zenodo.6637599 . To demonstrate its value, here we present three case studies that highlight how the Tallo database can be used to address a range of theoretical and applied questions in ecology—from testing the predictions of metabolic scaling theory, to exploring the limits of tree allometric plasticity along environmental gradients and modelling global variation in maximum attainable tree height. In doing so, we provide a key resource for field ecologists, remote sensing researchers and the modelling community working together to better understand the role that trees play in regulating the terrestrial carbon cycle.

Tree crown damage and its effects on forest carbon cycling in a tropical forest - Jessica F. Needham; Gabriel Arellano; Stuart J. Davies; Rosie A. Fisher; Valerie Hammer; Ryan G. Knox; David Mitre; Helene C. Muller‐Landau; Daniel Zuleta; Charlie D. Koven (Global Change Biology, 2022)
Crown damage can account for over 23% of canopy biomass turnover in tropical forests and is a strong predictor of tree mortality; yet, it is not typically represented in vegetation models. We incorporate crown damage into the Functionally Assembled Terrestrial Ecosystem Simulator (FATES), to evaluate how lags between damage and tree recovery or death alter demographic rates and patterns of carbon turnover. We represent crown damage as a reduction in a tree's crown area and leaf and branch biomass, and allow associated variation in the ratio of aboveground to belowground plant tissue. We compare simulations with crown damage to simulations with equivalent instant increases in mortality and benchmark results against data from Barro Colorado Island (BCI), Panama. In FATES, crown damage causes decreases in growth rates that match observations from BCI. Crown damage leads to increases in carbon starvation mortality in FATES, but only in configurations with high root respiration and decreases in carbon storage following damage. Crown damage also alters competitive dynamics, as plant functional types that can recover from crown damage outcompete those that cannot. This is a first exploration of the trade‐off between the additional complexity of the novel crown damage module and improved predictive capabilities. At BCI, a tropical forest that does not experience high levels of disturbance, both the crown damage simulations and simulations with equivalent increases in mortality does a reasonable job of capturing observations. The crown damage module provides functionality for exploring dynamics in forests with more extreme disturbances such as cyclones and for capturing the synergistic effects of disturbances that overlap in space and time.

Coralline Hills: high complexity reef habitats on seamount summits of the Vitória-Trindade Chain - Helder Coelho Guabiroba; Luiz A. Rocha; Jean-Christophe Joyeux; Caio R. Pimentel; João Batista Teixeira; Raphael M. Macieira; João Luiz Gasparini; Ronaldo Bastos Francini-Filho; Ryan Andrades; Eric Mazzei; Thiony Simon; Marina Sissini; et al. (Coral Reefs, 2022)

Genomic erosion in a demographically recovered bird species during conservation rescue - Hazel A. Jackson; Lawrence Percival‐Alwyn; Camilla Ryan; Mohammed F. Albeshr; Luca Venturi; Hernán E. Morales; Thomas C. Mathers; Jonathan Cocker; Samuel A. Speak; Gonzalo G. Accinelli; Tom Barker; Darren Heavens; et al. (Conservation Biology, 2022)
The pink pigeon ( Nesoenas mayeri ) is an endemic species of Mauritius that has made a remarkable recovery after a severe population bottleneck in the 1970s to early 1990s. Prior to this bottleneck, an ex situ population was established from which captive‐bred individuals were released into free‐living subpopulations to increase population size and genetic variation. This conservation rescue led to rapid population recovery to 400–480 individuals, and the species was twice downlisted on the International Union for the Conservation of Nature (IUCN) Red List. We analyzed the impacts of the bottleneck and genetic rescue on neutral genetic variation during and after population recovery (1993–2008) with restriction site‐associated sequencing, microsatellite analyses, and quantitative genetic analysis of studbook data of 1112 birds from zoos in Europe and the United States. We used computer simulations to study the predicted changes in genetic variation and population viability from the past into the future. Genetic variation declined rapidly, despite the population rebound, and the effective population size was approximately an order of magnitude smaller than census size. The species carried a high genetic load of circa 15 lethal equivalents for longevity. Our computer simulations predicted continued inbreeding will likely result in increased expression of deleterious mutations (i.e., a high realized load) and severe inbreeding depression. Without continued conservation actions, it is likely that the pink pigeon will go extinct in the wild within 100 years. Conservation rescue of the pink pigeon has been instrumental in the recovery of the free‐living population. However, further genetic rescue with captive‐bred birds from zoos is required to recover lost variation, reduce expression of harmful deleterious variation, and prevent extinction. The use of genomics and modeling data can inform IUCN assessments of the viability and extinction risk of species, and it helps in assessments of the conservation dependency of populations.

FDA Approaches in Monitoring Drug Quality, Forces Impacting the Drug Quality, and Recent Alternative Strategies to Assess Quality in the US Drug Supply - Philip J. Almeter; James T. Isaacs; Aaron N. Hunter; Bradley S. Henderson; Thomas Platt; Billie J. Mitchell; David Do; Alyssa B. Brainard; Joshua E. Brown; Rachael M. Stone; Bao-Han Nguyen; Matthew F. Warren; et al. (Journal of Pharmaceutical Innovation, 2022)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Assessing the risk of human‐to‐wildlife pathogen transmission for conservation and public health - Anna C. Fagre; Lily E. Cohen; Evan A. Eskew; Max Farrell; Emma Glennon; Maxwell B. Joseph; Hannah K. Frank; Sadie J. Ryan; Colin J Carlson; Gregory F. Albery (Ecology Letters, 2022)
The SARS‐CoV‐2 pandemic has led to increased concern over transmission of pathogens from humans to animals, and its potential to threaten conservation and public health. To assess this threat, we reviewed published evidence of human‐to‐wildlife transmission events, with a focus on how such events could threaten animal and human health. We identified 97 verified examples, involving a wide range of pathogens; however, reported hosts were mostly non‐human primates or large, long‐lived captive animals. Relatively few documented examples resulted in morbidity and mortality, and very few led to maintenance of a human pathogen in a new reservoir or subsequent “secondary spillover” back into humans. We discuss limitations in the literature surrounding these phenomena, including strong evidence of sampling bias towards non‐human primates and human‐proximate mammals and the possibility of systematic bias against reporting human parasites in wildlife, both of which limit our ability to assess the risk of human‐to‐wildlife pathogen transmission. We outline how researchers can collect experimental and observational evidence that will expand our capacity for risk assessment for human‐to‐wildlife pathogen transmission.

Synthesizing Empirical and Modelling Studies to Predict Past and Future Primary Production in the North Sea - Michael A. Spence; Christopher P. Lynam; Robert B. Thorpe; Ryan F. Heneghan; Paul J. Dolder (Frontiers in Marine Science, 2022)
Understanding change at the base of the marine foodwebs is fundamental to understanding how climate change can impact fisheries. However, there is a shortage of empirical measurements of primary productivity, and models estimates often disagree with each other by an order of magnitude or more. In this study we incorporate information from empirical studies and a suite of Earth system models statistically downscaled using an ensemble model to produce estimates of North Sea primary production with robust quantification of uncertainties under two different climate scenarios. The results give a synthesised estimate of primary production that can feed into regional fisheries models. We found that Earth system models describe the dynamics of primary production in the North Sea poorly, and therefore the effects of climate change on future primary production are uncertain. The methods demonstrated here can be applied to other geographical locations and are not limited in application to primary production.

Wildfire, Smoke Exposure, Human Health, and Environmental Justice Need to be Integrated into Forest Restoration and Management - Savannah M. D’Evelyn; Jihoon Jung; Ernesto Alvarado; Jill Baumgartner; Pete Caligiuri; R. Keala Hagmann; Sarah B. Henderson; Paul F. Hessburg; Sean Hopkins; Edward J. Kasner; Meg A. Krawchuk; Jennifer E. Krenz; et al. (Current Environmental Health Reports, 2022)
Purpose of Review Increasing wildfire size and severity across the western United States has created an environmental and social crisis that must be approached from a transdisciplinary perspective. Climate change and more than a century of fire exclusion and wildfire suppression have led to contemporary wildfires with more severe environmental impacts and human smoke exposure. Wildfires increase smoke exposure for broad swaths of the US population, though outdoor workers and socially disadvantaged groups with limited adaptive capacity can be disproportionally exposed. Exposure to wildfire smoke is associated with a range of health impacts in children and adults, including exacerbation of existing respiratory diseases such as asthma and chronic obstructive pulmonary disease, worse birth outcomes, and cardiovascular events. Seasonally dry forests in Washington, Oregon, and California can benefit from ecological restoration as a way to adapt forests to climate change and reduce smoke impacts on affected communities. Recent Findings Each wildfire season, large smoke events, and their adverse impacts on human health receive considerable attention from both the public and policymakers. The severity of recent wildfire seasons has state and federal governments outlining budgets and prioritizing policies to combat the worsening crisis. This surging attention provides an opportunity to outline the actions needed now to advance research and practice on conservation, economic, environmental justice, and public health interests, as well as the trade-offs that must be considered. Summary Scientists, planners, foresters and fire managers, fire safety, air quality, and public health practitioners must collaboratively work together. This article is the result of a series of transdisciplinary conversations to find common ground and subsequently provide a holistic view of how forest and fire management intersect with human health through the impacts of smoke and articulate the need for an integrated approach to both planning and practice.

Disruption of miR-18a Alters Proliferation, Photoreceptor Replacement Kinetics, Inflammatory Signaling, and Microglia/Macrophage Numbers During Retinal Regeneration in Zebrafish - Evin Magner; Pamela Sandoval-Sanchez; Ashley C. Kramer; Ryan Thummel; Peter F. Hitchcock; Scott M. Taylor (Molecular Neurobiology, 2022)

The Effect of Axial Compression and Distraction on Cervical Facet Cartilage Apposition During Shear and Bending Motions - Ryan D. Quarrington; Darcy W. Thompson-Bagshaw; Claire F. Jones (Annals of Biomedical Engineering, 2022)
During cervical spine trauma, complex intervertebral motions can cause a reduction in facet joint cartilage apposition area (CAA), leading to cervical facet dislocation (CFD). Intervertebral compression and distraction likely alter the magnitude and location of CAA, and may influence the risk of facet fracture. The aim of this study was to investigate facet joint CAA resulting from intervertebral distraction (2.5 mm) or compression (50, 300 N) superimposed on shear and bending motions. Intervertebral and facet joint kinematics were applied to multi rigid-body kinematic models of twelve C6/C7 motion segments (70 ± 13 year, nine male) with specimen-specific cartilage profiles. CAA was qualitatively and quantitatively compared between distraction and compression conditions for each motion; linear mixed-effects models ( α = 0.05) were applied. Distraction significantly decreased CAA throughout all motions, compared to the compressed conditions ( p

Expert range maps of global mammal distributions harmonised to three taxonomic authorities - Charles J. Marsh; Yanina V. Sica; Connor J. Burgin; Wendy A. Dorman; Robert C. Anderson; Isabel del Toro Mijares; Jessica G. Vigneron; Vijay Barve; Victoria L. Dombrowik; Michelle Duong; Robert Guralnick; Julie A. Hart; et al. (Journal of Biogeography, 2022)
Aim Comprehensive, global information on species' occurrences is an essential biodiversity variable and central to a range of applications in ecology, evolution, biogeography and conservation. Expert range maps often represent a species' only available distributional information and play an increasing role in conservation assessments and macroecology. We provide global range maps for the native ranges of all extant mammal species harmonised to the taxonomy of the Mammal Diversity Database (MDD) mobilised from two sources, the Handbook of the Mammals of the World (HMW) and the Illustrated Checklist of the Mammals of the World (CMW). Location Global. Taxon All extant mammal species. Methods Range maps were digitally interpreted, georeferenced, error‐checked and subsequently taxonomically aligned between the HMW (6253 species), the CMW (6431 species) and the MDD taxonomies (6362 species). Results Range maps can be evaluated and visualised in an online map browser at Map of Life ( mol.org ) and accessed for individual or batch download for non‐commercial use. Main conclusion Expert maps of species' global distributions are limited in their spatial detail and temporal specificity, but form a useful basis for broad‐scale characterizations and model‐based integration with other data. We provide georeferenced range maps for the native ranges of all extant mammal species as shapefiles, with species‐level metadata and source information packaged together in geodatabase format. Across the three taxonomic sources our maps entail, there are 1784 taxonomic name differences compared to the maps currently available on the IUCN Red List website. The expert maps provided here are harmonised to the MDD taxonomic authority and linked to a community of online tools that will enable transparent future updates and version control.

Rapid radiation of Southern Ocean shags in response to receding sea ice - Nicolas J. Rawlence; Alexander T. Salis; Hamish G. Spencer; Jonathan M. Waters; Lachie Scarsbrook; Kieren J. Mitchell; Richard A. Phillips; Luciano Calderón; Timothée R. Cook; Charles‐André Bost; Ludovic Dutoit; Tania M. King; et al. (Journal of Biogeography, 2022)
Aim Understanding how natural populations respond to climatic shifts is a fundamental goal of biological research in a fast‐changing world. The Southern Ocean represents a fascinating system for assessing large‐scale climate‐driven biological change, as it contains extremely isolated island groups within a predominantly westerly, circumpolar wind and current system. Blue‐eyed shags represent a paradoxical seabird radiation—a circumpolar distribution implies strong dispersal capacity yet their species‐rich nature suggests local adaptation and isolation. Here we attempt to resolve this paradox in light of the history of repeated cycles of climate change in the Southern Ocean. Location Southern Ocean. Taxa 16 species and subspecies of blue‐eyed shags (Phalacrocoracidae; Leucocarbo spp.). Methods We use mitochondrial and nuclear sequence data from individuals across the geographical range of the genus to conduct the first comprehensive, time‐calibrated phylogenetic analyses and ancestral‐range biogeographical reconstructions of the blue‐eyed shags. Results The origins of many island‐endemic lineages are remarkably recent, consistent with a recent high‐latitude circumpolar radiation in the Pliocene or Early Pleistocene. This recent sub‐Antarctic expansion contrasts with significantly deeper lineages detected in South America and, to a lesser extent, New Zealand. These regions, particularly South America, acted as glacial refugia and sources for multiple waves of post‐glacial dispersal. Main conclusions The blue‐eyed shag paradox is resolved, with at least two waves of dispersal, linked to interglacial cycles, explaining the current distribution and diversity. Descendants of a Pliocene or Early Pleistocene wave of dispersal out of South America survive in the New Zealand region. In contrast, taxa distributed on sub‐Antarctic islands originated much later, possibly since the Last Glacial Maximum. Blue‐eyed shags therefore represent a powerful model system—comprising several natural replicates—for studying the early stages of founder‐event speciation and adaptation in a Southern‐Ocean bird group.

Translational advancements in transdermal and mucosal delivery - Emmanuel A. Ho; Ryan F. Donnelly (Drug Delivery and Translational Research, 2022)

Nanoemulsion-based dissolving microneedle arrays for enhanced intradermal and transdermal delivery - Muhammad Iqbal Nasiri; Lalitkumar K. Vora; Juhaina Abu Ershaid; Ke Peng; Ismaiel A. Tekko; Ryan F. Donnelly (Drug Delivery and Translational Research, 2022)
The development of dissolving microneedles (DMN) is one of the advanced technologies in transdermal drug delivery systems, which precisely deliver the drugs through a rapid dissolution of polymers after insertion into the skin. In this study, we fabricated nanoemulsion-loaded dissolving microneedle (DMN) arrays for intradermal and transdermal drug delivery. For this task, model drug (amphotericin B, AmB)-loaded nanoemulsion (NE) were prepared by the probe-sonication method. AmB-loaded-NE was prepared using Capmul MCM C-8 EP/NF, Tween ® 80, poly(vinyl alcohol) (PVA-10 kDa), and poly (vinyl pyrrolidone) (PVP-360 kDa or K29/32) by using SpeedMixer™, followed by probe-sonication and evaluated for particle size and polydispersity index (PDI). Transmission electron microscopy (TEM) was also used to assess the particle size before and after DMN casting. AmB-NE embedded DMN arrays were found to be strong enough, revealed efficient skin insertion, and penetrated down to the fourth layer (depth ≈ 508 μm) of Parafilm M ® (validated skin model). Ex vivo skin deposition experiments in full-thickness neonatal porcine demonstrated that after 24 h, AmB-NE-DMN arrays were able to deposit 111.05 ± 48.4 µg/patch AmB into the skin. At the same time, transdermal porcine skin permeation studies showed significantly higher permeability of AmB (29.60 ± 8.23 μg/patch) from AmB-NE-DMN compared to MN-free AmB-NE patches (5.0 ± 6.15 μg/patch) over 24 h. Antifungal studies of optimized AmB-NE-DMN, AmB-loaded discs and drug-free DMN against Candida albicans , confirmed the synergistic activity of Campul-MCM C-8, used in the nanoemulsion formulation. This study establishes that nanoemulsion based dissolving microneedle may serve as an efficient system for intradermal as well as transdermal drug delivery. Graphical abstract

Designing a unique feedback mechanism for hydrogel-forming microneedle array patches: a concept study - Aaron R. J. Hutton; Melissa Kirkby; Eneko Larrañeta; Ryan F. Donnelly (Drug Delivery and Translational Research, 2022)
Although microneedle array patch (MAP) technology is reaching ever closer to regulatory approval, it remains imperative that approaches to further improve patient acceptance are still explored. Addressing this perception, a water-filled reservoir was incorporated into a hydrogel-forming MAP system to provide a novel feedback mechanism. To confirm successful MAP skin insertion, the end user would both hear and feel the rupture of the water-filled reservoir. Interestingly, a 50-µL water-filled reservoir ruptured at 30.27 ± 0.39 N, which has previously been shown as the mean application force for MN insertion in human subjects following appropriate instruction. Importantly, no significant difference in % cumulative permeation of FITC-dextran 10 kDa and fluorescein sodium after 24 h was observed between a 50-µL reservoir and the current method of application that has been successfully used in both in vitro and in vivo studies ( p > 0.05). Therefore, as drug delivery was not affected, this proof-of-concept study has shown that a water-filled reservoir feedback mechanism has the potential to serve as a viable tool for consistent MAP skin insertion. Graphical abstract

Rapidly dissolving microneedle patch of amphotericin B for intracorneal fungal infections - Alyaa A. Albadr; Ismaiel A. Tekko; Lalitkumar K. Vora; Ahlam A. Ali; Garry Laverty; Ryan F. Donnelly; Raghu Raj Singh Thakur (Drug Delivery and Translational Research, 2022)
Chronic fungal infection of the cornea could lead to blindness if not treated properly. Topical amphotericin B (AMP-B) is considered the first treatment of choice for ocular fungal infection. However, factors related to its poor solubility and penetration through intact cornea lead to poor bioavailability. Microneedles (MNs) are emerging as a minimally invasive method to enhance ocular drug delivery. This study aims to investigate the potential use of biodegradable poly(vinylpyrrolidone) (PVP) and hyaluronic acid (HA)–based rapidly dissolving MNs for delivery of AMP-B to treat fungal infection. The data obtained illustrates PVP/HA MN arrays’ reproducibility, good mechanical strength, and faster dissolution with 100% drug recovery. Multiphoton microscopic results revealed that MNs successfully penetrate the corneal tissue and enhance AMP-B permeation through corneal layers. Furthermore, PVP/HA MN arrays showed high solubility. Both PVP and HA successfully decreased AMP-B cytotoxicity when compared to free drug. More interestingly, the biocompatible MN formulations preserved the antifungal activity of AMP-B, as demonstrated by significant inhibition of fungal growth. Therefore, this study shows the feasibility of ocular delivery of the poorly soluble AMP-B using a fast-dissolving MN patch. Graphical abstract

Enhancement strategies for transdermal drug delivery systems: current trends and applications - Delly Ramadon; Maeliosa T. C. McCrudden; Aaron J. Courtenay; Ryan F. Donnelly (Drug Delivery and Translational Research, 2022)
Transdermal drug delivery systems have become an intriguing research topic in pharmaceutical technology area and one of the most frequently developed pharmaceutical products in global market. The use of these systems can overcome associated drawbacks of other delivery routes, such as oral and parenteral. The authors will review current trends, and future applications of transdermal technologies, with specific focus on providing a comprehensive understanding of transdermal drug delivery systems and enhancement strategies. This article will initially discuss each transdermal enhancement method used in the development of first-generation transdermal products. These methods include drug/vehicle interactions, vesicles and particles, stratum corneum modification, energy-driven methods and stratum corneum bypassing techniques. Through suitable design and implementation of active stratum corneum bypassing methods, notably microneedle technology, transdermal delivery systems have been shown to deliver both low and high molecular weight drugs. Microneedle technology platforms have proven themselves to be more versatile than other transdermal systems with opportunities for intradermal delivery of drugs/biotherapeutics and therapeutic drug monitoring. These have shown that microneedles have been a prospective strategy for improving transdermal delivery systems. Graphical abstract

Larvicidal activity against Aedes aegypti and molecular docking studies of compounds extracted from the endophytic fungus Aspergillus sp. isolated from Bertholletia excelsa Humn. & Bonpl - Inana F. Araújo; Victor Hugo de S. Marinho; Iracirema da S. Sena; Jhone M. Curti; Ryan da S. Ramos; Ricardo M. A. Ferreira; Raimundo N. P. Souto; Irlon M. Ferreira (Biotechnology Letters, 2022)

Two common bee-sampling methods reflect different assemblages of the bee (Hymenoptera: Apoidea) community in mixed-grass prairie systems and are dependent on surrounding floral resource availability - C. K. Pei; Torre J. Hovick; Cameron A. Duquette; Ryan F. Limb; Jason P. Harmon; Benjamin A. Geaumont (Journal of Insect Conservation, 2022)

Review of Mercury’s dynamic magnetosphere: Post-MESSENGER era and comparative magnetospheres - Weijie Sun; Ryan M. Dewey; Sae Aizawa; Jia Huang; James A. Slavin; Suiyan Fu; Yong Wei; Charles F. Bowers (Science China Earth Sciences, 2022)
This review paper summarizes the research of Mercury’s magnetosphere in the Post-MESSENGER era and compares its dynamics to those in other planetary magnetospheres, especially to those in Earth’s magnetosphere. This review starts by introducing the planet Mercury, including its interplanetary environment, magnetosphere, exosphere, and conducting core. The frequent and intense magnetic reconnection on the dayside magnetopause, which is represented by the flux transfer event “shower”, is reviewed on how they depend on magnetosheath plasma β and magnetic shear angle across the magnetopause, following by how it contributes to the flux circulation and magnetosphere-surface-exosphere coupling. In the next, Mercury’s magnetosphere under extreme solar events, including the core induction and the reconnection erosion on the dayside magnetosphere, the responses of the nightside magnetosphere, are reviewed. Then, the dawn-dusk properties of the plasma sheet, including the features of the ions, the structure of the current sheet, and the dynamics of magnetic reconnection, are summarized. The last topic is devoted to the particle energization in Mercury’s magnetosphere, which includes the energization of the Kelvin-Helmholtz waves on the magnetopause boundaries, reconnection-generated magnetic structures, and the cross-tail electric field. In each chapter, the last section discusses the open questions related to each topic, which can be considered by the simulations and the future spacecraft mission. We end this paper by summarizing the future BepiColombo opportunities, which is a joint mission of ESA and JAXA and is en route to Mercury.

Independent evolution of intermediate bill widths in a seabird clade - Juan F. Masello; Peter G. Ryan; Lara D. Shepherd; Petra Quillfeldt; Yves Cherel; Alan J. D. Tennyson; Rachael Alderman; Luciano Calderón; Theresa L. Cole; Richard J. Cuthbert; Ben J. Dilley; Melanie Massaro; et al. (Molecular Genetics and Genomics, 2022)
Interspecific introgression can occur between species that evolve rapidly within an adaptive radiation. Pachyptila petrels differ in bill size and are characterised by incomplete reproductive isolation, leading to interspecific gene flow. Salvin’s prion ( Pachyptila salvini ), whose bill width is intermediate between broad-billed ( P. vittata ) and Antarctic ( P. desolata ) prions, evolved through homoploid hybrid speciation. MacGillivray’s prion ( P. macgillivrayi ), known from a single population on St Paul (Indian Ocean), has a bill width intermediate between salvini and vittata and could also be the product of interspecies introgression or hybrid speciation. Recently, another prion population phenotypically similar to macgillivrayi was discovered on Gough (Atlantic Ocean), where it breeds 3 months later than vittata . The similarity in bill width between the medium-billed birds on Gough and macgillivrayi suggest that they could be closely related. In this study, we used genetic and morphological data to infer the phylogenetic position and evolutionary history of P. macgillivrayi and the Gough medium-billed prion relative other Pachyptila taxa, to determine whether species with medium bill widths evolved through common ancestry or convergence. We found that Gough medium-billed prions belong to the same evolutionary lineage as macgillivrayi , representing a new population of MacGillivray’s prion that originated through a colonisation event from St Paul. We show that macgillivrayi ’s medium bill width evolved through divergence (genetic drift) and independently from that of salvini , which evolved through hybridisation (gene flow). This represents the independent convergence towards a similarly medium-billed phenotype. The newly discovered MacGillivray’s prion population on Gough is of utmost conservation relevance, as the relict macgillivrayi population in the Indian Ocean is very small.

Modelling the effects of cold temperature during the reproductive stage on the yield of chickpea (Cicer arietinum L.) - Muhuddin Rajin Anwar; David J. Luckett; Yashvir S. Chauhan; Ryan H. L. Ip; Lancelot Maphosa; Marja Simpson; Annie Warren; Rosy Raman; Mark F. Richards; Georgina Pengilley; Kristy Hobson; Neroli Graham (International Journal of Biometeorology, 2022)
During the reproductive stage, chilling temperatures and frost reduce the yield of chickpea and limit its adaptation. The adverse effects of chilling temperature and frost in terms of the threshold temperatures, impact of cold duration, and genotype-by-environment-by-management interactions are not well quantified. Crop growth models that predict flowering time and yield under diverse climates can identify combinations of cultivars and sowing time to reduce frost risk in target environments. The Agricultural Production Systems Simulator (APSIM-chickpea) model uses daily temperatures to model basic crop growth but does not include penalties for either frost damage or cold temperatures during flowering and podding stages. Regression analysis overcame this limitation of the model for chickpea crops grown at 95 locations in Australia using 70 years of historic data incorporating three cultivars and three sowing times (early, mid, and late). We modified model parameters to include the effect of soil water on thermal time calculations, which significantly improved the prediction of flowering time. Simulated data, and data from field experiments grown in Australia (2013 to 2019), showed robust predictions for flowering time ( n = 29; R 2 = 0.97), and grain yield ( n = 22; R 2 = 0.63–0.70). In addition, we identified threshold cold temperatures that significantly affected predicted yield, and combinations of locations, variety, and sowing time where the overlap between peak cold temperatures and peak flowering was minimal. Our results showed that frost and/or cold temperature–induced yield losses are a major limitation in some unexpected Australian locations, e.g., inland, subtropical latitudes in Queensland. Intermediate sowing maximise yield, as it avoids cold temperature, late heat, and drought stresses potentially limiting yield in early and late sowing respectively.

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Estimating Facet Joint Apposition with Specimen-Specific Computer Models of Subaxial Cervical Spine Kinematics - Ryan D. Quarrington; Darcy W. Thompson-Bagshaw; Claire F. Jones (Annals of Biomedical Engineering, 2021)

Improving species status assessments under the U.S. Endangered Species Act and implications for multispecies conservation challenges worldwide - Reed F. Noss; Jennifer M. Cartwright; Dwayne Estes; Theo Witsell; Gregg Elliott; Daniel Adams; Matthew Albrecht; Ryan Boyles; Patrick Comer; Chris Doffitt; Don Faber‐Langendoen; JoVonn Hill; et al. (Conservation Biology, 2021)
Despite its successes, the U.S. Endangered Species Act (ESA) has proven challenging to implement due to funding limitations, workload backlog, and other problems. As threats to species survival intensify and as more species come under threat, the need for the ESA and similar conservation laws and policies in other countries to function efficiently has grown. Attempts by the U.S. Fish and Wildlife Service (USFWS) to streamline ESA decisions include multispecies recovery plans and habitat conservation plans. We address species status assessment (SSA), a USFWS process to inform ESA decisions from listing to recovery, within the context of multispecies and ecosystem planning. Although existing SSAs have a single‐species focus, ecosystem‐based research can efficiently inform multiple SSAs within a region and provide a foundation for transition to multispecies SSAs in the future. We considered at‐risk grassland species and ecosystems within the southeastern United States, where a disproportionate number of rare and endemic species are associated with grasslands. To initiate our ecosystem‐based approach, we used a combined literature‐based and structured World Café workshop format to identify science needs for SSAs. Discussions concentrated on 5 categories of threats to grassland species and ecosystems, consistent with recommendations to make shared threats a focus of planning under the ESA: (1) habitat loss, fragmentation, and disruption of functional connectivity; (2) climate change; (3) altered disturbance regimes; (4) invasive species; and (5) localized impacts. For each threat, workshop participants identified science and information needs, including database availability, research priorities, and modeling and mapping needs. Grouping species by habitat and shared threats can make the SSA process and other planning processes for conservation of at‐risk species worldwide more efficient and useful. We found a combination of literature review and structured discussion effective for identifying the scientific information and analysis needed to support the development of multiple SSAs. Article impact statement : Species status assessments can be improved by an ecosystem‐based approach that groups imperiled species by shared habitats and threats.

The origins of marine and non-marine boulder deposits: a brief review - J. F. Dewey; J. Goff; P. D. Ryan (Natural Hazards, 2021)
We identify 14 mechanisms, marine and non-marine, one man made, that result and could result in the formation of boulder deposits after reviewing issues associated with clast shape, size and classification. Four of these mechanisms: storm deposits; waterspouts; cliff collapse; and catastrophic flooding below sea level, may produce deposits stretching for significant distances along shorelines which could be confused with historical or prehistoric tsunami deposits. However, recent debate has more specifically focused on parameters that can be employed in the distinction between coarse-grained tsunami and storm deposits, both of which can occur in the same location. We argue that features such as size, areal distribution and clast shape are not uniquely characteristic of either deposit. Rather, a wide variety of parameters, which reflect the period and the frequency of the transporting waves, need to be taken into account. Such analyses may be aided by profiles which evaluate the variation in modeled flow velocities with distance from the shoreline. Finally, we compare and contrast characteristics of coarse grained tsunami deposits with those of northeast Atlantic storm deposits that may aid in the identification of the transporting wave.

Recessive ciliopathy mutations in primary endocardial fibroelastosis: a rare neonatal cardiomyopathy in a case of Alstrom syndrome - Yan Zhao; Lee-kai Wang; Ascia Eskin; Xuedong Kang; Viviana M. Fajardo; Zubin Mehta; Stacy Pineles; Ryan J. Schmidt; Aaron Nagiel; Gary Satou; Meena Garg; Myke Federman; et al. (Journal of Molecular Medicine, 2021)
Among neonatal cardiomyopathies, primary endocardial fibroelastosis (pEFE) remains a mysterious disease of the endomyocardium that is poorly genetically characterized, affecting 1/5000 live births and accounting for 25% of the entire pediatric dilated cardiomyopathy (DCM) with a devastating course and grave prognosis. To investigate the potential genetic contribution to pEFE, we performed integrative genomic analysis, using whole exome sequencing (WES) and RNA-seq in a female infant with confirmed pathological diagnosis of pEFE. Within regions of homozygosity in the proband genome, WES analysis revealed novel parent-transmitted homozygous mutations affecting three genes with known roles in cilia assembly or function. Among them, a novel homozygous variant [c.1943delA] of uncertain significance in ALMS1 was prioritized for functional genomic and mechanistic analysis. Loss of function mutations of ALMS1 have been implicated in Alstrom syndrome (AS) [OMIM 203800], a rare recessive ciliopathy that has been associated with cardiomyopathy. The variant of interest results in a frameshift introducing a premature stop codon. RNA-seq of the proband’s dermal fibroblasts confirmed the impact of the novel ALMS1 variant on RNA-seq reads and revealed dysregulated cellular signaling and function, including the induction of epithelial mesenchymal transition (EMT) and activation of TGFβ signaling. ALMS1 loss enhanced cellular migration in patient fibroblasts as well as neonatal cardiac fibroblasts, while ALMS1-depleted cardiomyocytes exhibited enhanced proliferation activity. Herein, we present the unique pathological features of pEFE compared to DCM and utilize integrated genomic analysis to elucidate the molecular impact of a novel mutation in ALMS1 gene in an AS case. Our report provides insights into pEFE etiology and suggests, for the first time to our knowledge, ciliopathy as a potential underlying mechanism for this poorly understood and incurable form of neonatal cardiomyopathy. Key message Primary endocardial fibroelastosis (pEFE) is a rare form of neonatal cardiomyopathy that occurs in 1/5000 live births with significant consequences but unknown etiology. Integrated genomics analysis (whole exome sequencing and RNA sequencing) elucidates novel genetic contribution to pEFE etiology. In this case, the cardiac manifestation in Alstrom syndrome is pEFE. To our knowledge, this report provides the first evidence linking ciliopathy to pEFE etiology. Infants with pEFE should be examined for syndromic features of Alstrom syndrome. Our findings lead to a better understanding of the molecular mechanisms of pEFE, paving the way to potential diagnostic and therapeutic applications.

The role of CDHR3 in susceptibility to otitis media - Scott D. Hirsch; Christina L. Elling; Tori C. Bootpetch; Melissa A. Scholes; Lena Hafrén; Sven-Olrik Streubel; Harold S. Pine; Todd M. Wine; Wasyl Szeremeta; Jeremy D. Prager; Elisabet Einarsdottir; Ayesha Yousaf; et al. (Journal of Molecular Medicine, 2021)

From the laboratory to the end-user: a primary packaging study for microneedle patches containing amoxicillin sodium - Emma McAlister; Mary-Carmel Kearney; E. Linzi Martin; Ryan F. Donnelly (Drug Delivery and Translational Research, 2021)
As microneedle (MN) patches progress towards commercialisation, there is a need to address issues surrounding their translation from the laboratory to the end-user. One important aspect of MN patches moving forward is appropriate primary packaging. This research focuses on MN patches containing amoxicillin (AMX) sodium for the potential treatment of neonatal sepsis in hot and humid countries. A MN patch consists of a hydrogel-forming MN array and a drug-containing reservoir. Improper primary packaging in hot and humid countries may result in degradation of active pharmaceutical ingredients, with the use of substandard medicines a major health concern. The research presented here, for the first time, seeks to investigate the integrity of MN patches in different primary packaging when stored under accelerated storage conditions, according to international guidelines. At pre-defined intervals, the performance of the MN patch was investigated. Major causes of drug instability are moisture and temperature. To avoid unnecessary degradation, suitable primary packaging was sought. After 168 days, the percentage of AMX sodium recovered from drug-containing reservoirs packaged in Protect™ 470 foil was 103.51 ± 7.03%. However, packaged in poly(ester) foil, the AMX sodium content decreased significantly ( p = 0.0286), which is likely due to the degradation of AMX sodium by the imbibed moisture. Therefore, convincing evidence was provided as to the importance of investigating the stability of MN patches in primary packaging intended for MN-mediated transdermal delivery so that they are ‘fit for purpose’ when it reaches the end-user. Future work will include qualitative studies to assess MN patch usability. Graphical abstract

Multi-Variate Analyses of Coral Mortality From the 2014–2015 Stony Coral Tissue Loss Disease Outbreak Off Miami-Dade County, Florida - Rachele Spadafore; Ryan Fura; William F. Precht; Steven V. Vollmer (Frontiers in Marine Science, 2021)
Environmental compliance monitoring associated with the Port Miami dredging project (2013–2015), designed to assess the impact of project-generated sediments on the local coral community, fortuitously captured a thermal bleaching event and the first reports of an emergent, highly contagious, white-plague-like coral disease outbreak in the fall of 2014. The disease, now termed stony coral tissue loss disease (SCTLD), has decimated reefs throughout Florida and is now spreading across the Caribbean. The high prevalence of disease, the number of affected species, and the high mortality of corals affected suggests SCTLD may be the most lethal coral disease ever recorded. Previous analyses of the dredge monitoring data have reached mixed conclusions about the relative impact of dredging on coral mortality and has often parsed out disease susceptible individuals to isolate the impacts of dredging only. We use multi-variate analyses, including time-based survival analyses, to examine the timing and impacts of dredging, coral bleaching, and disease on local coral mortality. By examining the status of corals monthly from the October 2013 to July 2015 observational period, we found that coral mortality was not significantly affected by a coral’s proximity to the dredge site or sediment burial. Instead, coral mortality was most strongly impacted by disease and the emergence of SCTLD during the monitoring period. During the 2-year monitoring period, 26.3% of the monitored corals died, but the only conditions significantly affected by the dredge were partial burial and partial mortality. The strongest link to mortality was due to disease, which impacted coral species differently depending on their susceptibility to SCTLD. The focus on disturbances associated with dredging created a circumstance where the greater impacts of this emergent disease were downplayed, leading to a false narrative of the resulting mortality on the local coral communities. The results of this study reveal that while local events such as a dredging project do have quantifiable effects and can be harmful to corals, regional and global threats that result in mass coral mortality such as thermal stress and disease represent an existential threat to coral reefs and must be urgently addressed.

Non-random Co-occurrence of Juvenile White Sharks (Carcharodon carcharias) at Seasonal Aggregation Sites in Southern California - James M. Anderson; Alyssa J. Clevenstine; Brian S. Stirling; Echelle S. Burns; Emily N. Meese; Connor F. White; Ryan K. Logan; John O’Sullivan; Patrick T. Rex; Jack May; Kady Lyons; Chuck Winkler; et al. (Frontiers in Marine Science, 2021)
Many terrestrial and aquatic taxa are known to form periodic aggregations, whether across life history or solely during specific life stages, that are generally governed by the availability and distribution of resources. Associations between individuals during such aggregation events are considered random and not driven by social attraction or underlying community structure. White sharks ( Carcharodon carcharias ) have been described as a species that exhibits resource-driven aggregative behaviors across ontogenetic stages and juvenile white sharks are known to form aggregations at specific nursery sites where individuals may remain for extended periods of time in the presence of other individuals. We hypothesized juvenile white sharks form distinct communities during these critical early phases of ontogeny and discuss how a tendency to co-occur across life stages may be seeded by the formation of these communities in early ontogeny. We present results from a series of social network analyses of 86 juvenile white sharks derived from 6 years of passive acoustic telemetry data in southern California, demonstrating the likelihood of association of tagged juvenile white sharks is greater when sharks are of similar size-classes. Individuals in observed networks exhibited behaviors that best approximated fission-fusion dynamics with spatiotemporally unstable group membership. These results provide evidence of possible non-resource driven co-occurrence and community structure in juvenile white sharks during early life stages.

Tidal Marsh Restoration Optimism in a Changing Climate and Urbanizing Seascape - Nathan J. Waltham; Caitlin Alcott; Myriam A. Barbeau; Just Cebrian; Rod M. Connolly; Linda A. Deegan; Kate Dodds; Lucy A. Goodridge Gaines; Ben L. Gilby; Christopher J. Henderson; Catherine M. McLuckie; Thomas J. Minello; et al. (Estuaries and Coasts, 2021)

Physiological responses to maximal 4 s sprint interval cycling using inertial loading: the influence of inter-sprint recovery duration - Emre Vardarli; Remzi Satiroglu; Jacob R. Allen; Ryan Bjellquist-Ledger; Heath M. Burton; Edward F. Coyle (European Journal of Applied Physiology, 2021)

An agenda for research and action toward diverse and just futures for life on Earth - C. Wyborn; J. Montana; N. Kalas; S. Clement; F. Davila; N. Knowles; E. Louder; M. Balan; J. Chambers; L. Christel; T. Forsyth; G. Henderson; et al. (Conservation Biology, 2021)
Decades of research and policy interventions on biodiversity have insufficiently addressed the dual issues of biodiversity degradation and social justice. New approaches are therefore needed. We devised a research and action agenda that calls for a collective task of revisiting biodiversity toward the goal of sustaining diverse and just futures for life on Earth. Revisiting biodiversity involves critically reflecting on past and present research, policy, and practice concerning biodiversity to inspire creative thinking about the future. The agenda was developed through a 2‐year dialogue process that involved close to 300 experts from diverse disciplines and locations. This process was informed by social science insights that show biodiversity research and action is underpinned by choices about how problems are conceptualized. Recognizing knowledge, action, and ethics as inseparable, we synthesized a set of principles that help navigate the task of revisiting biodiversity. The agenda articulates 4 thematic areas for future research. First, researchers need to revisit biodiversity narratives by challenging conceptualizations that exclude diversity and entrench the separation of humans, cultures, economies, and societies from nature. Second, researchers should focus on the relationships between the Anthropocene, biodiversity, and culture by considering humanity and biodiversity as tied together in specific contexts. Third, researchers should focus on nature and economies by better accounting for the interacting structures of economic and financial systems as core drivers of biodiversity loss. Finally, researchers should enable transformative biodiversity research and action by reconfiguring relationships between human and nonhuman communities in and through science, policy, and practice. Revisiting biodiversity necessitates a renewed focus on dialogue among biodiversity communities and beyond that critically reflects on the past to channel research and action toward fostering just and diverse futures for human and nonhuman life on Earth.

A Role for Extracellular Vesicles in SARS-CoV-2 Therapeutics and Prevention - Jatin Machhi; Farah Shahjin; Srijanee Das; Milankumar Patel; Mai Mohamed Abdelmoaty; Jacob D. Cohen; Preet Amol Singh; Ashish Baldi; Neha Bajwa; Raj Kumar; Lalit K. Vora; Tapan A. Patel; et al. (Journal of Neuroimmune Pharmacology, 2021)

Exploration into the opinions of patients with HIV, healthcare professionals and the lay public of the use of microneedles in clinical practice: highlighting the translational potential for their role in HIV infection - Kurtis Moffatt; Caoimhe Quinn; Paul J. McCague; Ryan F. Donnelly (Drug Delivery and Translational Research, 2021)
Poor adherence to oral antiretroviral therapy (ART) remains an important challenge in the treatment of HIV. Microneedles (MN) potentially could offer a non-invasive long-acting (LA) delivery approach, avoiding the need for daily dosing of ART. However, this claim has yet to be explored amongst its potential end-users. The aim of this mixed methods study was to investigate the perspectives from various end-users surrounding the translation of MN technology to general clinical practice, with a particular focus on delivery of ART. Quantitative postal questionnaires were distributed amongst healthcare professionals (HCPs) and the lay public (LP). A total of 208 responses were obtained (HCP, 69; LP, 139), with a completion rate of 34.7%. The consensus on MN technology was positive from both demographics (HCP, 97.1%; LP, 98.6%), with further strong support of postulated MN use within HIV (HCP, 97.1%; LP, 98.6%). Qualitative focus groups were employed to investigate in-depth, the perspectives of 12 patients with HIV. Again, consensus on MN technology was positive, highlighting benefits pertinent to HIV, including discreet self-application and potential sustained release thus avoiding daily oral ART and associated side effects. Patient concerns focused on the need for varied MN dosing schedules and a reluctance to change from established ART. The findings of this study provide an initial indication of MN acceptability, particularly for use within HIV, from various end-user demographics. Furthermore, concerns raised advocate the importance of continued translational research in this area and should act as motivators for those in MN development to ensure a patient-centred MN product is delivered.

Seal body condition and atmospheric circulation patterns influence polar bear body condition, recruitment, and feeding ecology in the Chukchi Sea - Karyn D. Rode; Eric V. Regehr; Jeffrey F. Bromaghin; Ryan R. Wilson; Michelle St. Martin; Justin A. Crawford; Lori T. Quakenbush (Global Change Biology, 2021)
Polar bears ( Ursus maritimus ) are experiencing loss of sea ice habitats used to access their marine mammal prey. Simultaneously, ocean warming is changing ecosystems that support marine mammal populations. The interactive effects of sea ice and prey are not well understood yet may explain spatial–temporal variation in the response of polar bears to sea ice loss. Here, we examined the potential combined effects of sea ice, seal body condition, and atmospheric circulation patterns on the body condition, recruitment, diet, and feeding probability of 469 polar bears captured in the Chukchi Sea, 2008–2017. The body condition of ringed seals ( Pusa hispida ), the primary prey of females and subadults, was related to dietary proportions of ringed seal, feeding probability, and the body condition of females and cubs. In contrast, adult males consumed more bearded seals ( Erignathus barbatus ) and exhibited better condition when bearded seal body condition was higher. The litter size, number of yearlings per adult female, and the condition of dependent young were higher following winters characterized by low Arctic Oscillation conditions, consistent with a growing number of studies. Body condition, recruitment, and feeding probability were either not associated or negatively associated with sea ice conditions, suggesting that, unlike some subpopulations, Chukchi Sea bears are not currently limited by sea ice availability. However, spring sea ice cover declined 2% per year during our study reaching levels not previously observed in the satellite record and resulting in the loss of polar bear hunting and seal pupping habitat. Our study suggests that the status of ice seal populations is likely an important factor that can either compound or mitigate the response of polar bears to sea ice loss over the short term. In the long term, neither polar bears nor their prey are likely robust to limitless loss of their sea ice habitat.

Relationship Between Metabolic Fitness and Performance in Police Occupational Tasks - Elisa F. D. Canetti; J. Jay Dawes; Phoebe H. Drysdale; Robert Lockie; Charlie Kornhauser; Ryan Holmes; Ben Schram; Robin M. Orr (Journal of Science in Sport and Exercise, 2021)
Purpose To determine the relationship between metabolic fitness test scores and performance in police occupational tasks. Methods Retrospective data from 106 law enforcement officers who completed two metabolic fitness assessments [anaerobic: a 20-m (10-m and 20-m splits) sprint, aerobic: 20 m Multi-Stage Fitness Test (20 m-MSFT)] and three routine occupational tasks [1.22 m Fence jump (FJ), 8.5 m Victim Drag (VD with 102.3 kg) and “Get-up” (GU)] were collected. A Person’s correlation coefficient and a standard multiple regression were used to assess the relationship between and predictive ability of, respectively, the fitness tests scores and performance on occupational tasks. Results There was a significant positive correlation between the 10-m sprint scores and FJ ( r = 0.524, P < 0.001), VD ( r = 0.528, P < 0.001) and GU ( r = 0.486, P < 0.001). Similarly, the 20-m sprint scores were significantly and moderately correlated with FJ ( r = 0.573, P < 0.001), VD ( r = 0.603, P < 0.001) and GU ( r = 0.533, P < 0.001). These anaerobic tests’ scores predicted approximately 40% of the performance in the occupational tasks analysed. The MSFT fitness assessment had a small, albeit significant negative correlation with the three tasks: FJ ( r = − 0.360, P < 0.001), VD ( r = − 0.266, P = 0.012) and GU ( r = − 0.375, P < 0.001). Conclusion High levels of metabolic fitness correlated with faster performance in police officer occupational tasks, particularly ones of an anaerobic nature (i.e. the maximal sprint tests). In addition to typical aerobic fitness conditioning, anaerobic fitness conditioning could be vital for optimal performance in physically demanding tasks required of police officer.

A new primer set for Clade I nosZ that recovers genes from a broader range of taxa - Bangzhou Zhang; C. Ryan Penton; Zhenhua Yu; Chao Xue; Qiongyun Chen; Zhangran Chen; Changsheng Yan; Qiang Zhang; Mengxin Zhao; John F. Quensen; James M. Tiedje (Biology and Fertility of Soils, 2021)

Draft Genome of the Sea Cucumber Holothuria glaberrima, a Model for the Study of Regeneration - Joshua G. Medina-Feliciano; Stacy Pirro; Jose E. García-Arrarás; Vladimir Mashanov; Joseph F. Ryan (Frontiers in Marine Science, 2021)
Regeneration is one of the most fascinating and yet least understood biological processes. Echinoderms, one of the closest related invertebrate groups to humans, can contribute to our understanding of the genetic basis of regenerative processes. Among echinoderms, sea cucumbers have the ability to grow back most of their body parts following injury, including the intestine and nervous tissue. The cellular and molecular events underlying these abilities in sea cucumbers have been most extensively studied in the species Holothuria glaberrima . However, research into the regenerative abilities of this species has been impeded due to the lack of adequate genomic resources. Here, we report the first draft genome assembly of H. glaberrima and demonstrate its value for future genetic studies. Using only short sequencing reads, we assembled the genome into 89,105 scaffolds totaling 1.1 gigabases with an N50 of 25 kilobases. Our BUSCO assessment of the genome resulted in 894 (91.4%) complete and partial genes from 978 genes queried. We incorporated transcriptomic data from several different life history stages to annotate 51,415 genes in our final assembly. To demonstrate the usefulness of the genome, we fully annotated the melanotransferrin ( Mtf) gene family, which have a potential role in the regeneration of the sea cucumber intestine. Using these same data, we extracted the mitochondrial genome, which showed high conservation to that of other holothuroids. Thus, these data will be a critical resource for ongoing studies of regeneration and other studies in sea cucumbers.

Tree‐induced alterations to soil properties and rhizoplane‐associated bacteria following 23 years in a common garden - Caylon F. Yates; Jing Guo; Terrence H. Bell; Suzanne M. Fleishman; Hayden W. Bock; Ryan V. Trexler; David M. Eissenstat; Michela Centinari (Plant and Soil, 2021)

Challenges and opportunities for neuroimaging in young patients with traumatic brain injury: a coordinated effort towards advancing discovery from the ENIGMA pediatric moderate/severe TBI group - Emily L Dennis; Karen Caeyenberghs; Robert F Asarnow; Talin Babikian; Brenda Bartnik-Olson; Erin D Bigler; Anthony Figaji; Christopher C Giza; Naomi J Goodrich-Hunsaker; Cooper B Hodges; Kristen R Hoskinson; Marsh Königs; et al. (Brain Imaging and Behavior, 2021)

Interannual Nearshore Habitat Use of Young of the Year White Sharks Off Southern California - James M. Anderson; Echelle S. Burns; Emily N. Meese; Thomas J. Farrugia; Brian S. Stirling; Connor F. White; Ryan K. Logan; John O’Sullivan; Chuck Winkler; Christopher G. Lowe (Frontiers in Marine Science, 2021)
Young-of-the-year (YOY) and juvenile-stage white sharks may use southern California nearshore beach habitats more extensively than previously known, within meters of some of the most heavily used beaches in the world. Such knowledge forms a critical component of species management and conservation plans, in addition to public safety and risk mitigation planning. We used data derived from a combination of satellite tag locations (13 animals over 3 years) and passive acoustic monitoring (34 animals over 8 years) to examine the occurrence, relative abundance, and residency patterns of YOY white sharks in southern California waters. Our results suggest that southern California contains spatiotemporally dynamic centers of primary nursery habitat. Tagged YOY white sharks formed loose aggregations at “hotspot” locations that were interannually variable, where individuals exhibited temporal fidelity, higher levels of residency, and spatially restricted movements, with multiple YOY individuals simultaneously displaying this behavior. While models of biotic and abiotic variables suggested relative abundance of tagged sharks may be predicted by sea surface temperature, salinity and productivity (chlorophyll-A), these predictors were not consistent across all years of the study. Thus, novel approaches that incorporate technologies to derive high resolution environmental data, paired with more comprehensive telemetry datasets are therefore required to better understand the extrinsic factors that drive habitat selection and residency patterns in juvenile white sharks.

Tsunami Deposits on a Paleoproterozoic Unconformity? The 2.2 Ga Yerrida Marine Transgression on the Northern Margin of the Yilgarn Craton, Western Australia - Desmond F. Lascelles; Ryan J. Lowe (Journal of Marine Science and Engineering, 2021)
Large blocks and boulders of banded iron formations and massive hematite up to 40 × 27 × 6 m3 and in excess of 10,000 metric tonnes were detached from an outcrop of the Wilgie Mia Formation during the ca 2.20 Ga marine transgression at the base of the Paleoproterozoic Windplain Group and deposited in a broad band on the wave-cut surface 900 to 1200 m to the east. At the same time, sand and shingle were scoured from the sea floor, leaving remnants only on the western side of the Wilgie Mia Formation and on the eastern sides of the boulders. Evidence suggesting that the blocks were detached and transported and the sea floor scoured by a tsunami bore with a height of at least 40 m is provided by the following: (1) the deposition of the blocks indicates transportation by a unidirectional sub-horizontal force, whereas the smaller boulders are randomly oriented; (2) 900–1200 m separates the banded iron formation (BIF) outcrop and the blocks (3) there is an absence of the basal conglomerate between the blocks; (4) the blocks and boulders rest directly on the wave-cut surface of deeply weathered amphibolites; (5) the blocks and boulders are surrounded and overlain by fine-grained sandstone of the Windplain Group.

Pantropical variability in tree crown allometry - Grace Jopaul Loubota Panzou; Adeline Fayolle; Tommaso Jucker; Oliver L. Phillips; Stephanie Bohlman; Lindsay F. Banin; Simon L. Lewis; Kofi Affum‐Baffoe; Luciana F. Alves; Cécile Antin; Eric Arets; Luzmila Arroyo; et al. (Global Ecology and Biogeography, 2021)
Aim Tree crowns determine light interception, carbon and water exchange. Thus, understanding the factors causing tree crown allometry to vary at the tree and stand level matters greatly for the development of future vegetation modelling and for the calibration of remote sensing products. Nevertheless, we know little about large‐scale variation and determinants in tropical tree crown allometry. In this study, we explored the continental variation in scaling exponents of site‐specific crown allometry and assessed their relationships with environmental and stand‐level variables in the tropics. Location Global tropics. Time period Early 21st century. Major taxa studied Woody plants. Methods Using a dataset of 87,737 trees distributed among 245 forest and savanna sites across the tropics, we fitted site‐specific allometric relationships between crown dimensions (crown depth, diameter and volume) and stem diameter using power‐law models. Stand‐level and environmental drivers of crown allometric relationships were assessed at pantropical and continental scales. Results The scaling exponents of allometric relationships between stem diameter and crown dimensions were higher in savannas than in forests. We identified that continental crown models were better than pantropical crown models and that continental differences in crown allometric relationships were driven by both stand‐level (wood density) and environmental (precipitation, cation exchange capacity and soil texture) variables for both tropical biomes. For a given diameter, forest trees from Asia and savanna trees from Australia had smaller crown dimensions than trees in Africa and America, with crown volumes for some Asian forest trees being smaller than those of trees in African forests. Main conclusions Our results provide new insight into geographical variability, with large continental differences in tropical tree crown allometry that were driven by stand‐level and environmental variables. They have implications for the assessment of ecosystem function and for the monitoring of woody biomass by remote sensing techniques in the global tropics.

Germline variants discovered in lymphoma patients undergoing tumor profiling: a case series - Anthony J. Scott; Molly C. Tokaz; Michelle F. Jacobs; Arul M. Chinnaiyan; Tycel J. Phillips; Ryan A. Wilcox (Familial Cancer, 2021)

Development of an RTD-Based Flowsheet Modeling Framework for the Assessment of In-Process Control Strategies - Geng Tian; Abdollah Koolivand; Zongyu Gu; Michael Orella; Ryan Shaw; Thomas F. O’Connor (AAPS PharmSciTech, 2021)

Using genomic tools to inform management of the Atlantic northern fulmar - Lila Colston-Nepali; Jennifer F. Provencher; Mark L. Mallory; Ryan P. Franckowiak; Zhengxin Sun; Gregory J. Robertson; Vicki L. Friesen (Conservation Genetics, 2020)

Life history of the river goby Glossogobius callidus ( Teleostei: Gobiidae ) - Lubabalo Mofu; Darragh J. Woodford; Ryan J. Wasserman; Olaf L. F. Weyl (Journal of Fish Biology, 2020)
The river goby Glossogobius callidus is native to freshwater and estuarine habitats in South Africa. Individuals [21.1–144.4 mm total length ( L T )] were sampled from impoundments in the Sundays River Valley, Eastern Cape, from February 2014 to March 2015. The largest female was 137.2 mm L T , and the largest male was 144.4 mm L T . Length‐at‐50% maturity was 75.2 ± 2.1 mm L T for males and 76.2 ± 2.0 mm L T for females. Absolute fecundity was 1028.2 ± 131.7 oocytes per fish, and relative fecundity was 50.1 ± 18.1 oocytes per gram. The spawning season extended from October to December. Fish were aged using sectioned sagittal otoliths. The growth zone periodicity was validated using edge analysis. Longevity was more than 7 years for females and more than 6 years for males. Length‐at‐age was similar for the two sexes and was best described using the von Bertalanffy growth model as L t = 74.7(1 − e –1.0( t + 0.1) ) mm L T for the entire population. Using the population age structure, the mortality rate was estimated at 1.3 per year.

A genoscape‐network model for conservation prioritization in a migratory bird - Kristen C. Ruegg; Ryan J. Harrigan; James F. Saracco; Thomas B. Smith; Caz M. Taylor (Conservation Biology, 2020)
Migratory animals are declining worldwide and coordinated conservation efforts are needed to reverse current trends. We devised a novel genoscape‐network model that combines genetic analyses with species distribution modeling and demographic data to overcome challenges with conceptualizing alternative risk factors in migratory species across their full annual cycle. We applied our method to the long distance, Neotropical migratory bird, Wilson's Warbler ( Cardellina pusilla ). Despite a lack of data from some wintering locations, we demonstrated how the results can be used to help prioritize conservation of breeding and wintering areas. For example, we showed that when genetic, demographic, and network modeling results were considered together it became clear that conservation recommendations will differ depending on whether the goal is to preserve unique genetic lineages or the largest number of birds per unit area. More specifically, if preservation of genetic lineages is the goal, then limited resources should be focused on preserving habitat in the California Sierra, Basin Rockies, or Coastal California, where the 3 most vulnerable genetic lineages breed, or in western Mexico, where 2 of the 3 most vulnerable lineages overwinter. Alternatively, if preservation of the largest number of individuals per unit area is the goal, then limited conservation dollars should be placed in the Pacific Northwest or Central America, where densities are estimated to be the highest. Overall, our results demonstrated the utility of adopting a genetically based network model for integrating multiple types of data across vast geographic scales and better inform conservation decision‐making for migratory animals.

Blunted cardiac output response to exercise in adolescents born preterm - Kristin Haraldsdottir; Andrew M. Watson; David F. Pegelow; Mari Palta; Laura H. Tetri; Taylor Levin; Melissa D. Brix; Ryan M. Centanni; Kara N. Goss; Marlowe M. Eldridge (European Journal of Applied Physiology, 2020)

Interactions among Triatoma sanguisuga blood feeding sources, gut microbiota and Trypanosoma cruzi diversity in southern Louisiana - Eric Dumonteil; Henry Pronovost; Eli F. Bierman; Anna Sanford; Alicia Majeau; Ryan Moore; Claudia Herrera (Molecular Ecology, 2020)
Integrating how biodiversity and infectious disease dynamics are linked at multiple levels and scales is highly challenging. Chagas disease is a vector‐borne disease, with specificities of the triatomine vectors and Trypanosoma cruzi parasite life histories resulting in a complex multihost and multistrain life cycle. Here, we tested the hypothesis that T. cruzi transmission cycles are shaped by triatomine host communities and gut microbiota composition by comparing the integrated interactions of Triatoma sanguisuga in southern Louisiana with feeding hosts, T. cruzi parasite and bacterial microbiota in two habitats. Bugs were collected from resident's houses and animal shelters and analysed for genetic structure, blood feeding sources, T. cruzi parasites, and bacterial diversity by PCR amplification of specific DNA markers followed by next‐generation sequencing, in an integrative metabarcoding approach. T. sanguisuga feeding host communities appeared opportunistic and defined by host abundance in each habitat, yielding distinct parasite transmission networks among hosts. The circulation of a large diversity of T. cruzi DTUs was also detected, with TcII and TcV detected for the first time in triatomines in the US. The bacterial microbiota was highly diverse and varied significantly according to the DTU infecting the bugs, indicating specific interactions among them in the gut. Expanding such studies to multiple habitats and additional triatomine species would be key to further refine our understanding of the complex life cycles of multihost, multistrain parasites such as T. cruzi , and may lead to improved disease control strategies.

Forest responses to simulated elevated CO 2 under alternate hypotheses of size‐ and age‐dependent mortality - Jessica F. Needham; Jeffrey Chambers; Rosie Fisher; Ryan Knox; Charles D. Koven (Global Change Biology, 2020)
Elevated atmospheric carbon dioxide (eCO 2 ) is predicted to increase growth rates of forest trees. The extent to which increased growth translates to changes in biomass is dependent on the turnover time of the carbon, and thus tree mortality rates. Size‐ or age‐dependent mortality combined with increased growth rates could result in either decreased carbon turnover from a speeding up of tree life cycles, or increased biomass from trees reaching larger sizes, respectively. However, most vegetation models currently lack any representation of size‐ or age‐dependent mortality and the effect of eCO 2 on changes in biomass and carbon turnover times is thus a major source of uncertainty in predictions of future vegetation dynamics. Using a reduced‐complexity form of the vegetation demographic model the Functionally Assembled Terrestrial Ecosystem Simulator to simulate an idealised tropical forest, we find increases in biomass despite reductions in carbon turnover time in both size‐ and age‐dependent mortality scenarios in response to a hypothetical eCO 2 ‐driven 25% increase in woody net primary productivity (wNPP). Carbon turnover times decreased by 9.6% in size‐dependent mortality scenarios due to a speeding up of tree life cycles, but also by 2.0% when mortality was age‐dependent, as larger crowns led to increased light competition. Increases in aboveground biomass (AGB) were much larger when mortality was age‐dependent (24.3%) compared with size‐dependent (13.4%) as trees reached larger sizes before death. In simulations with a constant background mortality rate, carbon turnover time decreased by 2.1% and AGB increased by 24.0%, however, absolute values of AGB and carbon turnover were higher than in either size‐ or age‐dependent mortality scenario. The extent to which AGB increases and carbon turnover decreases will thus depend on the mechanisms of large tree mortality: if increased size itself results in elevated mortality rates, then this could reduce by about half the increase in AGB relative to the increase in wNPP.

Two-Photon Polymerisation 3D Printing of Microneedle Array Templates with Versatile Designs: Application in the Development of Polymeric Drug Delivery Systems - Ana Sara Cordeiro; Ismaiel A. Tekko; Mohamed H. Jomaa; Lalitkumar Vora; Emma McAlister; Fabiana Volpe-Zanutto; Matthew Nethery; Paul T. Baine; Neil Mitchell; David W. McNeill; Ryan F. Donnelly (Pharmaceutical Research, 2020)
Purpose To apply a simple and flexible manufacturing technique, two-photon polymerisation (2PP), to the fabrication of microneedle (MN) array templates with high precision and low cost in a short time. Methods Seven different MN array templates were produced by 2PP 3D printing, varying needle height (900–1300 μm), shape (conical, pyramidal, cross-shaped and with pedestal), base width (300–500 μm) and interspacing (100–500 μm). Silicone MN array moulds were fabricated from these templates and used to produce dissolving and hydrogel-forming MN arrays. These polymeric MN arrays were evaluated for their insertion in skin models and their ability to deliver model drugs (cabotegravir sodium and ibuprofen sodium) to viable layers of the skin (ex vivo and in vitro) for subsequent controlled release and/or absorption. Results The various templates obtained with 2PP 3D printing allowed the reproducible fabrication of multiple MN array moulds. The polymeric MN arrays produced were efficiently inserted into two different skin models, with sharp conical and pyramidal needles showing the highest insertion depth values (64–90% of needle height). These results correlated generally with ex vivo and in vitro drug delivery results, where the same designs showed higher drug delivery rates after 24 h of application. Conclusion This work highlights the benefits of using 2PP 3D printing to prototype variable MN array designs in a simple and reproducible manner, for their application in drug delivery.

Comment on the letter of the Society of Vertebrate Paleontology (SVP) dated April 21, 2020 regarding “Fossils from conflict zones and reproducibility of fossil-based scientific data”: the importance of private collections - Carolin Haug; Jelle W. F. Reumer; Joachim T. Haug; Antonio Arillo; Denis Audo; Dany Azar; Viktor Baranov; Rolf Beutel; Sylvain Charbonnier; Rodney Feldmann; Christian Foth; René H. B. Fraaije; et al. (PalZ, 2020)

Body mass and cardiorespiratory fitness are associated with altered brain metabolism - Ryan J. Larsen; Lauren B. Raine; Charles H. Hillman; Arthur F. Kramer; Neal J. Cohen; Aron K. Barbey (Metabolic Brain Disease, 2020)

Coral loss alters guarding and farming behavior of a Caribbean damselfish - Valentina Di Santo; Lois A. O’Boyle; Ryan K. Saylor; Theresa F. Dabruzzi; Marthe A. Covell; Katrina Kaack; Rachel Scharer; Katherine Seger; Nicholas Favazza; Christopher M. Pomory; Wayne A. Bennett (Marine Biology, 2020)
Coral loss is a major element of global ecological change in the oceans that may shape the behavior of keystone species such as habitat-attached animals. Farming damselfishes cultivate and aggressively protect algal garden within their territory, thereby shaping local fish assemblages and macro-algae diversity. Following the widespread loss of live branching coral throughout Florida and the Caribbean Sea, dusky damselfish ( Stegastes adustus ) have modified their territorial behavior. We compared antagonistic behavior, and size and algal species composition of territories of dusky damselfish on dead branching coral rubble and live boulder coral in the Dry Tortugas National Park, USA. Even though similar numbers of “intruders” entered each habitat type, dusky damselfish on rubble territories chased out significantly more fishes, had larger territories and more species of algae were present in their gardens. This study shows that dusky damselfish successfully occupy living and dead coral areas; however, there are potential trade-offs between defending a larger territory and cultivating fewer algal species.

Fitness, independent of physical activity is associated with cerebral blood flow in adults at risk for Alzheimer’s disease - Ryan J. Dougherty; Elizabeth A. Boots; Jacob B. Lindheimer; Aaron J. Stegner; Stephanie Van Riper; Dorothy F. Edwards; Catherine L. Gallagher; Cynthia M. Carlsson; Howard A. Rowley; Barbara B. Bendlin; Sanjay Asthana; Bruce P. Hermann; et al. (Brain Imaging and Behavior, 2020)

Gene-environment regulation of chamber-specific maturation during hypoxemic perinatal circulatory transition - Yan Zhao; Xuedong Kang; Alexander Barsegian; Jian He; Alejandra Guzman; Ryan P. Lau; Reshma Biniwale; Madhuri Wadhra; Brian Reemtsen; Meena Garg; Nancy Halnon; Fabiola Quintero-Rivera; et al. (Journal of Molecular Medicine, 2020)

Microneedle Mediated Transdermal Delivery of Protein, Peptide and Antibody Based Therapeutics: Current Status and Future Considerations - Melissa Kirkby; Aaron R.J. Hutton; Ryan F. Donnelly (Pharmaceutical Research, 2020)
The success of protein, peptide and antibody based therapies is evident - the biopharmaceuticals market is predicted to reach $388 billion by 2024 [1], and more than half of the current top 20 blockbuster drugs are biopharmaceuticals. However, the intrinsic properties of biopharmaceuticals has restricted the routes available for successful drug delivery. While providing 100% bioavailability, the intravenous route is often associated with pain and needle phobia from a patient perspective, which may translate as a reluctance to receive necessary treatment. Several non-invasive strategies have since emerged to overcome these limitations. One such strategy involves the use of microneedles (MNs), which are able to painlessly penetrate the stratum corneum barrier to dramatically increase transdermal drug delivery of numerous drugs. This review reports the wealth of studies that aim to enhance transdermal delivery of biopharmaceutics using MNs. The true potential of MNs as a drug delivery device for biopharmaceuticals will not only rely on acceptance from prescribers, patients and the regulatory authorities, but the ability to upscale MN manufacture in a cost-effective manner and the long term safety of MN application. Thus, the current barriers to clinical translation of MNs, and how these barriers may be overcome are also discussed.

Evaluation of the clinical impact of repeat application of hydrogel-forming microneedle array patches - Rehan Al-Kasasbeh; Aaron J. Brady; Aaron J. Courtenay; Eneko Larrañeta; Maelíosa T.C. McCrudden; Donal O’Kane; Stephen Liggett; Ryan F. Donnelly (Drug Delivery and Translational Research, 2020)
Hydrogel-forming microneedle array patches (MAPs) have been proposed as viable clinical tools for patient monitoring purposes, providing an alternative to traditional methods of sample acquisition, such as venepuncture and intradermal sampling. They are also undergoing investigation in the management of non-melanoma skin cancers. In contrast to drug or vaccine delivery, when only a small number of MAP applications would be required, hydrogel MAPs utilised for sampling purposes or for tumour eradication would necessitate regular, repeat applications. Therefore, the current study was designed to address one of the key translational aspects of MAP development, namely patient safety. We demonstrate, for the first time in human volunteers, that repeat MAP application and wear does not lead to prolonged skin reactions or prolonged disruption of skin barrier function. Importantly, concentrations of specific systemic biomarkers of inflammation (C-reactive protein (CRP); tumour necrosis factor-α (TNF-α)); infection (interleukin-1β (IL-1β); allergy (immunoglobulin E (IgE)) and immunity (immunoglobulin G (IgG)) were all recorded over the course of this fixed study period. No biomarker concentrations above the normal, documented adult ranges were recorded over the course of the study, indicating that no systemic reactions had been initiated in volunteers. Building upon the results of this study, which serve to highlight the safety of our hydrogel MAP, we are actively working towards CE marking of our MAP technology as a medical device.

Historical deposition of trace metals in a marine sapropel from Mangrove Lake, Bermuda with emphasis on mercury, lead, and their isotopic composition - Byunggwon Jeon; Austin Scircle; James V. Cizdziel; Jingjing Chen; Oscar Black; Davin J. Wallace; Ying Zhou; Ryan F. Lepak; James P. Hurley (Journal of Soils and Sediments, 2020)

Walleye growth declines following zebra mussel and Bythotrephes invasion - Gretchen J. A. Hansen; Tyler D. Ahrenstorff; Bethany J. Bethke; Joshua D. Dumke; Jodie Hirsch; Katya E. Kovalenko; Jaime F. LeDuc; Ryan P. Maki; Heidi M. Rantala; Tyler Wagner (Biological Invasions, 2020)
Invasive species represent a threat to aquatic ecosystems globally; however, impacts can be heterogenous across systems. Documented impacts of invasive zebra mussels ( Dreissena polymorpha ) and spiny water fleas ( Bythotrephes cederströmii ; hereafter Bythotrephes ) on native fishes are variable and context dependent across locations and time periods. Here, we use a hierarchical Bayesian analysis of a 35-year dataset on two fish species from 9 lakes to demonstrate that early life growth of ecologically important fishes are influenced by these aquatic invasive species. Walleye ( Sander vitreus ) in their first year of life grew more slowly in the presence of either invader after correcting for temperature (measured by degree days), and were on average 12 or 14% smaller at the end of their first summer following invasion by Bythotrephes or zebra mussels, respectively. Yellow perch ( Perca flavescens ) growth was less affected by invasion. Yellow perch on average grew more slowly in their first year of life following invasion by zebra mussels, although this effect was not statistically distinguishable from zero. Early life growth of both walleye and yellow perch was less tightly coupled to degree days in invaded systems, as demonstrated by increased variance surrounding the degree day-length relationship. Smaller first-year size is related to walleye survival and recruitment to later life stages and has important implications for lake food webs and fisheries management. Future research quantifying effects of zebra mussels and Bythotrephes on other population-level processes and across a wider gradient of lake types is needed to understand the mechanisms driving observed changes in walleye growth.

A chromatogram-simplified Streptomyces albus host for heterologous production of natural products - Asif Fazal; Divya Thankachan; Ellie Harris; Ryan F. Seipke (Antonie van Leeuwenhoek, 2020)
Cloning natural product biosynthetic gene clusters from cultured or uncultured sources and their subsequent expression by genetically tractable heterologous hosts is an essential strategy for the elucidation and characterisation of novel microbial natural products. The availability of suitable expression hosts is a critical aspect of this workflow. In this work, we mutagenised five endogenous biosynthetic gene clusters from Streptomyces albus S4, which reduced the complexity of chemical extracts generated from the strain and eliminated antifungal and antibacterial bioactivity. We showed that the resulting quintuple mutant can express foreign biosynthetic gene clusters by heterologously producing actinorhodin, cinnamycin and prunustatin. We envisage that our strain will be a useful addition to the growing suite of heterologous expression hosts available for exploring microbial secondary metabolism.

Assessing multiple predator, diurnal and search area effects on predatory impacts by ephemeral wetland specialist copepods - Ross N. Cuthbert; Tatenda Dalu; Ryan J. Wasserman; Cristián J. Monaco; Amanda Callaghan; Olaf L. F. Weyl; Jaimie T. A. Dick (Aquatic Ecology, 2020)
Predator–prey interaction strengths can be highly context-dependent. In particular, multiple predator effects (MPEs), variations in predator sex and physical habitat characteristics may affect prey consumption rates and thus the persistence of lower trophic groups. Ephemeral wetlands are transient ecosystems in which predatory copepods can be numerically dominant. We examine the interaction strengths of a specialist copepod Paradiaptomus lamellatus towards mosquito prey in the presence of conspecifics using a functional response approach. Further, we examine sex variability in predation rates of P. lamellatus under circadian and surface area variations. Then, we assess the influence of a co-occurring heterospecific predatory copepod, Lovenula raynerae , on total predation rates. We demonstrate MPEs on consumption, with antagonism between conspecific P. lamellatus predatory units evident, irrespective of prey density. Furthermore, we show differences between sexes in interaction strengths, with female P. lamellatus significantly more voracious than males, irrespective of time of day and experimental arena surface area. Predation rates by P. lamellatus were significantly lower than the heterospecific calanoid copepod L. raynerae , whilst heterospecific copepod groups exhibited the greatest predatory impact. Our results provide insights into the predation dynamics by specialist copepods, wherein species density, diversity and sex affect interaction strengths. In turn, this may influence population-level persistence of lower trophic groups under shifting copepod predator composition.

Sex demographics alter the effect of habitat structure on predation by a temporary pond specialist - Ross N. Cuthbert; Tatenda Dalu; Ryan J. Wasserman; Olaf L. F. Weyl; P. William Froneman; Amanda Callaghan; Jaimie T. A. Dick (Hydrobiologia, 2020)
Habitat structure can profoundly influence interaction strengths between predators and prey. Spatio-temporal habitat structure in temporary wetland ecosystems is particularly variable because of fluctuations in water levels and vegetation colonisation dynamics. Demographic characteristics within animal populations may also alter the influence of habitat structure on biotic interactions, but have remained untested. Here, we investigate the influence of vegetation habitat structure on the consumption of larval mosquito prey by the calanoid copepod Lovenula raynerae , a temporary pond specialist. Increased habitat complexity reduced predation, and gravid female copepods were generally more voracious than male copepods in simplified habitats. However, sexes were more similar as habitat complexity increased. Type II functional responses were exhibited by the copepods irrespective of habitat complexity and sex, owing to consistent high prey acquisition at low prey densities. Attack rates by copepods were relatively unaffected by the complexity gradient, whilst handling times lengthened under more complex environments in gravid female copepods. We demonstrate emergent effects of habitat complexity across species demographics, with predation by males more robust to differences in habitat complexity than females. For ecosystems such as temporary ponds where sex-skewed predator ratios develop, our laboratory findings suggest habitat complexity and sex demographics mediate prey risk.

Klotho gene polymorphism, brain structure and cognition in early-life development - Clarisse F. de Vries; Roger T. Staff; Kimberly G. Noble; Ryan L. Muetzel; Meike W. Vernooij; Tonya White; Gordon D. Waiter; Alison D. Murray (Brain Imaging and Behavior, 2020)

An hypoxia‐tolerant flatfish: consequences of sustained stress on the slender sole Lyopsetta exilis (Pleuronectidae) in the context of a changing ocean - Verena Tunnicliffe; Ryan Gasbarro; Francis Juanes; Jessica Qualley; Nicole Soderberg; Jackson W. F. Chu (Journal of Fish Biology, 2020)
Slender sole Lyopsetta exilis is an abundant groundfish on the continental shelf and inner waters of British Columbia, Canada, where it reaches a maximum standard length of 44 cm. Benthic image surveys coupled with oxygen measurements in Saanich Inlet document a dense population in bottom conditions near anoxia (0.03 ml l −1 oxygen) where diel migrating zooplankton intersect the bottom; we confirm this species is a planktivore, which limits its depth range to the base of the migration layer. In a comparison with slender sole from a nearby well‐oxygenated habitat, several probable effects of living in severe hypoxia emerge: both sexes are significantly smaller in Saanich and the sex ratio is male‐skewed. Otoliths from the Saanich fish were difficult to read due to many checks, but both sexes were smaller at age with the largest female (20 cm) from the hypoxia zone registering 17 years. Hypoxia appears to have a direct consequence on growth despite good food supply in this productive basin. Hyperventilation, a low metabolic rate and a very low critical oxygen tension help this fish regulate oxygen uptake in severely hypoxic conditions; it will be particularly resilient as the incidence of hypoxia increases on the continental shelf. Data from small‐mesh bottom‐trawl surveys over four decades reveal an increase in mean annual catch per unit effort in southern regions of the province, including the outer shelf and the Strait of Georgia. The California Cooperative Oceanic Fisheries Investigations (CalCOFI) ichthyoplankton database records a general decline in fish larvae on the Oregon–California shelf since 1990, but slender sole larvae are increasing there, as they are in the Strait of Georgia. We project that the slender sole will gain relative benefits in the future warming, deoxygenated northeast Pacific Ocean.

BRUVS reveal locally extinct shark and the way for shark monitoring in Brazilian oceanic islands - Caio R. Pimentel; Ryan Andrades; Carlos E. L. Ferreira; Otto B. F. Gadig; Euan S. Harvey; Jean‐Christophe Joyeux; Tommaso Giarrizzo (Journal of Fish Biology, 2020)
Here we present records of sharks obtained using baited remote underwater stereo‐video systems (stereo‐BRUVS) at two Brazilian oceanic islands. Fourteen of the 60 deployments recorded 19 sharks in Trindade Island. In Saint Peter and Saint Paul Archipelago (SPSPA), two pelagic and two demersal deployments recorded two and one shark, respectively, including the locally extinct Galapagos shark Carcharhinus galapagensis . Stereo‐BRUVS should be considered as adjuncts to other non‐invasive methods to monitor shark populations.

The impact of different approaches to exposure assessment on understanding non-malignant respiratory disease risk in taconite miners - Nnaemeka U. Odo; Jeffrey H. Mandel; Bruce H. Alexander; David M. Perlman; Richard F. MacLehose; Gurumurthy Ramachandran; Andrew D. Ryan; Yuan Shao (International Archives of Occupational and Environmental Health, 2020)

Temperature regime drives differential predatory performance in Largemouth Bass and Florida Bass - Dumisani Khosa; Josie South; Ross N. Cuthbert; Ryan J. Wasserman; Olaf L. F. Weyl (Environmental Biology of Fishes, 2020)

Influence of turbulence and in-stream structures on the transport and survival of grass carp eggs and larvae at various developmental stages - Andres F. Prada; Amy E. George; Benjamin H. Stahlschmidt; Patrick Ryan Jackson; Duane C. Chapman; Rafael O. Tinoco (Aquatic Sciences, 2020)
Understanding the response of grass carp to flow and turbulence regimes during early life stages is fundamental to monitoring and controlling their spread. A comprehensive set of hydrodynamic experiments was conducted with live grass carp eggs and larvae, to better understand their drifting and swimming patterns with 3 different in-stream obstructions: (1) a gravel bump, (2) a single cylinder, and (3) submerged vegetation. The hydrodynamic behavior of eggs and larvae with each obstruction was continuously monitored for about 85 consecutive hours. Transient spatial distributions of the locations of eggs and larvae throughout the water column were generated for each flow scenario. Results show that the active swimming capabilities of larvae allow them to seek areas of low turbulence and low shear stresses, and that eggs are susceptible to damage by high levels of turbulence, which was further corroborated with tests in an oscillating grid-stirred turbulence tank. Our study seeks to better inform field collection of grass carp during early life stages, and to guide the design of alternative approaches to control the dispersal of this invasive species in North America.

Microbial communities of the Laurentian Great Lakes reflect connectivity and local biogeochemistry - Sara F. Paver; Ryan J. Newton; Maureen L. Coleman (Environmental Microbiology, 2020)
Summary The Laurentian Great Lakes are a vast, interconnected freshwater system spanning strong physicochemical gradients, thus constituting a powerful natural laboratory for addressing fundamental questions about microbial ecology and evolution. We present a comparative analysis of pelagic microbial communities across all five Laurentian Great Lakes, focusing on Bacterial and Archaeal picoplankton characterized via 16S rRNA amplicon sequencing. We collected samples throughout the water column from the major basins of each lake in spring and summer over 2 years. Two oligotypes, classified as LD12 ( Alphaproteobacteria ) and acI‐B1 ( Actinobacteria ), were among the most abundant in every sample. At the same time, microbial communities showed distinct patterns with depth during summer stratification. Deep hypolimnion samples were frequently dominated by a Chloroflexi oligotype that reached up to 19% relative abundance. Stratified surface communities differed between the colder, less productive upper lakes (Superior, Michigan, Huron) and warmer, more productive lower lakes (Erie, Ontario), in part due to an Actinobacteria oligotype (acI‐C2) that averaged 7.7% of sequences in the lower lakes but

Gene-environment regulatory circuits of right ventricular pathology in tetralogy of fallot - Yan Zhao; Xuedong Kang; Fuying Gao; Alejandra Guzman; Ryan P. Lau; Reshma Biniwale; Madhuri Wadehra; Brian Reemtsen; Meena Garg; Nancy Halnon; Fabiola Quintero-Rivera; Glen Van Arsdell; et al. (Journal of Molecular Medicine, 2019)

Acute exposure to urban air pollution impairs olfactory learning and memory in honeybees - Ryan J. Leonard; Thomas J. Pettit; Peter Irga; Clare McArthur; Dieter F. Hochuli (Ecotoxicology, 2019)

Regional coral disease outbreak overwhelms impacts from a local dredge project - Brooke E. Gintert; William F. Precht; Ryan Fura; Kristian Rogers; Mike Rice; Lindsey L. Precht; Martine D’Alessandro; Jason Croop; Christina Vilmar; Martha L. Robbart (Environmental Monitoring and Assessment, 2019)

Onset kinetics of noise-induced purinergic adaptation of the ‘cochlear amplifier’ - Jennie M. E. Cederholm; Allen F. Ryan; Gary D. Housley (Purinergic Signalling, 2019)

Global Perspectives on Observing Ocean Boundary Current Systems - Robert E. Todd; Francisco P. Chavez; Sophie Clayton; Sophie Cravatte; Marlos Goes; Michelle Graco; Xiaopei Lin; Janet Sprintall; Nathalie V. Zilberman; Matthew Archer; Javier Arístegui; Magdalena Balmaseda; et al. (Frontiers in Marine Science, 2019)

Evaluation of microneedles-assisted in situ depot forming poloxamer gels for sustained transdermal drug delivery - Samiullah Khan; Muhammad Usman Minhas; Ismaiel A. Tekko; Ryan F. Donnelly; Raghu Raj Singh Thakur (Drug Delivery and Translational Research, 2019)

Coral bleaching and recovery from 2016 to 2017 at East and West Flower Garden Banks, Gulf of Mexico - Michelle A. Johnston; Emma L. Hickerson; Marissa F. Nuttall; Raven D. Blakeway; Travis K. Sterne; Ryan J. Eckert; George P. Schmahl (Coral Reefs, 2019)

Consecutive days of exercise decrease insulin response more than a single exercise session in healthy, inactive men - Todd Castleberry; Christopher Irvine; Sarah E. Deemer; Matthew F. Brisebois; Ryan Gordon; Michael D. Oldham; Anthony A. Duplanty; Vic Ben-Ezra (European Journal of Applied Physiology, 2019)

The effects of weather, group size and type of nest on the timing of egg-laying in the Southern Ground-hornbill Bucorvus leadbeateri - Kate F. Carstens; Reshma Kassanjee; Rob M. Little; Peter G. Ryan; Phillip A. R. Hockey (Journal of Ornithology, 2019)

The influence of river discharge and wind on Patos Lagoon, Brazil, Suspended Particulate Matter - Juliana Tavora; Elisa H. L. Fernandes; Andrew C. Thomas; Ryan Weatherbee; Carlos A. F. Schettini (International Journal of Remote Sensing, 2019)

To manage or not? Successful native tree seedling restoration despite a dense, invasive shrub, Berberis thunbergii - Arthur F. Link; Linda M. K. Johnson; Ryan M. Utz (Plant Ecology, 2019)

An evaluation of the current extent and potential spread of Black Bass invasions in South Africa - Dumisani Khosa; Sean M. Marr; Ryan J. Wasserman; Tsungai A. Zengeya; Olaf L. F. Weyl (Biological Invasions, 2019)

Stable carbon isotope analysis on fossil Cedrus pollen shows summer aridification in Morocco during the last 5000 years - Benjamin A. Bell; William J. Fletcher; Henk L. Cornelissen; Jennifer F. E. Campbell; Peter Ryan; Helen Grant; Christoph Zielhofer (Journal of Quaternary Science, 2019)
Quantitative climate reconstructions from pollen typically rely on empirical relationships between pollen abundances or assemblages and climate, such as the modern analogue technique. However, these techniques may be problematic when applied to fossil sequences, as they cannot separate anthropogenic from climatic influence on pollen assemblages. Here, we reconstruct Mid‐ to Late Holocene summer aridity in the Middle Atlas, Morocco, using stable carbon isotope analysis of isolated fossil Cedrus pollen. This approach is based on well‐documented plant physiological responses to moisture stress and is therefore independent of vegetation composition. We find that there has been a general long‐term trend of increasing summer aridity in the region during the last 5000 years to the present day. The gradual decline of Cedrus atlantica forest in the Late Holocene follows this aridity trend. Additionally, we show how isolating a specific pollen type for carbon isotope analysis yields a robust climate signal, versus using pollen concentrates or bulk sediment. Our findings indicate that climate has become drier in the region and confirms the Mid‐ to Late Holocene aridification trend observed more widely in the western Mediterranean, using a novel proxy for this region with good potential for wider application in other environments.

Simulating rewetting events in intermittent rivers and ephemeral streams: A global analysis of leached nutrients and organic matter - Oleksandra Shumilova; Dominik Zak; Thibault Datry; Daniel von Schiller; Roland Corti; Arnaud Foulquier; Biel Obrador; Klement Tockner; Daniel C. Allan; Florian Altermatt; María Isabel Arce; Shai Arnon; et al. (Global Change Biology, 2019)
Climate change and human pressures are changing the global distribution and the extent of intermittent rivers and ephemeral streams (IRES), which comprise half of the global river network area. IRES are characterized by periods of flow cessation, during which channel substrates accumulate and undergo physico‐chemical changes (preconditioning), and periods of flow resumption, when these substrates are rewetted and release pulses of dissolved nutrients and organic matter (OM). However, there are no estimates of the amounts and quality of leached substances, nor is there information on the underlying environmental constraints operating at the global scale. We experimentally simulated, under standard laboratory conditions, rewetting of leaves, riverbed sediments, and epilithic biofilms collected during the dry phase across 205 IRES from five major climate zones. We determined the amounts and qualitative characteristics of the leached nutrients and OM, and estimated their areal fluxes from riverbeds. In addition, we evaluated the variance in leachate characteristics in relation to selected environmental variables and substrate characteristics. We found that sediments, due to their large quantities within riverbeds, contribute most to the overall flux of dissolved substances during rewetting events (56%–98%), and that flux rates distinctly differ among climate zones. Dissolved organic carbon, phenolics, and nitrate contributed most to the areal fluxes. The largest amounts of leached substances were found in the continental climate zone, coinciding with the lowest potential bioavailability of the leached OM. The opposite pattern was found in the arid zone. Environmental variables expected to be modified under climate change (i.e. potential evapotranspiration, aridity, dry period duration, land use) were correlated with the amount of leached substances, with the strongest relationship found for sediments. These results show that the role of IRES should be accounted for in global biogeochemical cycles, especially because prevalence of IRES will increase due to increasing severity of drying events.

Advancing Research for the Management of Long-Lived Species: A Case Study on the Greenland Shark - Jena E. Edwards; Elizabeth Hiltz; Franziska Broell; Peter G. Bushnell; Steven E. Campana; Jørgen S. Christiansen; Brynn M. Devine; Jeffrey J. Gallant; Kevin J. Hedges; M. Aaron MacNeil; Bailey C. McMeans; Julius Nielsen; et al. (Frontiers in Marine Science, 2019)

Heart rate recovery after maximal exercise is impaired in healthy young adults born preterm - Kristin Haraldsdottir; Andrew M. Watson; Arij G. Beshish; Dave F. Pegelow; Mari Palta; Laura H. Tetri; Melissa D. Brix; Ryan M. Centanni; Kara N. Goss; Marlowe W. Eldridge (European Journal of Applied Physiology, 2019)

Future Directions in Conservation Research on Petrels and Shearwaters - Airam Rodríguez; José M. Arcos; Vincent Bretagnolle; Maria P. Dias; Nick D. Holmes; Maite Louzao; Jennifer Provencher; André F. Raine; Francisco Ramírez; Beneharo Rodríguez; Robert A. Ronconi; Rebecca S. Taylor; et al. (Frontiers in Marine Science, 2019)

Cardiac Valve Bioreactor for Physiological Conditioning and Hydrodynamic Performance Assessment - Brandon J. Tefft; Joshua A. Choe; Melissa D. Young; Ryan S. Hennessy; David W. Morse; Jeffery A. Bouchard; Herbert J. Hedberg; Joseph F. Consiglio; Dan Dragomir-Daescu; Robert D. Simari; Amir Lerman (Cardiovascular Engineering and Technology, 2019)

Ocean Data Product Integration Through Innovation-The Next Level of Data Interoperability - Justin J. H. Buck; Scott J. Bainbridge; Eugene F. Burger; Alexandra C. Kraberg; Matthew Casari; Kenneth S. Casey; Louise Darroch; Joaquin Del Rio; Katja Metfies; Eric Delory; Philipp F. Fischer; Thomas Gardner; et al. (Frontiers in Marine Science, 2019)

Understanding the evolving phenotype of vascular complications in telomere biology disorders - Cecilia Higgs; Yanick J. Crow; Denise M. Adams; Emmanuel Chang; Don Hayes; Utz Herbig; James N. Huang; Ryan Himes; Kunal Jajoo; F. Brad Johnson; Susan D. Reynolds; Yoshihiro Yonekawa; et al. (Angiogenesis, 2019)

Late Pleistocene to Holocene paleoenvironmental changes in the NW Black Sea - Andrei Briceag; Anastasia Yanchilina; William B. F. Ryan; Marius Stoica; Mihaela C. Melinte‐Dobrinescu (Journal of Quaternary Science, 2019)
Two gravity cores that penetrated Upper Pleistocene to Upper Holocene sediments in the NW Black Sea have been studied lithologically and microfaunally. The investigations have been coupled with isotopic, calcium carbonate and radiocarbon dating. Six ecological intervals have been distinguished based on changes in microfossil assemblages, giving new insights on the sea‐level and paleoenvironmental changes that took place in the last 25 000 a BP. For the Last Glacial Maximum the ostracod community contains a homogeneous brackish assemblage dominated by Candonidae, suggesting a salinity around 5–8‰. The salinity decrease (to 0.5–5‰) that started concomitantly with the first Meltwater Pulse during Heinrich Stadial 1 is mirrored by increasing diversity and abundance of microfaunal assemblages. This microfaunal increase reached maximum values within the Bølling–Allerød warm period. The shift from Loxoconchidae to Candonidae towards the top of the Younger Dryas suggests a slight increase in salinity. The Preboreal warming period is marked by an abundance increase of ostracod assemblages. During the Late Holocene, stable marine conditions set in, reflected by assemblages similar to those of the present‐day. Based on these data, the first marine influx into the Black Sea before 9390 a BP is assumed.

A sharp floristic discontinuity revealed by the biogeographic regionalization of African savannas - Adeline Fayolle; Michael D. Swaine; Julie Aleman; Akomian F. Azihou; David Bauman; Mariska te Beest; Emmanuel N. Chidumayo; Joris P. G. M. Cromsigt; Hélène Dessard; Manfred Finckh; Francisco Maiato P. Gonçalves; Jean‐Francois Gillet; et al. (Journal of Biogeography, 2019)
Aim In tropical Africa, savannas cover huge areas, have high plant species richness and are considered as a major natural resource for most countries. There is, however, little information available on their floristics and biogeography at the continental scale, despite the importance of such information for our understanding of the drivers of species diversity at various scales and for effective conservation and management. Here, we collated and analysed floristic data from across the continent in order to propose a biogeographical regionalization for African savannas. Location We collated floristic information (specifically woody species lists) for 298 samples of savanna vegetation across Africa, extending from 18° N to 33° S and from 17° W to 48° E. Taxa We focused on native woody species. Methods We used ordination and clustering to identify the floristic discontinuities and gradual transitions across African savannas. Floristic relationships, specificity and turnover, within and between floristic clusters, were analysed using a (dis‐)similarity‐based approach. Results We identified eight floristic clusters across African savannas which in turn were grouped into two larger macro‐units. Ordinations at species and genus levels showed a clear differentiation in woody species composition between the North/West macro‐unit and the South/East macro‐unit. This floristic discontinuity matches to the High (i.e. N&W) and Low (S&E) division of Africa previously proposed by White ( ) and which tracks climatic and topographical variation. In the N&W savannas, the floristic gradient determined by rainfall was partitioned into the Sudanian (drier) and Guinean (wetter) clusters. Within the highly heterogeneous S&E savannas and woodlands, six clusters were identified: Ugandan, Ethiopian, Mozambican, Zambezian, Namibian and South African. Main conclusions The proposed pan‐African classification of savannas and woodlands might assist the development of coordinated management and conservation policies.

Surface Ocean Dispersion Observations From the Ship-Tethered Aerostat Remote Sensing System - Daniel F. Carlson; Tamay Özgökmen; Guillaume Novelli; Cedric Guigand; Henry Chang; Baylor Fox-Kemper; Jean Mensa; Sanchit Mehta; Erick Fredj; Helga Huntley; A. D. Kirwan; Maristella Berta; et al. (Frontiers in Marine Science, 2018)

Separation, banking, and quality control of peripheral blood mononuclear cells from whole blood of melanoma patients - Martha Holland; Rachel Cunningham; Lake Seymour; Katja Kleinsteuber; Amy Cunningham; Tara Patel; Michael Manos; Ryan Brennick; Jun Zhou; F. Stephen Hodi; Mariano Severgnini (Cell and Tissue Banking, 2018)

Glacier protection laws: Potential conflicts in managing glacial hazards and adapting to climate change - Pablo Iribarren Anacona; Josie Kinney; Marius Schaefer; Stephan Harrison; Ryan Wilson; Alexis Segovia; Bruno Mazzorana; Felipe Guerra; David Farías; John M. Reynolds; Neil F. Glasser (Ambio, 2018)

An evaluation of body condition and morphometric relationships within southern California juvenile white sharks Carcharodon carcharias - Ryan K. Logan; Connor F. White; Chuck Winkler; Salvador J. Jorgensen; John B. O'Sullivan; Christopher G. Lowe; Kady Lyons (Journal of Fish Biology, 2018)
Length, mass and girth relationships are presented for 112 juvenile white sharks (JWS) Carcharodon carcharias caught in the Southern California Bight (SCB) nursery area between June 2008 and August 2017. No difference was found between male and female JWS length–mass relationships, but data suggest that JWS in the SCB gain more mass per unit length for the juvenile size classes compared with other C. carcharias populations. Condition‐factor‐to‐liver‐mass and condition‐factor‐to‐liver‐lipid‐content relationships revealed that length and mass ( i.e. , condition factor) can be used as a non‐invasive proxy for body condition for juveniles of this species. The parameters estimated in this study are key information for population assessments of juvenile C. carcharias in the north‐east Pacific Ocean and will contribute to the conservation and management of this IUCN Red List Vulnerable species.

Seeking salt: herbivorous prairie insects can be co‐limited by macronutrients and sodium - Chelse M. Prather; Angela N. Laws; Juan F. Cuellar; Ryan W. Reihart; Kaitlin M. Gawkins; Steven C. Pennings (Ecology Letters, 2018)
The canonical factors typically thought to determine herbivore community structure often explain only a small fraction of the variation in herbivore abundance and diversity. We tested how macronutrients and relatively understudied micronutrients interacted to influence the structure of insect herbivore (orthopteran) communities. We conducted a factorial fertilisation experiment manipulating macronutrients (N and P, added together) and micronutrients (Ca, Na and K) in large plots (30 × 30 m 2 ) in a Texas coastal prairie. Although no single or combination of micronutrients affected herbivore communities in the absence of additional macronutrients, macronutrients and sodium added together increased herbivore abundance by 60%, richness by 15% and diversity by 20%. These results represent the first large‐scale manipulation of single micronutrients and macronutrients in concert, and revealed an herbivore community co‐limited by macronutrients and Na. Our work supports an emerging paradigm that Na may be important in limiting herbivore communities.

Genomes of ubiquitous marine and hypersaline Hydrogenovibrio , Thiomicrorhabdus and Thiomicrospira spp. encode a diversity of mechanisms to sustain chemolithoautotrophy in heterogeneous environments - Kathleen M. Scott; John Williams; Cody M. B. Porter; Sydney Russel; Tara L. Harmer; John H. Paul; Kirsten M. Antonen; Megan K. Bridges; Gary J. Camper; Christie K. Campla; Leila G. Casella; Eva Chase; et al. (Environmental Microbiology, 2018)
Summary Chemolithoautotrophic bacteria from the genera Hydrogenovibrio, Thiomicrorhabdus and Thiomicrospira are common, sometimes dominant, isolates from sulfidic habitats including hydrothermal vents, soda and salt lakes and marine sediments. Their genome sequences confirm their membership in a deeply branching clade of the Gammaproteobacteria . Several adaptations to heterogeneous habitats are apparent. Their genomes include large numbers of genes for sensing and responding to their environment (EAL‐ and GGDEF‐domain proteins and methyl‐accepting chemotaxis proteins) despite their small sizes (2.1–3.1 Mbp). An array of sulfur‐oxidizing complexes are encoded, likely to facilitate these organisms' use of multiple forms of reduced sulfur as electron donors. Hydrogenase genes are present in some taxa, including group 1d and 2b hydrogenases in Hydrogenovibrio marinus and H. thermophilus MA2‐6, acquired via horizontal gene transfer. In addition to high‐affinity cbb 3 cytochrome c oxidase, some also encode cytochrome bd‐ type quinol oxidase or ba 3 ‐ type cytochrome c oxidase, which could facilitate growth under different oxygen tensions, or maintain redox balance. Carboxysome operons are present in most, with genes downstream encoding transporters from four evolutionarily distinct families, which may act with the carboxysomes to form CO 2 concentrating mechanisms. These adaptations to habitat variability likely contribute to the cosmopolitan distribution of these organisms.

Long-term population fluctuations of the exotic New Zealand mudsnail Potamopyrgus antipodarum and its introduced aporocotylid trematode in northwestern France - Claudia Gérard; Maxime Hervé; Ryan F. Hechinger (Hydrobiologia, 2018)

Boundary spanning at the science–policy interface: the practitioners’ perspectives - A. T. Bednarek; C. Wyborn; C. Cvitanovic; R. Meyer; R. M. Colvin; P. F. E. Addison; S. L. Close; K. Curran; M. Farooque; E. Goldman; D. Hart; H. Mannix; et al. (Sustainability Science, 2018)

Ecological genomics predicts climate vulnerability in an endangered southwestern songbird - Kristen Ruegg; Rachael A. Bay; Eric C. Anderson; James F. Saracco; Ryan J. Harrigan; Mary Whitfield; Eben H. Paxton; Thomas B. Smith (Ecology Letters, 2018)
Few regions have been more severely impacted by climate change in the USA than the Desert Southwest. Here, we use ecological genomics to assess the potential for adaptation to rising global temperatures in a widespread songbird, the willow flycatcher ( Empidonax traillii ), and find the endangered desert southwestern subspecies ( E. t. extimus ) most vulnerable to future climate change. Highly significant correlations between present abundance and estimates of genomic vulnerability – the mismatch between current and predicted future genotype–environment relationships – indicate small, fragmented populations of the southwestern willow flycatcher will have to adapt most to keep pace with climate change. Links between climate‐associated genotypes and genes important to thermal tolerance in birds provide a potential mechanism for adaptation to temperature extremes. Our results demonstrate that the incorporation of genotype–environment relationships into landscape‐scale models of climate vulnerability can facilitate more precise predictions of climate impacts and help guide conservation in threatened and endangered groups.

Leveraging model-informed approaches for drug discovery and development in the cardiovascular space - Marissa F. Dockendorf; Ryan C. Vargo; Ferdous Gheyas; Anne S. Y. Chain; Manash S. Chatterjee; Larissa A. Wenning (Journal of Pharmacokinetics and Pharmacodynamics, 2018)

Water guns affect abundance and behavior of bigheaded carp and native fish differently - José M. Rivera; David C. Glover; Patrick M. Kocovsky; James E. Garvey; Mark P. Gaikowski; Nathan R. Jensen; Ryan F. Adams (Biological Invasions, 2018)

In vivo and qualitative studies investigating the translational potential of microneedles for use in the older population - Helen L. Quinn; Carmel M. Hughes; Ryan F. Donnelly (Drug Delivery and Translational Research, 2018)

Mercury isotope constraints on the source for sediment-hosted lead-zinc deposits in the Changdu area, southwestern China - Chunxia Xu; Runsheng Yin; Jiantang Peng; James P. Hurley; Ryan F. Lepak; Jianfeng Gao; Xinbin Feng; Ruizhong Hu; Xianwu Bi (Mineralium Deposita, 2018)

Colonizing tropical seagrasses increase root exudation under fluctuating and continuous low light - Belinda C. Martin; John Statton; Andre R. Siebers; Pauline F. Grierson; Megan H. Ryan; Gary A. Kendrick (Limnology and Oceanography, 2018)
While light availability plays a critical role in seagrass growth and distribution, there is limited understanding of how changes in light exposure impact belowground processes. We investigated the effect of prolonged and fluctuating reductions in light on root growth and exudation by three colonizing seagrasses: Cymodocea serrulata , Halophila ovalis , and Halodule uninervis . Seagrasses were grown in mesocosms under continuous full light (control), under continuous light reduction (medium or low), or under fluctuating light (10 d of low and 4 d of high light, repeated three times). Plants were harvested (1) 6 weeks after light treatments (impact), and (2) after an additional 4 weeks of continuous full light (recovery). Root exudates were collected from trap solutions and measured for dissolved organic carbon (DOC), total dissolved nitrogen (TDN), and dissolved organic matter (DOM) excitation/emission fluorescence spectroscopy. Root biomass decreased in all shading treatments. The most notable impact of light treatment was an increase in root exudation of DOC, protein‐like DOM and humic‐like DOM under fluctuating light for all species. After 4 weeks of recovery, exudation of DOC, and protein‐like DOM observed under fluctuating light returned to the control light levels. However exudation of DOC and protein‐like DOM by H. ovalis grown in continuous low light remained greater than the control, likely due to root death. This study suggests the belowground environment of seagrasses is sensitive to light reduction. Monitoring changes in root exudation of seagrasses can provide an effective and rapid method to assess light stress and short‐term recovery of seagrasses.

Variation in grazing management practices supports diverse butterfly communities across grassland working landscapes - Cayla R. Bendel; Torre J. Hovick; Ryan F. Limb; Jason P. Harmon (Journal of Insect Conservation, 2018)

RETRACTED ARTICLE: Timed Release of Cerebrolysin Using Drug-Loaded Titanate Nanospheres Reduces Brain Pathology and Improves Behavioral Functions in Parkinson’s Disease - Asya Ozkizilcik; Aruna Sharma; Dafin F. Muresanu; José V. Lafuente; Z. Ryan Tian; Ranjana Patnaik; Herbert Mössler; Hari S. Sharma (Molecular Neurobiology, 2018)

Repeated Forced Swim Exacerbates Methamphetamine-Induced Neurotoxicity: Neuroprotective Effects of Nanowired Delivery of 5-HT3-Receptor Antagonist Ondansetron - José Vicente Lafuente; Aruna Sharma; Dafin F. Muresanu; Asya Ozkizilcik; Z. Ryan Tian; Ranjana Patnaik; Hari S. Sharma (Molecular Neurobiology, 2018)

RETRACTED ARTICLE: Cold Environment Exacerbates Brain Pathology and Oxidative Stress Following Traumatic Brain Injuries: Potential Therapeutic Effects of Nanowired Antioxidant Compound H-290/51 - Aruna Sharma; Dafin F Muresanu; José Vicente Lafuente; Per-Ove Sjöquist; Ranjana Patnaik; Z Ryan Tian; Asya Ozkizilcik; Hari S Sharma (Molecular Neurobiology, 2018)

River sediment metal and nutrient variations along an urban–agriculture gradient in an arid austral landscape: implications for environmental health - Tatenda Dalu; Ryan J. Wasserman; Qihang Wu; William P. Froneman; Olaf L. F. Weyl (Environmental Science and Pollution Research, 2018)

No evidence for ecological segregation protecting native trout from invasive hybridization - Ryan P. Kovach; Clint C. Muhlfeld; Robert Al‐Chokhachy; Stephen J. Amish; Jeffrey L. Kershner; Robb F. Leary; Winsor H. Lowe; Gordon Luikart; Phil Matson; David A. Schmetterling; Bradley B. Shepard; Peter A. H. Westley; et al. (Global Change Biology, 2017)

Legacy introductions and climatic variation explain spatiotemporal patterns of invasive hybridization in a native trout - Clint C. Muhlfeld; Ryan P. Kovach; Robert Al‐Chokhachy; Stephen J. Amish; Jeffrey L. Kershner; Robb F. Leary; Winsor H. Lowe; Gordon Luikart; Phil Matson; David A. Schmetterling; Bradley B. Shepard; Peter A. H. Westley; et al. (Global Change Biology, 2017)
Hybridization between invasive and native species, a significant threat to worldwide biodiversity, is predicted to increase due to climate‐induced expansions of invasive species. Long‐term research and monitoring are crucial for understanding the ecological and evolutionary processes that modulate the effects of invasive species. Using a large, multidecade genetics dataset ( N = 582 sites, 12,878 individuals) with high‐resolution climate predictions and extensive stocking records, we evaluate the spatiotemporal dynamics of hybridization between native cutthroat trout and invasive rainbow trout, the world's most widely introduced invasive fish, across the Northern Rocky Mountains of the United States. Historical effects of stocking and contemporary patterns of climatic variation were strongly related to the spread of hybridization across space and time. The probability of occurrence, extent of, and temporal changes in hybridization increased at sites in close proximity to historical stocking locations with greater rainbow trout propagule pressure, warmer water temperatures, and lower spring precipitation. Although locations with warmer water temperatures were more prone to hybridization, cold sites were not protected from invasion; 58% of hybridized sites had cold mean summer water temperatures (

A Dose Ranging Pharmacokinetic Evaluation of IQP-0528 Released from Intravaginal Rings in Non-Human Primates - Jonathan T. Su; Ryan S. Teller; Priya Srinivasan; Jining Zhang; Amy Martin; Samuel Sung; James M. Smith; Patrick F. Kiser (Pharmaceutical Research, 2017)

Characterisation of Peptide5 systemic administration for treating traumatic spinal cord injured rats - Yilin Mao; Tara Nguyen; Ryan S. Tonkin; Justin G. Lees; Caitlyn Warren; Simon J. O’Carroll; Louise F. B. Nicholson; Colin R. Green; Gila Moalem-Taylor; Catherine A. Gorrie (Experimental Brain Research, 2017)

Seabird mortality induced by land‐based artificial lights - Airam Rodríguez; Nick D. Holmes; Peter G. Ryan; Kerry‐Jayne Wilson; Lucie Faulquier; Yovana Murillo; André F. Raine; Jay F. Penniman; Verónica Neves; Beneharo Rodríguez; Juan J. Negro; André Chiaradia; et al. (Conservation Biology, 2017)
Artificial lights at night cause high mortality of seabirds, one of the most endangered groups of birds globally. Fledglings of burrow‐nesting seabirds, and to a lesser extent adults, are attracted to and then grounded (i.e., forced to land) by lights when they fly at night. We reviewed the current state of knowledge of seabird attraction to light to identify information gaps and propose measures to address the problem. Although species in families such as Alcidae and Anatidae can be grounded by artificial light, the most affected seabirds are petrels and shearwaters (Procellariiformes). At least 56 species of Procellariiformes, more than one‐third of them (24) threatened, are subject to grounding by lights. Seabirds grounded by lights have been found worldwide, mainly on oceanic islands but also at some continental locations. Petrel breeding grounds confined to formerly uninhabited islands are particularly at risk from light pollution due to tourism and urban sprawl. Where it is impractical to ban external lights, rescue programs of grounded birds offer the most immediate and employed mitigation to reduce the rate of light‐induced mortality and save thousands of birds every year. These programs also provide useful information for seabird management. However, these data are typically fragmentary, biased, and uncertain and can lead to inaccurate impact estimates and poor understanding of the phenomenon of seabird attraction to lights. We believe the most urgently needed actions to mitigate and understand light‐induced mortality of seabirds are estimation of mortality and effects on populations; determination of threshold light levels and safe distances from light sources; documentation of the fate of rescued birds; improvement of rescue campaigns, particularly in terms of increasing recovery rates and level of care; and research on seabird‐friendly lights to reduce attraction.

The Promoter and Multiple Enhancers of the pou4f3 Gene Regulate Expression in Inner Ear Hair Cells - Masatsugu Masuda; Yan Li; Kwang Pak; Eduardo Chavez; Lina Mullen; Allen F Ryan (Molecular Neurobiology, 2017)

Linking the Abundance of Estuarine Fish and Crustaceans in Nearshore Waters to Shoreline Hardening and Land Cover - Matthew S. Kornis; Denise Breitburg; Richard Balouskus; Donna M. Bilkovic; Lori A. Davias; Steve Giordano; Keira Heggie; Anson H. Hines; John M. Jacobs; Thomas E. Jordan; Ryan S. King; Christopher J. Patrick; et al. (Estuaries and Coasts, 2017)

Changes in Habitat Availability for Multiple Life Stages of Diamondback Terrapins (Malaclemys terrapin) in Chesapeake Bay in Response to Sea Level Rise - Ryan J. Woodland; Christopher L. Rowe; Paula F. P. Henry (Estuaries and Coasts, 2017)

Patterns of divergence across the geographic and genomic landscape of a butterfly hybrid zone associated with a climatic gradient - Sean F. Ryan; Michael C. Fontaine; J. Mark Scriber; Michael E. Pfrender; Shawn T. O'Neil; Jessica J. Hellmann (Molecular Ecology, 2017)
Hybrid zones are a valuable tool for studying the process of speciation and for identifying the genomic regions undergoing divergence and the ecological (extrinsic) and nonecological (intrinsic) factors involved. Here, we explored the genomic and geographic landscape of divergence in a hybrid zone between Papilio glaucus and Papilio canadensis . Using a genome scan of 28,417 dd RAD SNP s, we identified genomic regions under possible selection and examined their distribution in the context of previously identified candidate genes for ecological adaptations. We showed that differentiation was genomewide, including multiple candidate genes for ecological adaptations, particularly those involved in seasonal adaptation and host plant detoxification. The Z chromosome and four autosomes showed a disproportionate amount of differentiation, suggesting genes on these chromosomes play a potential role in reproductive isolation. Cline analyses of significantly differentiated genomic SNP s, and of species‐diagnostic genetic markers, showed a high degree of geographic coincidence (81%) and concordance (80%) and were associated with the geographic distribution of a climate‐mediated developmental threshold (length of the growing season). A relatively large proportion (1.3%) of the outliers for divergent selection were not associated with candidate genes for ecological adaptations and may reflect the presence of previously unrecognized intrinsic barriers between these species. These results suggest that exogenous (climate‐mediated) and endogenous (unknown) clines may have become coupled and act together to reinforce reproductive isolation. This approach of assessing divergence across both the genomic and geographic landscape can provide insight about the interplay between the genetic architecture of reproductive isolation and endogenous and exogenous selection.

Decrease in young-of-the-year yellow perch growth rates following Bythotrephes longimanus invasion - David F. Staples; Ryan P. Maki; Jodie K. Hirsch; W. Charles Kerfoot; Jaime F. LeDuc; Tom Burri; Brenda Moraska Lafrancois; Jay Glase (Biological Invasions, 2017)

Cognitive reserve moderates the relationship between neuropsychological performance and white matter fiber bundle length in healthy older adults - Laurie M. Baker; David H. Laidlaw; Ryan Cabeen; Erbil Akbudak; Thomas E. Conturo; Stephen Correia; David F. Tate; Jodi M. Heaps-Woodruff; Matthew R. Brier; Jacob Bolzenius; Lauren E. Salminen; Elizabeth M. Lane; et al. (Brain Imaging and Behavior, 2017)

Unexpected survival of sharptooth catfish Clarias gariepinus (Burchell 1822) during acute rotenone toxicity trials will complicate management of invasions - Martine S. Jordaan; Tatenda Dalu; Ryan J. Wasserman; Etienne Slabbert; Olaf L. F. Weyl (Biological Invasions, 2017)

Habitat degradation affects the summer activity of polar bears - Jasmine V. Ware; Karyn D. Rode; Jeffrey F. Bromaghin; David C. Douglas; Ryan R. Wilson; Eric V. Regehr; Steven C. Amstrup; George M. Durner; Anthony M. Pagano; Jay Olson; Charles T. Robbins; Heiko T. Jansen (Oecologia, 2017)

Functional responses can unify invasion ecology - Jaimie T. A. Dick; Mhairi E. Alexander; Anthony Ricciardi; Ciaran Laverty; Paul O. Downey; Meng Xu; Jonathan M. Jeschke; Wolf-Christian Saul; Matthew P. Hill; Ryan Wasserman; Daniel Barrios-O’Neill; Olaf L. F. Weyl; et al. (Biological Invasions, 2017)
We contend that invasion ecology requires a universal, measurable trait of species and their interactions with resources that predicts key elements of invasibility and ecological impact; here, we advocate that functional responses can help achieve this across taxonomic and trophic groups, among habitats and contexts, and can hence help unify disparate research interests in invasion ecology.

Fictional responses from Vonesh et al. - Jaimie T. A. Dick; Mhairi E. Alexander; Anthony Ricciardi; Ciaran Laverty; Paul O. Downey; Meng Xu; Jonathan M. Jeschke; Wolf-Christian Saul; Matthew P. Hill; Ryan Wasserman; Daniel Barrios-O’Neill; Olaf L. F. Weyl; et al. (Biological Invasions, 2017)

A global database of nitrogen and phosphorus excretion rates of aquatic animals - Michael J. Vanni; Peter B. McIntyre; Dennis Allen; Diane L. Arnott; Jonathan P. Benstead; David J. Berg; Åge Brabrand; Sébastien Brosse; Paul A. Bukaveckas; Adriano Caliman; Krista A. Capps; Luciana S. Carneiro; et al. (Ecology, 2017)
Animals can be important in modulating ecosystem‐level nutrient cycling, although their importance varies greatly among species and ecosystems. Nutrient cycling rates of individual animals represent valuable data for testing the predictions of important frameworks such as the Metabolic Theory of Ecology ( MTE ) and ecological stoichiometry ( ES ). They also represent an important set of functional traits that may reflect both environmental and phylogenetic influences. Over the past two decades, studies of animal‐mediated nutrient cycling have increased dramatically, especially in aquatic ecosystems. Here we present a global compilation of aquatic animal nutrient excretion rates. The dataset includes 10,534 observations from freshwater and marine animals of N and/or P excretion rates. These observations represent 491 species, including most aquatic phyla. Coverage varies greatly among phyla and other taxonomic levels. The dataset includes information on animal body size, ambient temperature, taxonomic affiliations, and animal body N:P. This data set was used to test predictions of MTE and ES , as described in Vanni and McIntyre (2016; Ecology DOI : 10.1002/ecy.1582 ).

Fine and Coarse-Scale Patterns of Vegetation Diversity on Reclaimed Surface Mine-land Over a 40-Year Chronosequence - Stefanie L. Bohrer; Ryan F. Limb; Aaron L. Daigh; Jay M. Volk; Abbey F. Wick (Environmental Management, 2017)

Erratum to: Visions of Restoration in Fire-Adapted Forest Landscapes: Lessons from the Collaborative Forest Landscape Restoration Program - Lauren S. Urgenson; Clare M. Ryan; Charles B. Halpern; Jonathan D. Bakker; R. Travis Belote; Jerry F. Franklin; Ryan D. Haugo; Cara R. Nelson; Amy E.M. Waltz (Environmental Management, 2017)

Visions of Restoration in Fire-Adapted Forest Landscapes: Lessons from the Collaborative Forest Landscape Restoration Program - Lauren S. Urgenson; Clare M. Ryan; Charles B. Halpern; Jonathan D. Bakker; R. Travis Belote; Jerry F. Franklin; Ryan D. Haugo; Cara R. Nelson; Amy E.M. Waltz (Environmental Management, 2017)

Genetic and Manual Survey Methods Yield Different and Complementary Views of an Ecosystem - Ryan P. Kelly; Collin J. Closek; James L. O'Donnell; James E. Kralj; Andrew O. Shelton; Jameal F. Samhouri (Frontiers in Marine Science, 2017)

A native-range source for a persistent trematode parasite of the exotic New Zealand mudsnail (Potamopyrgus antipodarum) in France - Claudia Gérard; Osamu Miura; Julio Lorda; Thomas H. Cribb; Matthew J. Nolan; Ryan F. Hechinger (Hydrobiologia, 2017)

The Use of a Pressure-Indicating Sensor Film to Provide Feedback upon Hydrogel-Forming Microneedle Array Self-Application In Vivo - Eva M. Vicente-Pérez; Helen L. Quinn; Emma McAlister; Shannon O’Neill; Lezley-Anne Hanna; Johanne G. Barry; Ryan F. Donnelly (Pharmaceutical Research, 2016)

Rapidly dissolving polymeric microneedles for minimally invasive intraocular drug delivery - Raghu Raj Singh Thakur; Ismaiel A. Tekko; Farhan Al-Shammari; Ahlam A. Ali; Helen McCarthy; Ryan F. Donnelly (Drug Delivery and Translational Research, 2016)
In this study, dissolving microneedles (MNs) were used to enhance ocular drug delivery of macromolecules. MNs were fabricated using polyvinylpyrrolidone (PVP) polymer of various molecular weights (MWs) containing three model molecules of increasing MW, namely fluorescein sodium and fluorescein isothiocyanate–dextrans (with MW of 70 k and 150 k Da). Arrays (3 × 3) of PVP MNs with conical shape measuring about 800 μm in height with a 300 μm base diameter, containing the model drugs, were fabricated and characterized for their fracture forces, insertion forces (in the sclera and cornea), depth of penetration (using OCT and confocal imaging), dissolution time and in vitro permeation. The average drug content of the MNs (only in MN shafts) ranged from 0.96 to 9.91 μg, and the average moisture content was below 11 %. High MW PVP produced MNs that can withstand higher forces with minimal reduction in needle height. PVP MNs showed rapid dissolution that ranged from 10 to 180 s, which was dependent upon PVP’s MW. In vitro studies showed significant enhancement of macromolecule permeation when MNs were used, across both the corneal and scleral tissues, in comparison to topically applied aqueous solutions. Confocal images showed that the macromolecules formed depots within the tissues, which led to sustained permeation. However, use of MNs did not significantly benefit the permeation of small molecules; nevertheless, MN application has the potential for drug retention within the selected ocular tissues unlike topical application for small molecules. The material used in the fabrication of the MNs was found to be biocompatible with retinal cells (i.e. ARPE-19). Overall, this study reported the design and fabrication of minimally invasive rapidly dissolving polymeric MN arrays which were able to deliver high MW molecules to the eye via the intrastromal or intrascleral route. Thus, dissolving MNs have potential applications in enhancing ocular delivery of both small and macromolecules.

A trait stacking system via intra-genomic homologous recombination - Sandeep Kumar; Andrew Worden; Stephen Novak; Ryan Lee; Joseph F. Petolino (Planta, 2016)

Zooplankton Are Not Fish: Improving Zooplankton Realism in Size-Spectrum Models Mediates Energy Transfer in Food Webs - Ryan F. Heneghan; Jason D. Everett; Julia L. Blanchard; Anthony J. Richardson (Frontiers in Marine Science, 2016)

Persistence of coral assemblages at East and West Flower Garden Banks, Gulf of Mexico - Michelle A. Johnston; John A. Embesi; Ryan J. Eckert; Marissa F. Nuttall; Emma L. Hickerson; George P. Schmahl (Coral Reefs, 2016)

Temporal stability and rates of post‐depositional change in geochemical signatures of brown trout Salmo trutta scales - D. Ryan; S. Shephard; F. L. Kelly (Journal of Fish Biology, 2016)
This study investigates temporal stability in the scale microchemistry of brown trout Salmo trutta in feeder streams of a large heterogeneous lake catchment and rates of change after migration into the lake. Laser‐ablation inductively coupled plasma mass spectrometry was used to quantify the elemental concentrations of Na, Mg, Mn, Cu, Zn, Ba and Sr in archived (1997–2002) scales of juvenile S. trutta collected from six major feeder streams of Lough Mask, County Mayo, Ireland. Water‐element Ca ratios within these streams were determined for the fish sampling period and for a later period (2013–2015). Salmo trutta scale Sr and Ba concentrations were significantly ( P S. trutta to their stream of origin using a cross‐validated classification model. This model was used to test whether assumed post‐depositional change in scale element concentrations reduced correct natal stream classification of S. trutta in successive years after migration into Lough Mask. Fish residing in the lake for 1–3 years could be reliably classified to their most likely natal stream, but the probability of correct classification diminished strongly with longer lake residence. Use of scale chemistry to identify natal streams of lake S. trutta should focus on recent migrants, but may not require contemporary water chemistry data.

Recreational fisheries data requirements for monitoring catch shares - K. L. Ryan; F. I. Trinnie; R. Jones; A. M. Hart; B. S. Wise (Fisheries Management and Ecology, 2016)
Catch sharing among fishing sectors requires credible data for decision‐making, allocation and management. Integrated Fisheries Management in Western Australia formally allocates allowable catch for Western Rock Lobster ( WRL ) ( Panulirus cygnus ) with 95% commercial and 5% recreational; Roe's abalone ( Haliotis roei ) with 36 t commercial and 40 t recreational; and West Coast Demersal Scalefish ( WCDS ) with 64% commercial and 36% recreational. While commercial catch is obtained from statutory returns, estimates of recreational catches from surveys depend upon spatial and temporal scales of the resource and fishing activity. WRL is a single‐species, licensed recreational fishery operating across large spatial and temporal scales. Mail surveys supplemented with occasional phone‐recall surveys provide cost‐effective monitoring. Roe's abalone is a single‐species, licensed recreational fishery operating over restricted spatial and temporal scales appropriate for aerial‐access surveys. The WCDS recreational fishery targets multiple species across large spatial and temporal scales. The introduction of charter logbooks and a Recreational Fishing from Boat Licence has provided the basis for monitoring charter and private boat‐based recreational fishing. Monitoring allocations is ongoing, with routine surveys required to provide catch estimates with a known confidence. This study highlights the application and importance of surveys in providing timely and accurate data for formal catch sharing.

The role of competition – colonization tradeoffs and spatial heterogeneity in promoting trematode coexistence - Erin A. Mordecai; Alejandra G. Jaramillo; Jacob E. Ashford; Ryan F. Hechinger; Kevin D. Lafferty (Ecology, 2016)
Competition – colonization tradeoffs occur in many systems, and theory predicts that they can strongly promote species coexistence. However, there is little empirical evidence that observed competition‐ colonization tradeoffs are strong enough to maintain diversity in natural systems. This is due in part to a mismatch between theoretical assumptions and biological reality in some systems. We tested whether a competition – colonization tradeoff explains how a diverse trematode guild coexists in California horn snail populations, a system that meets the requisite criteria for the tradeoff to promote coexistence. A field experiment showed that subordinate trematode species tended to have higher colonization rates than dominant species. This tradeoff promoted coexistence in parameterized models but did not fully explain trematode diversity and abundance, suggesting a role of additional diversity maintenance mechanisms. Spatial heterogeneity is an alternative way to promote coexistence if it isolates competing species. We used scale transition theory to expand the competition – colonization tradeoff model to include spatial variation. The parameterized model showed that spatial variation in trematode prevalence did not isolate most species sufficiently to explain the overall high diversity, but could benefit some rare species. Together, the results suggest that several mechanisms combine to maintain diversity, even when a competition – colonization tradeoff occurs.

Seasonal Variability in Stormwater Quality Treatment of Permeable Pavements Situated Over Heavy Clay and in a Cold Climate - Ryan J. Winston; Keely M. Davidson-Bennett; Kristen M. Buccier; William F. Hunt (Water, Air, & Soil Pollution, 2016)

Microneedles: A New Frontier in Nanomedicine Delivery - Eneko Larrañeta; Maelíosa T. C. McCrudden; Aaron J. Courtenay; Ryan F. Donnelly (Pharmaceutical Research, 2016)

Activated Carbon and Biochar Reduce Mercury Methylation Potentials in Aquatic Sediments - Derek D. Bussan; Ryan F. Sessums; James V. Cizdziel (Bulletin of Environmental Contamination and Toxicology, 2016)

Trophic interactions in an austral temperate ephemeral pond inferred using stable isotope analysis - Tatenda Dalu; Olaf L. F. Weyl; P. William Froneman; Ryan J. Wasserman (Hydrobiologia, 2016)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

Properties of ATP-gated ion channels assembled from P2X2 subunits in mouse cochlear Reissner’s membrane epithelial cells - Rachel T. Morton-Jones; Srdjan M. Vlajkovic; Peter R. Thorne; Debra A. Cockayne; Allen F. Ryan; Gary D. Housley (Purinergic Signalling, 2015)

Bryostatin-1 Restores Blood Brain Barrier Integrity following Blast-Induced Traumatic Brain Injury - Brandon P. Lucke-Wold; Aric F. Logsdon; Kelly E. Smith; Ryan C. Turner; Daniel L. Alkon; Zhenjun Tan; Zachary J. Naser; Chelsea M. Knotts; Jason D. Huber; Charles L. Rosen (Molecular Neurobiology, 2015)

Parasite species richness and intensity of interspecific interactions increase with latitude in two wide‐ranging hosts - Mark E. Torchin; Osamu Miura; Ryan F. Hechinger (Ecology, 2015)
Although the latitudinal diversity gradient is a well‐known and general pattern, the mechanisms structuring it remain elusive. Two key issues limit differentiating these. First, habitat type usually varies with latitude, precluding a standardized evaluation of species richness. Second, broad‐scale and local factors hypothesized to shape diversity patterns co‐vary with one another, making it difficult to tease apart independent effects. Examining communities of parasites in widely distributed hosts can eliminate some of these confounding factors. We quantified diversity and interspecific interactions for trematode parasites infecting two similar snail species across 27 degrees of latitude from 43 locations in tropical and temperate oceans. Counter to typical patterns, we found that species richness, levels of parasitism, and intensity of intraguild predation increased with latitude. Because speciation rates are precluded from driving diversity gradients in this particular system, the reversed gradients are likely due to local ecological factors, specifically, increased productivity and stability. We highlight how this system may serve as a useful tool to provide insight into what processes drive diversity gradients in general.

RETRACTED ARTICLE: Sleep Deprivation-Induced Blood-Brain Barrier Breakdown and Brain Dysfunction are Exacerbated by Size-Related Exposure to Ag and Cu Nanoparticles. Neuroprotective Effects of a 5-HT3 Receptor Antagonist Ondansetron - Aruna Sharma; Dafin F. Muresanu; José V. Lafuente; Ranjana Patnaik; Z. Ryan Tian; Anca D. Buzoianu; Hari S. Sharma (Molecular Neurobiology, 2015)

RETRACTED ARTICLE: Nanowired Delivery of Growth Hormone Attenuates Pathophysiology of Spinal Cord Injury and Enhances Insulin-Like Growth Factor-1 Concentration in the Plasma and the Spinal Cord - Dafin F. Muresanu; Aruna Sharma; José V. Lafuente; Ranjana Patnaik; Z. Ryan Tian; Fred Nyberg; Hari S. Sharma (Molecular Neurobiology, 2015)

Microneedles: an innovative platform for gene delivery - Joanne McCaffrey; Ryan F. Donnelly; Helen O. McCarthy (Drug Delivery and Translational Research, 2015)

Microneedle characterisation: the need for universal acceptance criteria and GMP specifications when moving towards commercialisation - Rebecca E. M. Lutton; Jessica Moore; Eneko Larrañeta; Stephen Ligett; A. David Woolfson; Ryan F. Donnelly (Drug Delivery and Translational Research, 2015)

Paediatricians’ opinions of microneedle-mediated monitoring: a key stage in the translation of microneedle technology from laboratory into clinical practice - Karen Mooney; James C. McElnay; Ryan F. Donnelly (Drug Delivery and Translational Research, 2015)

Internal structure of carbonized wheat (Triticum spp.) grains: relationships to kernel texture and ploidy - Ryan M. Szymanski; Craig F. Morris (Vegetation History and Archaeobotany, 2015)

Transcription Factors with Conserved Binding Sites Near ATOH1 on the POU4F3 Gene Enhance the Induction of Cochlear Hair Cells - Ryoukichi Ikeda; Kwang Pak; Eduardo Chavez; Allen F. Ryan (Molecular Neurobiology, 2015)

Neural Cell Adhesion Molecule NrCAM Is Expressed in the Mammalian Inner Ear and Modulates Spiral Ganglion Neurite Outgrowth in an In Vitro Alternate Choice Assay - Yves Brand; Michael Sung; Kwang Pak; Eduardo Chavez; Eric Wei; Vesna Radojevic; Daniel Bodmer; Allen F. Ryan (Journal of Molecular Neuroscience, 2015)

The evolution of phylogeographic data sets - Ryan C. Garrick; Isabel A. S. Bonatelli; Chaz Hyseni; Ariadna Morales; Tara A. Pelletier; Manolo F. Perez; Edwin Rice; Jordan D. Satler; Rebecca E. Symula; Maria Tereza C. Thomé; Bryan C. Carstens (Molecular Ecology, 2015)
Empirical phylogeographic studies have progressively sampled greater numbers of loci over time, in part motivated by theoretical papers showing that estimates of key demographic parameters improve as the number of loci increases. Recently, next‐generation sequencing has been applied to questions about organismal history, with the promise of revolutionizing the field. However, no systematic assessment of how phylogeographic data sets have changed over time with respect to overall size and information content has been performed. Here, we quantify the changing nature of these genetic data sets over the past 20 years, focusing on papers published in Molecular Ecology . We found that the number of independent loci, the total number of alleles sampled and the total number of single nucleotide polymorphisms ( SNP s) per data set has improved over time, with particularly dramatic increases within the past 5 years. Interestingly, uniparentally inherited organellar markers (e.g. animal mitochondrial and plant chloroplast DNA ) continue to represent an important component of phylogeographic data. Single‐species studies (cf. comparative studies) that focus on vertebrates (particularly fish and to some extent, birds) represent the gold standard of phylogeographic data collection. Based on the current trajectory seen in our survey data, forecast modelling indicates that the median number of SNP s per data set for studies published by the end of the year 2016 may approach ~20 000. This survey provides baseline information for understanding the evolution of phylogeographic data sets and underscores the fact that development of analytical methods for handling very large genetic data sets will be critical for facilitating growth of the field.

Considerations in the sterile manufacture of polymeric microneedle arrays - Maelíosa T. C. McCrudden; Ahlam Zaid Alkilani; Aaron J. Courtenay; Cian M. McCrudden; Bronagh McCloskey; Christine Walker; Nida Alshraiedeh; Rebecca E. M. Lutton; Brendan F. Gilmore; A. David Woolfson; Ryan F. Donnelly (Drug Delivery and Translational Research, 2015)

Parasites of Trinidadian guppies: evidence for sex‐ and age‐specific trait‐mediated indirect effects of predators - Jessica F. Stephenson; Cock van Oosterhout; Ryan S. Mohammed; Joanne Cable (Ecology, 2015)
Predation pressure can alter the morphology, physiology, life history, and behavior of prey; each of these in turn can change how surviving prey interact with parasites. These trait‐mediated indirect effects may change in direction or intensity during growth or, in sexually dimorphic species, between the sexes. The Trinidadian guppy, Poecilia reticulata presents a unique opportunity to examine these interactions; its behavioral ecology has been intensively studied in wild populations with well‐characterized predator faunas. Predation pressure is known to have driven the evolution of many guppy traits; for example, in high‐predation sites, females (but not males) tend to shoal, and this anti‐predator behavior facilitates parasite transmission. To test for evidence of predator‐driven differences in infection in natural populations, we collected 4715 guppies from 62 sites across Trinidad between 2003 and 2009 and screened them for ectosymbionts, including Gyrodactylus . A novel model‐averaging analysis revealed that females were more likely to be infected with Gyrodactylus parasites than males, but only in populations with both high predation pressure and high infection prevalence. We propose that the difference in shoaling tendency between the sexes could explain the observed difference in infection prevalence between males and females in high‐predation sites. The infection rate of juveniles did not vary with predation regime, probably because juveniles face constant predation pressure from conspecific adults and therefore tend to shoal in both high‐ and low‐predation sites. This represents the first evidence for age‐ and sex‐specific trait‐mediated indirect effects of predators on the probability of infection in their prey.

Prestin is an anion transporter dispensable for mechanical feedback amplification in Drosophila hearing - Ryan G. Kavlie; Janice L. Fritz; Florian Nies; Martin C. Göpfert; Dominik Oliver; Joerg T. Albert; Daniel F. Eberl (Journal of Comparative Physiology A, 2015)

Operationalizing resilience for adaptive coral reef management under global environmental change - Kenneth R.N. Anthony; Paul A. Marshall; Ameer Abdulla; Roger Beeden; Chris Bergh; Ryan Black; C. Mark Eakin; Edward T. Game; Margaret Gooch; Nicholas A.J. Graham; Alison Green; Scott F. Heron; et al. (Global Change Biology, 2015)
Cumulative pressures from global climate and ocean change combined with multiple regional and local‐scale stressors pose fundamental challenges to coral reef managers worldwide. Understanding how cumulative stressors affect coral reef vulnerability is critical for successful reef conservation now and in the future. In this review, we present the case that strategically managing for increased ecological resilience (capacity for stress resistance and recovery) can reduce coral reef vulnerability (risk of net decline) up to a point. Specifically, we propose an operational framework for identifying effective management levers to enhance resilience and support management decisions that reduce reef vulnerability. Building on a system understanding of biological and ecological processes that drive resilience of coral reefs in different environmental and socio‐economic settings, we present an Adaptive Resilience‐Based management ( ARBM ) framework and suggest a set of guidelines for how and where resilience can be enhanced via management interventions. We argue that press‐type stressors (pollution, sedimentation, overfishing, ocean warming and acidification) are key threats to coral reef resilience by affecting processes underpinning resistance and recovery, while pulse‐type (acute) stressors (e.g. storms, bleaching events, crown‐of‐thorns starfish outbreaks) increase the demand for resilience. We apply the framework to a set of example problems for Caribbean and Indo‐Pacific reefs. A combined strategy of active risk reduction and resilience support is needed, informed by key management objectives, knowledge of reef ecosystem processes and consideration of environmental and social drivers. As climate change and ocean acidification erode the resilience and increase the vulnerability of coral reefs globally, successful adaptive management of coral reefs will become increasingly difficult. Given limited resources, on‐the‐ground solutions are likely to focus increasingly on actions that support resilience at finer spatial scales, and that are tightly linked to ecosystem goods and services.

Pharmacological profile of a 17β-heteroaryl-substituted neuroactive steroid - Derk J. Hogenkamp; Minhtam B. Tran; Ryan F. Yoshimura; Timothy B. Johnstone; Richard Kanner; Kelvin W. Gee (Psychopharmacology, 2014)

Intravaginal Flux Controlled Pump for Sustained Release of Macromolecules - Ryan S. Teller; Rachna Rastogi; Todd J. Johnson; Michael J. Blair; Robert W. Hitchcock; Patrick F. Kiser (Pharmaceutical Research, 2014)

Reduced parasite diversity and abundance in a marine whelk in its expanded geographical range - Julie V. Hopper; Armand M. Kuris; Julio Lorda; Sara E. Simmonds; Crow White; Ryan F. Hechinger (Journal of Biogeography, 2014)
Aim To improve our understanding of how parasitism interacts with geographical range expansions by quantifying diversity and abundance of parasites in 25 populations of a large marine snail, Kellet's whelk ( Kelletia kelletii ), throughout its historical and recently expanded range, which are separated by a well‐known biogeographical boundary. Location California coast (western North America). Methods Parasitological examinations were conducted on 199 whelks from 25 subtidal reefs throughout its expanded and historical ranges. We calculated infection risk, parasite intensity, and parasite species diversity. Abiotic (temperature, latitude, distance from range limit) and biotic (host density) variables were analysed as potential drivers of differential parasitism between expanded‐ and historical‐range populations. Results Compared with historical‐range whelks, expanded‐range whelks were 20% as likely to be infected by parasites, and those that were infected had 6% the number of individual parasites. On average, expanded‐range whelks had 14% the number of parasite species than the historical‐range whelks. The marked decrease in species richness of parasites infecting expanded‐range whelks was only partly explained by the low numbers of parasites. The reduced parasite abundance and diversity in the expanded‐range whelks was not explained by the examined abiotic factors or by whelk density. Main conclusions Expanded‐range populations of Kellet's whelk experience substantially lower parasite abundance and diversity than the historical‐range populations, despite relatively poor demographic performance. The reduced parasitism observed resembles the enemy escape typically characterizing invasive species. A possible explanation for the observed ‘parasite escape’ is that the biogeographical boundary limits the movements or drives the low abundance of other host species (elasmobranchs) required to complete the life cycles of the ‘missing’ parasites. We suggest that parasite escape may generally characterize range‐margin expansions and be important in permitting expansions into what may otherwise be marginal habitats. This parasite escape may directly counter the spread of infectious diseases associated with global warming‐induced range shifts.

Hydrogel-Forming Microneedle Arrays Can Be Effectively Inserted in Skin by Self-Application: A Pilot Study Centred on Pharmacist Intervention and a Patient Information Leaflet - Ryan F. Donnelly; Kurtis Moffatt; Ahlam Zaid Alkilani; Eva M. Vicente-Pérez; Johanne Barry; Maelíosa T. C. McCrudden; A. David Woolfson (Pharmaceutical Research, 2014)

Genome-wide association studies identified novel loci for non-high-density lipoprotein cholesterol and its postprandial lipemic response - Ping An; Robert J. Straka; Toni I. Pollin; Mary F. Feitosa; Mary K. Wojczynski; E. Warwick Daw; Jeffrey R. O’Connell; Quince Gibson; Kathleen A. Ryan; Paul N. Hopkins; Michael Y. Tsai; Chao-Qiang Lai; et al. (Human Genetics, 2014)

Adapting to climate change in South East Queensland, Australia - Ryan R. J. McAllister; Timothy F. Smith; Catherine E. Lovelock; Darryl Low Choy; Andrew J. Ash; Jan McDonald (Regional Environmental Change, 2014)

Cancer risk and genotype–phenotype correlations in PTEN hamartoma tumor syndrome - Marry H. Nieuwenhuis; C. Marleen Kets; Maureen Murphy-Ryan; Helger G. Yntema; D. Gareth Evans; Chrystelle Colas; Pal Møller; Frederik J. Hes; Shirley V. Hodgson; Maran J. W. Olderode-Berends; Stefan Aretz; Karl Heinimann; et al. (Familial Cancer, 2014)

Seasonal reliance on nectar by an insectivorous bat revealed by stable isotopes - Winifred F. Frick; J. Ryan Shipley; Jeffrey F. Kelly; Paul A. Heady; Kathleen M. Kay (Oecologia, 2014)

Relative CO2/NH3 Permeabilities of Human RhAG, RhBG and RhCG - R. Ryan Geyer; Mark D. Parker; Ashley M. Toye; Walter F. Boron; Raif Musa-Aziz (The Journal of Membrane Biology, 2013)

The Threat of Disease Increases as Species Move Toward Extinction - MATTHEW J. HEARD; KATHERINE F. SMITH; KELSEY J. RIPP; MELANIE BERGER; JANE CHEN; JUSTIN DITTMEIER; MAGGIE GOTER; STEPHEN T. MCGARVEY; ELIZABETH RYAN (Conservation Biology, 2013)
At local scales, infectious disease is a common driver of population declines, but globally it is an infrequent contributor to species extinction and endangerment. For species at risk of extinction from disease important questions remain unanswered, including when does disease become a threat to species and does it co‐occur, predictably, with other threats? Using newly compiled data from the International Union for Conservation of Nature (IUCN) Red List, we examined the relative role and co‐occurrence of threats associated with amphibians, birds, and mammals at 6 levels of extinction risk (i.e., Red List status categories: least concern, near threatened, vulnerable, endangered, critically endangered, and extinct in the wild/extinct). We tested the null hypothesis that the proportion of species threatened by disease is the same in all 6 Red List status categories. Our approach revealed a new method for determining when disease most frequently threatens species at risk of extinction. The proportion of species threatened by disease varied significantly between IUCN status categories and linearly increased for amphibians, birds, and all species combined as these taxa move from move from least concern to critically endangered. Disease was infrequently the single contributing threat. However, when a species was negatively affected by a major threat other than disease (e.g., invasive species, land‐use change) that species was more likely to be simultaneously threatened by disease than species that had no other threats. Potential drivers of these trends include ecological factors, clustering of phylogenetically related species in Red List status categories, discovery bias among species at greater risk of extinction, and availability of data. We echo earlier calls for baseline data on the presence of parasites and pathogens in species when they show the first signs of extinction risk and arguably before. La Amenaza de Enfermedades Incrementa a Medida que las Especies se Aproximan a la Extinción

Neural Cell Adhesion Molecule L1 Modulates Type I But Not Type II Inner Ear Spiral Ganglion Neurite Outgrowth in an In Vitro Alternate Choice Assay - Yves Brand; Michael Sung; Eduardo Chavez; Eric Wei; Kwang K. Pak; Gary D. Housley; Daniel Bodmer; Allen F. Ryan (Journal of Molecular Neuroscience, 2013)

Novel statistical methods for integrating genetic and stable isotope data to infer individual‐level migratory connectivity - Colin W. Rundel; Michael B. Wunder; Allison H. Alvarado; Kristen C. Ruegg; Ryan Harrigan; Andrew Schuh; Jeffrey F. Kelly; Rodney B. Siegel; David F. DeSante; Thomas B. Smith; John Novembre (Molecular Ecology, 2013)
Methods for determining patterns of migratory connectivity in animal ecology have historically been limited due to logistical challenges. Recent progress in studying migratory bird connectivity has been made using genetic and stable‐isotope markers to assign migratory individuals to their breeding grounds. Here, we present a novel B ayesian approach to jointly leverage genetic and isotopic markers and we test its utility on two migratory passerine bird species. Our approach represents a principled model‐based combination of genetic and isotope data from samples collected on the breeding grounds and is able to achieve levels of assignment accuracy that exceed those of either method alone. When applied at large scale the method can reveal specific migratory connectivity patterns. In W ilson's warblers ( W ilsonia pusilla ), we detect a subgroup of birds wintering in B aja that uniquely migrate preferentially from the coastal P acific N orthwest. Our approach is implemented in a way that is easily extended to accommodate additional sources of information (e.g. bi‐allelic markers, species distribution models, etc.) or adapted to other species or assignment problems.

Experimental study on the effects of temperature cycling on coarsening of plagioclase and olivine in an alkali basalt - Ryan D. Mills; Allen F. Glazner (Contributions to Mineralogy and Petrology, 2013)

Ecological coassociations influence species' responses to past climatic change: an example from a S onoran D esert bark beetle - Ryan C. Garrick; John D. Nason; Juan F. Fernández‐Manjarrés; Rodney J. Dyer (Molecular Ecology, 2013)
Ecologically interacting species may have phylogeographical histories that are shaped both by features of their abiotic landscape and by biotic constraints imposed by their coassociation. The B aja C alifornia peninsula provides an excellent opportunity to examine the influence of abiotic vs. biotic factors on patterns of diversity in plant‐insect species. This is because past climatic and geological changes impacted the genetic structure of plants quite differently to that of codistributed free‐living animals (e.g. herpetofauna and small mammals). Thus, ‘plant‐like’ patterns should be discernible in host‐specific insect herbivores. Here, we investigate the population history of a monophagous bark beetle, A raptus attenuatus , and consider drivers of phylogeographical patterns in the light of previous work on its host plant, E uphorbia lomelii . Using a combination of phylogenetic, coalescent‐simulation‐based and exploratory analyses of mitochondrial DNA sequences and nuclear genotypic data, we found that the evolutionary history of A . attenuatus exhibits similarities to its host plant that are attributable to both biotic and abiotic processes. Southward range expansion and recent colonization of continental S onora from the B aja peninsula appear to be unique to this taxon pair and probably reflect influences of the host plant. On the other hand, abiotic factors with landscape‐level influences on a diverse suite of codistributed arid‐adapted taxa, such as P lio‐ and P leistocene‐aged marine incursions in the region, also left genetic signatures in beetle and host plant populations. Superimposed on these similarities, bark beetle‐specific patterns and processes were also evident: our data revealed two secondarily sympatric, reproductively isolated genetic lineages, as well as a previously unrecognized mid‐peninsular warm desert refuge. Taken together, this work illustrates that the evolutionary history of species‐specific insect herbivores may represent a mosaic of influences, including—but not limited to—those imposed by the host plant.

Assessment of exposure to outdoor BTEX concentrations on the Saint Regis Mohawk Tribe reservation at Akwesasne New York State - Sheila Kalenge; Ryan F. Lebouf; Philip K. Hopke; Alan Rossner; Angela Benedict-Dunn (Air Quality, Atmosphere & Health, 2013)

Developmental changes in the responsiveness of rat spiral ganglion neurons to neurotrophic factors in dissociated culture: differential responses for survival, neuritogenesis and neuronal morphology - Yulian Jin; Kenji Kondo; Munetaka Ushio; Kimitaka Kaga; Allen F. Ryan; Tatsuya Yamasoba (Cell and Tissue Research, 2013)

Development of the ear, hearing capabilities and laterophysic connection in the spotfin butterflyfish (Chaetodon ocellatus) - Jacqueline F. Webb; Ryan M. Walsh; Brandon M. Casper; David A. Mann; Natasha Kelly; Nicole Cicchino (Environmental Biology of Fishes, 2012)

Stress State and Strain Rate Dependence of the Human Placenta - Benjamin C. Weed; Ali Borazjani; Sourav S. Patnaik; R. Prabhu; M. F. Horstemeyer; Peter L. Ryan; Thomas Franz; Lakiesha N. Williams; Jun Liao (Annals of Biomedical Engineering, 2012)

A hard-knock life: the foraging ecology of Cape cormorants amidst shifting prey resources and industrial fishing pressure - MH Hamann; D Grémillet; PG Ryan; F Bonadonna; CD van der Lingen; L Pichegru (African Journal of Marine Science, 2012)

Erratum to: Multiple Scales of Influence on Wetland Vegetation Associated with Headwater Streams in Alaska, USA - Dennis F. Whingham; Coowe M. Walker; Ryan S. King; Steven J. Baird (Wetlands, 2012)

Multiple Scales of Influence on Wetland Vegetation Associated with Headwater Streams in Alaska, USA - Dennis F. Whigham; Coowe M. Walker; Ryan S. King; Steven J. Baird (Wetlands, 2012)

Molecular sexing of tigers, Panthera tigris - R. McEwing; K. Ouitavon; J. J. Rovie-Ryan; Wulansari; F. T. Sitam; R. Ogden (Conservation Genetics Resources, 2012)

Landscape and Wetland Influences on Headwater Stream Chemistry in the Kenai Lowlands, Alaska - Coowe M. Walker; Ryan S. King; Dennis F. Whigham; Steven J. Baird (Wetlands, 2012)

Obesity and knee osteoarthritis - Ryan Lee; Walter F. Kean (Inflammopharmacology, 2012)

A mathematical model of the commercial harvest of Palmaria palmata (Palmariales, Rhodophyta) on Digby Neck, Nova Scotia, Canada - Ryan J. Lukeman; Leah F. Beveridge; Andrea D. Flynn; David J. Garbary (Algae, 2012)

Fine mapping of 14q24.1 breast cancer susceptibility locus - Phoebe Lee; Yi-Ping Fu; Jonine D. Figueroa; Ludmila Prokunina-Olsson; Jesus Gonzalez-Bosquet; Peter Kraft; Zhaoming Wang; Kevin B. Jacobs; Meredith Yeager; Marie-Josèphe Horner; Susan E. Hankinson; Amy Hutchinson; et al. (Human Genetics, 2012)

An experimental test and models of drift and dispersal processes of pallid sturgeon (Scaphirhynchus albus) free embryos in the Missouri River - Patrick J. Braaten; David B. Fuller; Ryan D. Lott; Michael P. Ruggles; Tyrel F. Brandt; Robert G. Legare; Robert J. Holm (Environmental Biology of Fishes, 2012)

Fungus-growing Allomerus ants are associated with antibiotic-producing actinobacteria - Ryan F. Seipke; Jörg Barke; Mario X. Ruiz-Gonzalez; Jérôme Orivel; Douglas W. Yu; Matthew I. Hutchings (Antonie van Leeuwenhoek, 2012)

Plant and microbial strategies to improve the phosphorus efficiency of agriculture - Alan E. Richardson; Jonathan P. Lynch; Peter R. Ryan; Emmanuel Delhaize; F. Andrew Smith; Sally E. Smith; Paul R. Harvey; Megan H. Ryan; Erik J. Veneklaas; Hans Lambers; Astrid Oberson; Richard A. Culvenor; et al. (Plant and Soil, 2011)

Strategies and agronomic interventions to improve the phosphorus-use efficiency of farming systems - Richard J. Simpson; Astrid Oberson; Richard A. Culvenor; Megan H. Ryan; Erik J. Veneklaas; Hans Lambers; Jonathan P. Lynch; Peter R. Ryan; Emmanuel Delhaize; F. Andrew Smith; Sally E. Smith; Paul R. Harvey; et al. (Plant and Soil, 2011)

Localizing sadness activation within the subgenual cingulate in individuals: a novel functional MRI paradigm for detecting individual differences in the neural circuitry underlying depression - Ryan Smith; Richard A. Fadok; Michael Purcell; Seban Liu; Cynthia Stonnington; Robert F. Spetzler; Leslie C. Baxter (Brain Imaging and Behavior, 2011)

Multi-Decadal Changes in Tundra Environments and Ecosystems: Synthesis of the International Polar Year-Back to the Future Project (IPY-BTF) - Terry V. Callaghan; Craig E. Tweedie; Jonas Åkerman; Christopher Andrews; Johan Bergstedt; Malcolm G. Butler; Torben R. Christensen; Dorothy Cooley; Ulrika Dahlberg; Ryan K. Danby; Fred J. A. Daniёls; Johannes G. de Molenaar; et al. (Ambio, 2011)

Laser-Engineered Dissolving Microneedle Arrays for Transdermal Macromolecular Drug Delivery - Katarzyna Migalska; Desmond I. J. Morrow; Martin J. Garland; Raj Thakur; A. David Woolfson; Ryan F. Donnelly (Pharmaceutical Research, 2011)

Proteome changes in the initial bacterial colonist during ecological succession in an acid mine drainage biofilm community - Ryan S. Mueller; Brian D. Dill; Chongle Pan; Christopher P. Belnap; Brian C. Thomas; Nathan C. VerBerkmoes; Robert L. Hettich; Jillian F. Banfield (Environmental Microbiology, 2011)
Summary Proteomes of acid mine drainage biofilms at different stages of ecological succession were examined to understand microbial responses to changing community membership. We evaluated the degree of reproducibility of the community proteomes between samples of the same growth stage and found stable and predictable protein abundance patterns across time and sampling space, allowing for a set of 50 classifier proteins to be identified for use in predicting growth stages of undefined communities. Additionally, physiological changes in the dominant species, Leptospirillum Group II, were analysed as biofilms mature. During early growth stages, this population responds to abiotic stresses related to growth on the acid mine drainage solution. Enzymes involved in protein synthesis, cell division and utilization of 1‐ and 2‐carbon compounds were more abundant in early growth stages, suggesting rapid growth and a reorganization of metabolism during biofilm initiation. As biofilms thicken and diversify, external stresses arise from competition for dwindling resources, which may inhibit cell division of Leptospirillum Group II through the SOS response. This population also represses translation and synthesizes more complex carbohydrates and amino acids in mature biofilms. These findings provide unprecedented insight into the physiological changes that may result from competitive interactions within communities in natural environments.

Brominated flame retardants in Canadian chicken egg yolks - D.F.K. Rawn; A. Sadler; S.C. Quade; W.-F. Sun; B.P.-Y. Lau; I. Kosarac; S. Hayward; J.J. Ryan (Food Additives & Contaminants: Part A, 2011)

The effect of nicotine and trauma context on acoustic startle in smokers with and without posttraumatic stress disorder - Patrick S. Calhoun; H. Ryan Wagner; F. Joseph McClernon; Sherman Lee; Michelle F. Dennis; Scott R. Vrana; Carolina P. Clancy; Claire F. Collie; Yashika C. Johnson; Jean C. Beckham (Psychopharmacology, 2011)

Calpain Plays a Central Role in 1-Methyl-4-phenylpyridinium (MPP(+))-Induced Neurotoxicity in Cerebellar Granule Neurons - Richard A. Harbison; Kristen R. Ryan; Heather M. Wilkins; Emily K. Schroeder; F. Alexandra Loucks; Ron J. Bouchard; Daniel A. Linseman (Neurotoxicity Research, 2011)

Design, Optimization and Characterisation of Polymeric Microneedle Arrays Prepared by a Novel Laser-Based Micromoulding Technique - Ryan F. Donnelly; Rita Majithiya; Thakur Raghu Raj Singh; Desmond I. J. Morrow; Martin J. Garland; Yusuf K. Demir; Katarzyna Migalska; Elizabeth Ryan; David Gillen; Christopher J. Scott; A. David Woolfson (Pharmaceutical Research, 2011)

Efficacy of caspofungin as salvage therapy for invasive aspergillosis compared to standard therapy in a historical cohort - J. W. Hiemenz; I. I. Raad; J. A. Maertens; R. Y. Hachem; A. J. Saah; C. A. Sable; J. A. Chodakewitz; M. E. Severino; P. Saddier; R. S. Berman; D. M. Ryan; M. J. DiNubile; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2010)

Restoring biopedturbation in grasslands with anthropogenic focal disturbance - Ryan F. Limb; David M. Engle; Terrence G. Bidwell; Donald P. Althoff; Alan B. Anderson; Philip S. Gipson; Heidi R. Howard (Plant Ecology, 2010)

Microneedle Pre-treatment of Human Skin Improves 5-Aminolevulininc Acid (ALA)- and 5-Aminolevulinic Acid Methyl Ester (MAL)-Induced PpIX Production for Topical Photodynamic Therapy Without Increase in Pain or Erythema - Patrycja Mikolajewska; Ryan F. Donnelly; Martin J. Garland; Desmond I. J. Morrow; Thakur Raghu Raj Singh; Vladimir Iani; Johan Moan; Asta Juzeniene (Pharmaceutical Research, 2010)

Height is more important than light in determining leaf morphology in a tropical forest - Molly A. Cavaleri; Steven F. Oberbauer; David B. Clark; Deborah A. Clark; Michael G. Ryan (Ecology, 2010)
Both within and between species, leaf physiological parameters are strongly related to leaf dry mass per area (LMA, g/m 2 ), which has been found to increase from forest floor to canopy top in every forest where it has been measured. Although vertical LMA gradients in forests have historically been attributed to a direct phenotypic response to light, an increasing number of recent studies have provided evidence that water limitation in the upper canopy can constrain foliar morphological adaptations to higher light levels. We measured height, light, and LMA of all species encountered along 45 vertical canopy transects across a Costa Rican tropical rain forest. LMA was correlated with light levels in the lower canopy until approximately 18 m sample height and 22% diffuse transmittance. Height showed a remarkably linear relationship with LMA throughout the entire vertical canopy profile for all species pooled and for each functional group individually (except epiphytes), possibly through the influence of gravity on leaf water potential and turgor pressure. Models of forest function may be greatly simplified by estimating LMA‐correlated leaf physiological parameters solely from foliage height profiles, which in turn can be assessed with satellite‐ and aircraft‐based remote sensing.

Variation of Mo isotopes from molybdenite in high-temperature hydrothermal ore deposits - Ryan Mathur; S. Brantley; A. Anbar; F. Munizaga; V. Maksaev; R. Newberry; J. Vervoort; G. Hart (Mineralium Deposita, 2010)

Late-summer phytoplankton in western Lake Erie (Laurentian Great Lakes): bloom distributions, toxicity, and environmental influences - David F. Millie; Gary L. Fahnenstiel; Julianne Dyble Bressie; Ryan J. Pigg; Richard R. Rediske; David M. Klarer; Patricia A. Tester; R. Wayne Litaker (Aquatic Ecology, 2009)

Microneedle Arrays Allow Lower Microbial Penetration Than Hypodermic Needles In Vitro - Ryan F. Donnelly; Thakur Raghu Raj Singh; Michael M. Tunney; Desmond I. J. Morrow; Paul A. McCarron; Conor O’Mahony; A. David Woolfson (Pharmaceutical Research, 2009)

Estimating habitat selection when GPS fix success is less than 100% - Ryan M. Nielson; Bryan F. J. Manly; Lyman L. McDonald; Hall Sawyer; Trent L. McDonald (Ecology, 2009)
Inferences about habitat selection by animals derived from sequences of relocations obtained with global positioning system (GPS) collars can be influenced by GPS fix success. Environmental factors such as dense canopy cover or rugged terrain can reduce GPS fix success, making subsequent modeling problematic if fix success depends on the selected habitat. Ignoring failed fix attempts may affect estimates of model coefficients and lead to incorrect conclusions about habitat selection. Here, we present a habitat selection model that accounts for missing locations due to habitat‐induced data losses, called a resource selection function (RSF) for GPS fix success. The model's formulation is similar to adjusting estimates of probability of occupancy when detection is less than 100% in patch occupancy sampling. We demonstrate use of the model with GPS data collected from an adult female mule deer ( Odocoileus hemionus ) and discuss how to analyze data from multiple animals. In the simulations presented, our habitat selection model was generally unbiased for GPS data sets missing up to 50% of the locations.

Late Pleistocene to Holocene sedimentation and hydrocarbon seeps on the continental shelf of a steep, tectonically active margin, southern California, USA - Amy E. Draut; Patrick E. Hart; Thomas D. Lorenson; Holly F. Ryan; Florence L. Wong; Ray W. Sliter; James E. Conrad (Marine Geophysical Research, 2009)

How large is the hand in the puppet? Ecological and evolutionary factors affecting body mass of 15 trematode parasitic castrators in their snail host - Ryan F. Hechinger; Kevin D. Lafferty; Frank T. Mancini; Robert R. Warner; Armand M. Kuris (Evolutionary Ecology, 2009)

Compliance with physical activity guidelines in a group of UK-based postal workers using an objective monitoring technique - Sebastien F. M. Chastin; Philippa M. Dall; William W. Tigbe; Margaret P. Grant; Cormac G. Ryan; Danny Rafferty; Malcolm H. Granat (European Journal of Applied Physiology, 2009)

Scale of pluton/wall rock interaction near May Lake, Yosemite National Park, CA, USA - Ryan D. Mills; Allen F. Glazner; Drew S. Coleman (Contributions to Mineralogy and Petrology, 2009)

Coastal swimming patterns of white sharks (Carcharodon carcharias) at Mossel Bay, South Africa - Ryan Johnson; Marthán N. Bester; Sheldon F. J. Dudley; W. Herman Oosthuizen; Michael Meÿer; Lisa Hancke; Enrico Gennari (Environmental Biology of Fishes, 2009)

Mice hypomorphic for Atr have increased DNA damage and abnormal checkpoint response - Ryan L. Ragland; Martin F. Arlt; Elizabeth D. Hughes; Thomas L. Saunders; Thomas W. Glover (Mammalian Genome, 2009)

Hox cluster duplication in the basal teleost Hiodon alosoides (Osteoglossomorpha) - Karen E. Chambers; Ryan McDaniell; Jeremy D. Raincrow; Maya Deshmukh; Peter F. Stadler; Chi-hua Chiu (Theory in Biosciences, 2009)

Targeted transgene integration in plant cells using designed zinc finger nucleases - Charles Q. Cai; Yannick Doyon; W. Michael Ainley; Jeffrey C. Miller; Russell C. DeKelver; Erica A. Moehle; Jeremy M. Rock; Ya-Li Lee; Robbi Garrison; Lisa Schulenberg; Ryan Blue; Andrew Worden; et al. (Plant Molecular Biology, 2009)

Interaction of nickel and manganese in accumulation and localization in leaves of the Ni hyperaccumulators Alyssum murale and Alyssum corsicum - C. Leigh Broadhurst; Ryan V. Tappero; Timothy K. Maugel; Eric F. Erbe; Donald L. Sparks; Rufus L. Chaney (Plant and Soil, 2009)

Heterogeneity of Thermal Extremes: Driven by Disturbance or Inherent in the Landscape - Ryan F. Limb; Samuel D. Fuhlendorf; Darrel E. Townsend (Environmental Management, 2009)

MUlti-Dimensional Spline-Based Estimator (MUSE) for Motion Estimation: Algorithm Development and Initial Results - Francesco Viola; Ryan L. Coe; Kevin Owen; Drake A. Guenther; William F. Walker (Annals of Biomedical Engineering, 2008)

Allometric scaling of isometric biceps strength in adult females and the effect of body mass index - Robert F. Zoeller; Eric D. Ryan; Heather Gordish-Dressman; Thomas B. Price; Richard L. Seip; Theodore J. Angelopoulos; Niall M. Moyna; Paul M. Gordon; Paul D. Thompson; Eric P. Hoffman (European Journal of Applied Physiology, 2008)

Intestinal adenomagenesis involves core molecular signatures of the epithelial–mesenchymal transition - Xiaodi Chen; Richard B. Halberg; Ryan P. Burch; William F. Dove (Journal of Molecular Histology, 2008)

Thaxtomin biosynthesis: the path to plant pathogenicity in the genus Streptomyces - Rosemary Loria; Dawn R. D. Bignell; Simon Moll; José C. Huguet-Tapia; Madhumita V. Joshi; Evan G. Johnson; Ryan F. Seipke; Donna M. Gibson (Antonie van Leeuwenhoek, 2008)

Autoradiographic and Scintillation Analysis of 5-Aminolevulinic Acid Permeation Through Epithelialised Tissue: Implications for Topical Photodynamic Therapy of Superficial Gynaecological Neoplasias - Paul A. McCarron; Ryan F. Donnelly; A. David Woolfson (Pharmaceutical Research, 2008)

Neurotoxicity in Alzheimer’s disease: is covalently crosslinked Aβ responsible? - Ryan Naylor; Andrew F. Hill; Kevin J. Barnham (European Biophysics Journal, 2008)

First direct landscape‐scale measurement of tropical rain forest Leaf Area Index, a key driver of global primary productivity - David B. Clark; Paulo C. Olivas; Steven F. Oberbauer; Deborah A. Clark; Michael G. Ryan (Ecology Letters, 2008)
Leaf Area Index (leaf area per unit ground area, LAI) is a key driver of forest productivity but has never previously been measured directly at the landscape scale in tropical rain forest (TRF). We used a modular tower and stratified random sampling to harvest all foliage from forest floor to canopy top in 55 vertical transects (4.6 m 2 ) across 500 ha of old growth in Costa Rica. Landscape LAI was 6.00 ± 0.32 SEM. Trees, palms and lianas accounted for 89% of the total, and trees and lianas were 95% of the upper canopy. All vertical transects were organized into quantitatively defined strata, partially resolving the long‐standing controversy over canopy stratification in TRF. Total LAI was strongly correlated with forest height up to 21 m, while the number of canopy strata increased with forest height across the full height range. These data are a benchmark for understanding the structure and functional composition of TRF canopies at landscape scales, and also provide insights for improving ecosystem models and remote sensing validation.

Immunocolloidal Targeting of the Endocytotic Siglec-7 Receptor Using Peripheral Attachment of Siglec-7 Antibodies to Poly(Lactide-co-Glycolide) Nanoparticles - Christopher J. Scott; Waleed M. Marouf; Derek J. Quinn; Richard J. Buick; Selinda J. Orr; Ryan F. Donnelly; Paul A. McCarron (Pharmaceutical Research, 2008)

A majority of cotton genes are expressed in single-celled fiber - Ran Hovav; Joshua A. Udall; Einat Hovav; Ryan Rapp; Lex Flagel; Jonathan F. Wendel (Planta, 2007)

Neuronal expression of peripherin, a type III intermediate filament protein, in the mouse hindbrain - Meagan Barclay; Peter G. Noakes; Allen F. Ryan; Jean-Pierre Julien; Gary D. Housley (Histochemistry and Cell Biology, 2007)

Comparing functional assessments of wetlands to measurements of soil characteristics and nitrogen processing - Thomas E. Jordan; Mary Pittek Andrews; Ryan P. Szuch; Dennis F. Whigham; Donald E. Weller; Amy Deller Jacobs (Wetlands, 2007)

Threshold effects of coastal urbanization onPhragmites australis (common reed) abundance and foliar nitrogen in Chesapeake Bay - Ryan S. King; William V. Deluca; Dennis F. Whigham; Peter P. Marra (Estuaries and Coasts, 2007)

Lateral ball interception: hand movements during linear ball trajectories - Ryan Arzamarski; Steven J. Harrison; Alen Hajnal; Claire F. Michaels (Experimental Brain Research, 2007)

A gene family of putative immune recognition molecules in the hydroid Hydractinia - Ryan S. Schwarz; Linda Hodes-Villamar; Kelly A. Fitzpatrick; Matthew G. Fain; Austin L. Hughes; Luis F. Cadavid (Immunogenetics, 2007)

Can parasites be indicators of free-living diversity? Relationships between species richness and the abundance of larval trematodes and of local benthos and fishes - Ryan F. Hechinger; Kevin D. Lafferty; Todd C. Huspeni; Andrew J. Brooks; Armand M. Kuris (Oecologia, 2007)

Wood CO 2 efflux in a primary tropical rain forest - MOLLY A. CAVALERI; STEVEN F. OBERBAUER; MICHAEL G. RYAN (Global Change Biology, 2006)
The balance between photosynthesis and plant respiration in tropical forests may substantially affect the global carbon cycle. Woody tissue CO 2 efflux is a major component of total plant respiration, but estimates of ecosystem‐scale rates are uncertain because of poor sampling in the upper canopy and across landscapes. To overcome these problems, we used a portable scaffolding tower to measure woody tissue CO 2 efflux from ground level to the canopy top across a range of sites of varying slope and soil phosphorus content in a primary tropical rain forest in Costa Rica. The objectives of this study were to: (1) determine whether to use surface area, volume, or biomass for modeling and extrapolating wood CO 2 efflux, (2) determine if wood CO 2 efflux varied seasonally, (3) identify if wood CO 2 efflux varied by functional group, height in canopy, soil fertility, or slope, and (4) extrapolate wood CO 2 efflux to the forest. CO 2 efflux from small diameter woody tissue ( 2 efflux from stems >10 cm was related to both surface area and volume. Wood CO 2 efflux showed no evidence of seasonality over 2 years. CO 2 efflux per unit wood surface area at 25° ( F A ) was highest for the N‐fixing dominant tree species Pentaclethra macroloba , followed by other tree species, lianas, then palms. Small diameter F A increased steeply with increasing height, and large diameter F A increased with diameter. Soil phosphorus and slope had slight, but complex effects on F A . Wood CO 2 efflux per unit ground area was 1.34±0.36 μmol m −2 s −1 , or 508±135 g C m −2 yr −1 . Small diameter wood, only 15% of total woody biomass, accounted for 70% of total woody tissue CO 2 efflux from the forest; while lianas, only 3% of total woody biomass, contributed one‐fourth of the total wood CO 2 efflux.

Reconciling Carbon-cycle Concepts, Terminology, and Methods - F. S. Chapin; G. M. Woodwell; J. T. Randerson; E. B. Rastetter; G. M. Lovett; D. D. Baldocchi; D. A. Clark; M. E. Harmon; D. S. Schimel; R. Valentini; C. Wirth; J. D. Aber; et al. (Ecosystems, 2006)

Nitrous Oxide Emissions from a Fertilized and Grazed Grassland in the South East of Ireland - B. P. Hyde; M. J. Hawkins; A. F. Fanning; D. Noonan; M. Ryan; P. O’ Toole; O. T. Carton (Nutrient Cycling in Agroecosystems, 2006)

Human Strategies for Coping with El Niño Related Drought in Amazônia - Emilio F. Moran; Ryan Adams; Bryn Bakoyéma; Stefano Fiorini T.; Bruce Boucek (Climatic Change, 2006)

Developmentally regulated expression of the P2X3 receptor in the mouse cochlea - Lin-Chien Huang; Allen F. Ryan; Debra A. Cockayne; Gary D. Housley (Histochemistry and Cell Biology, 2006)

Molecular Confirmation of the Position of Gossypium trifurcatum Vollesen - Ryan A. Rapp; Ines Alvarez; Jonathan F. Wendel (Genetic Resources and Crop Evolution, 2005)

The introduced ribbed mussel (Geukensia demissa) in Estero de Punta Banda, Mexico: interactions with the native cord grass, Spartina foliosa - Mark E. Torchin; Ryan F. Hechinger; Todd C. Huspeni; Kathleen L. Whitney; Kevin D. Lafferty (Biological Invasions, 2005)

Reduced growth of autumn-sown wheat in a low-P soil is associated with high colonisation by arbuscular mycorrhizal fungi - Megan H. Ryan; Anthony F. van Herwaarden; John F. Angus; John A. Kirkegaard (Plant and Soil, 2005)

Challenges in Monitoring the Natural Attenuation of Spatially Variable Plumes - Ryan D. Wilson; Steven F. Thornton; Douglas M. Mackay (Biodegradation, 2004)

Environmental change and oyster colonization within the Hudson River estuary linked to Holocene climate - S. M. Carbotte; R. E. Bell; W. B. F. Ryan; C. McHugh; A. Slagle; F. Nitsche; J. Rubenstone (Geo-Marine Letters, 2004)

Phototoxicity of 5-Aminolevulinic Acid in the HeLa Cell Line as an Indicative Measure of Photodynamic Effect After Topical Administration to Gynecological Lesions of Intraepithelial Form - Paul A. McCarron; Ryan F. Donnelly; Brendan F. Gilmore; A. David Woolfson; Raymond McClelland; Agnieszka Zawislak; John H. Price (Pharmaceutical Research, 2004)

Recent occurrence of Cylindrospermopsis raciborskii in Waikato lakes of New Zealand - E. F. Ryan; D. P. Hamilton; G. E. Barnes (New Zealand Journal of Marine and Freshwater Research, 2003)
Cylindrospermopsis raciborskii is a toxin‐producing species of cyanobacteria that in autumn 2003 was recorded for the first time in three shallow (max. depth ≤5 m) Waikato lakes and a hydro‐electric dam on the Waikato River, New Zealand. It formed water blooms at densities >100 000 cells/ml in Lakes Waahi and Whangape. Net rates of population growth >0.2 day –1 were recorded for C. raciborskii in Lakes Ngaroto, Waahi, and Karapiro, based on comparisons of low numbers (detection of 15 000 cells/ml) in the subsequent sample “x”‐“y” days later. C. raciborskii may be well adapted to rapid proliferation in the Waikato lakes, which are eutrophic to hypertrophic, with high light attenuation, and where nitrogen (N) fixation may provide it with a competitive advantage over non‐nitrogen fixing algae under N‐limited conditions.

Eastern and Western Poor Cod ( Trisopterus minutus capelanus ) Populations in the Mediterranean Sea: Evidence from Allozyme and Minisatellite Loci - Valeria Mattiangeli; Anthony W. Ryan; Paul Galvin; Jarle Mork; Thomas F. Cross (Marine Ecology, 2003)
Nine allozyme and two minisatellite loci were used to investigate potential genetic differentiation among three samples of Mediterranean poor cod, Trisopterus minutus capelanus , from the Gulf of Lion, the Tuscan Archipelago and the Aegean Sea. Both types of markers showed consistent results, with F ST values of 0.0262 and 0.0296 (P

The relationship between tree height and leaf area: sapwood area ratio - N. McDowell; H. Barnard; B. Bond; T. Hinckley; R. Hubbard; H. Ishii; B. Köstner; F. Magnani; J. Marshall; F. Meinzer; N. Phillips; M. Ryan; et al. (Oecologia, 2002)

Separating the effects of intra- and interspecific age-structured interactions in an experimental fish assemblage - Ryan C. Taylor; Joel C. Trexler; William F. Loftus (Oecologia, 2001)

Allozyme analyses of the genus Trisopterus : taxonomic status and population structure of the poor cod - V. Mattiangelli; E. A. Bourke; A. W. Ryan; J Mork; T. F. Cross (Journal of Fish Biology, 2000)
Genetic analysis of the four Trisopterus (Gadidae) taxa suggests that the interrelationships of the two morphs of poor cod ( T. minutus minutus in the Atlantic and T. minutus capelanus in the Mediterranean) should be reconsidered. The Mediterranean poor cod T. m. capelanus is more closely related to bib T. luscus than to the Atlantic poor cod, so the population structure in the Atlantic and Mediterranean poor cod must be considered separately. Among 635 Atlantic individuals there was some evidence of poor cod population differentiation (allele frequency heterogeneity test P F ST =0·0135, P ≤0·0005). Levels of genetic variation were similar to those reported for related gadoid species. Some differentiation was present on the Norwegian coast (samples from Trondheimsfjord) and between the Faeroe Islands (Faeroe Bank) and the adjacent European coastal location. In contrast no statistically significant population differentiation was evident in Mediterranean poor cod, but fewer samples and individuals were screened.

Mast cells as a target in the treatment of rheumatoid arthritis - Olga Bakharevski; Peter F. J. Ryan (Inflammopharmacology, 1999)

Identification of a new quantitative trait locus on Chromosome 7 controlling disease severity of collagen-induced arthritis in rats - Svetlana V. Dracheva; Elaine F. Remmers; Pércio S. Gulko; Yutaka Kawahito; Ryan E. Longman; Van R. Reese; Grant W. Cannon; Marie M. Griffiths; R. L. Wilder (Immunogenetics, 1999)

A genetic linkage map of rat Chromosome 15 derived from five F 2 crosses - Jennifer S. Shepard; Elaine F. Remmers; Stephen Chen; Lisa Chang; Yutaka Kawahito; Pércio S. Gulko; Bina Joe; Ryan E. Longman; Svetlana Dracheva; Lynn Ge; Jianping Wang; Van R. Reese; et al. (Mammalian Genome, 1999)

A genetic linkage map of rat chromosome 20 derived from five F 2 crosses - Y. Kawahito; Elaine F. Remmers; R. L. Wilder; Ryan E. Longman; Pércio S. Gulko; Jianping Wang; Stephen Chen; Lisa Chang; V. R. Reese; Svetlana Dracheva; Lynn Ge; Jean H. Hoffman; et al. (Immunogenetics, 1998)

Reduced-Form Modelling of Surface Water and Soil Chemistry for the Tracking and Analysis Framework - R. Sinha; M. J. Small; P. F. Ryan; T. J. Sullivan; B. J. Cosby (Water, Air, & Soil Pollution, 1998)

Fibromyalgia antirheumatic drug trials: Effects of a standardized instructional videotape on the reliability of observer-dependent outcome measures - N. Bellamy; R. Buchbinder; S. Hall; P. Lowthian; M. R. Patrick; P. F. J. Ryan; A. Stockman; G. Grant; S. Green; J. Campbell (Inflammopharmacology, 1997)

Asymmetrical turbid surface-plume deposition near ice-outlets of the Pleistocene Laurentide ice sheet in the Labrador Sea - Reinhard Hesse; Saeed Khodabakhsh; Ingo Klaucke; William B. F. Ryan (Geo-Marine Letters, 1997)

The clonal and population structure of a rare endemic plant, Wyethia reticulata (Asteraceae): allozyme and RAPD analysis - D. R. Ayres; F. J. Ryan (Molecular Ecology, 1997)
Genetic structure arises when limited gene flow between populations favours the development of distinct arrays of genetic characters within each population. Determining the spatial scale at which this differentiation occurs is critical to our understanding of population biology and microevolution of species. The genetic structure and spatial pattern of genetic variation in an endemic, clonal perennial, Wyethia reticulata E. Greene, was investigated using random amplified polymorphic DNA (RAPD) markers and allozyme alleles. Large stands (250–360 m 2 ) were found to contain few genetic individuals. Despite the small population sizes and endemism of the species, W. reticulata was highly diverse genetically, with most of the variation (75–81%) distributed within populations. A population structure in full agreement with spatially defined populations was achieved only by combining RAPD and allozyme markers. Analysis using both types of markers appeared to provide estimates of genetic similarity between individuals that were most consistent with empirical data on plant distributions. We postulated that large, long‐lived clones dominated genetic relationships within populations but also provided opportunities for gene flow between populations on a longer time scale. The two marker types yielded different estimates of between‐individual similarity and revealed disparate patterns of population structure. This result will arise because allozymes and random DNA segments have dissimilar evolutionary dynamics with respect to mutation and selection.

Elimination of polychlorinated dibenzofurans (PCDFs) and polychlorinated biphenyls (PCBs) from human blood in the Yusho and Yu-Cheng rice oil poisonings - John J. Ryan; Dan Levesque; Luz G. Panopio; Wing F. Sun; Yoshito Masuda; Hiroaki Kuroki (Archives of Environmental Contamination and Toxicology, 1993)

Meningococcal serotypes in Canada, 1977?1984 - F. E. Ashton; J. A. Ryan; B. B. Diena (Antonie van Leeuwenhoek, 1986)

s of papers presented at the 63rd annual PAA meeting - Jose L. Rueda; Donald Berrios; W. R. Amoros; H. A. Mendoza; Jose Gil Archuleta; Gene D. Easton; C. R. Brown; Doug Bruce; Elsa Camadro; S. J. Peloquin; J. R. Davis; W. B. Jones; et al. (American Journal of Potato Research, 1979)